Sustainable valorization of rice husks into silicon carbide for high performance anti-corrosion coatings - Junjie Li; Peng Gao; Jie Li; Wenrui Hu; Yun Xia; Luxin Wang; Yida Wang; Xiaoyan Cui; Jun Zhao; Jianqiang Chen (Biomass and Bioenergy, 2027)

Multi-omics framework reveals molecular determinants of small peptide trileucine enhancing ethanol stress tolerance in industrial yeast - Xiaofan Jin; Lingyun Li; Mingwei Shao; Jun Ding; Yun Chen; Haifeng Zhao (Bioresource Technology, 2026)

Secondary metabolites from the heartwood of Toxicodendron vernicifluum (Stokes) F. A. Barkley (Anacardiaceae) and their chemotaxonomic significance - Cai-Wen Meng; Chun-Zhi Zhao; Jie Liu; Wen-Jing Zu; Hong-Yun Bai; Jian-Yu Liu; Yong-Nan Xu; Mei-Chen Li (Biochemical Systematics and Ecology, 2026)

Candosins A-L: potential antiparkinsonian agents from Candolleomyces sp. - Tong-De Zhao; Xue-Qiong Yang; Wei Chen; Hua Xu; Yan-Wei Yin; Yun-Li Zhao; Ya-Bin Yang; Zhong-Tao Ding (Phytochemistry, 2026)

Experimental study on fatigue performance of circular tubular column-to-H-shaped beam welded and cast steel connections - Fei Xu; Yuanbo Wang; Yun Zhao; Shuai Li; Jielong Zhu; Yongbo Shao (Engineering Structures, 2026)

Study on the mechanical behavior of helical anchors in soft soil sites under horizontal cyclic loading - Hang Cen; Zhong-ling Zong; Yun-han Huang; De-long Huang; Shi-li Ma; Jun-nan Zhao (Computers and Geotechnics, 2026)

Highly selective CO2/H2 separation by isomeric CALF-20-based porous slurry - Han Tang; Jin Cai; Zi-Ying Zhao; Long-Long Xie; Ping-Xiang Wang; Yang Meng; Hai-Hang Qin; Peng Xiao; Bei Liu; Yun-Lei Peng; Chang-Yu Sun; Zhi Li; et al. (Chemical Engineering Journal, 2026)

AM fungal and rhizobacteria jointly enhance vegetable waste decomposition in soils and harvest environmental and agronomic benefits in dryland - Muhammad Maqsood Ur Rehman; Sidra Khattak; Ling Zhao; Yun-Li Xiao; Ying Zhu; Awais Iqbal; Rafi Ullah; Nang Chang; Muhammad Abrar; Jian-Ming Li; Hao Sun; Adnan Khan; et al. (Agriculture, Ecosystems & Environment, 2026)

A pair of newly isolated terpenylated coumarins from Notopterygium incisum roots with anti-inflammatory activity - Li-Lian Zhao; Fei-Yuan Deng; Li Huang; Wei-Jun Dong; Wei-Zhen Dong; Li-Jun Huang; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2026)

Two new acylated iridoid glycosides with insulin resistance-improving activity from Scrophularia ningpoensis - Wen-Ying Zhou; Yu-Xin Peng; Bi-Qing Zhao; Hong-Yu Jiang; Xi-Ning Sun; Guang-Yun Su; Li Li; Xiao-Jiang Zhou (Phytochemistry Letters, 2026)

An undescribed tirucallane-type triterpenoid with anti-inflammatory activity from Ailanthus altissima - Zhong-Fu Wang; Xiang Guo; Li Huang; Li-Lian Zhao; Jie Li; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2026)

Aspergthones A and B, hybrids of dehydrosterigmatocystin with phenolic derivatives, isolated from the endophytic fungus Aspergillus versicolor VDL117 - Shan Hu; Mei Yang; Zhi-Yu Zhang; Yun-Xian Li; Xiao-Qin Yang; Wei-Hua Wang; Ying-Jun Zhang; Ping Zhao; Guo-Lei Zhu (Phytochemistry Letters, 2026)

Cadmium isotopes record tectonic control of tropical reef productivity in the South China Sea since the Late Oligocene - Yuru Zhao; Jie Li; Gang Li; Xiaowei Zhu; Zhaoyang Wang; Qiaohui Zhong; Yun Luo; Huiwen Huang; Jody M. Webster; Yang Lu; Hongqiang Yang; Weihai Xu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Thermal degradation mechanism of the 1,2,3-trichlorobenzene as PCDD/Fs precursor by waste polyurethane - Pu Lyu; Yun Xue; Jinhui Li; Dongliang Zhao; Yifei Sun; Linpeng Du; Yuan Chen; Jia Peng; Xiaohua Zhu; Songtao Yang; Huanliang Lu; Peiling Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

Unlocking efficient Li recovery from spent LiFePO4 batteries at high pulp density: Passivation release mechanism of Fe3+-mediated biochemical synergistic leaching and life cycle assessment - Ziyun Liang; Jinghan Gu; Xin Zhao; Lang Yun; Shenghan Li; Zaiyu Li; Wenyan Liu; Jiali Wang; Yao Wang; Xiaoyu Han (Journal of Environmental Chemical Engineering, 2026)

Multimodal machine learning reveals strain-specific flavor and kinetic dynamics in chinese spicy cabbage fermentation - Weiye Cheng; Qingyang Zhang; Xingye Sun; Xuan Wang; Yun Cen; Qiang Zhao; Hansheng Gong; Kanghee Ko; Wenli Liu; Xiaoping Liu; Huamin Li (Food Research International, 2026)

Rhamnolipids: from biosynthesis to applications - Ai-Ping Pang; Zhiqing Zhang; Guo-Zhao Li; Yun Wang; Kun Yang; Junping Zhou; Lianggang Huang; Li-Qun Jin; Zhi-Qiang Liu; Yu-Guo Zheng (Food Chemistry, 2026)

PFAS exposure is associated with retinal neurotoxicity in Chinese adolescents: Mechanistic insights from integrated toxicogenomic and in vitro analyses - Xing-Xuan Dong; Shi-Yi Gong; Yu-Hui Hu; Gang Liang; Hua Xu; Dan-Lin Li; Yun Zhao; Chen-Wei Pan (Environmental Pollution, 2026)

A novel self-assembling peptide-based fibrous delivery system integrating physical barrier and sustained drug release for enhanced therapeutic efficacy in allergic rhinitis - Yu Liu; Ai Yang; Tingmei Lyu; Yun Hong; Xuting Zhou; Yuxia Chang; Binhao Zhao; Zhiyan Zhang; Fei Qin; Baoping Jiang; Li Wu; Gaohong Lyu; et al. (Chemical Engineering Journal, 2026)

Machine learning for prediction and experimental validation of hydrochar characteristics via co-hydrothermal carbonization of sewage sludge and pomelo peel - Jie Li; Chenhui Xie; Junjie Li; Wenrui Hu; Yun Xia; Luxin Wang; Yida Wang; Xiaoyan Cui; Jun Zhao; Qianqian Shang; Jianqiang Chen (Bioresource Technology, 2026)

Methylome and transcriptome profiles reveal the importance of glycometabolism in thermal plasticity of large yellow croaker - Yanfei Yang; Yichen Li; Yidi Wu; Baohua Chen; Ji Zhao; Qiaozhen Ke; Weiqiang Zheng; Yun Li; Tao Zhou; Peng Xu; Ning Li (Aquaculture, 2026)

A synthetic microbial community for the enhanced removal of complex emerging pollutants from domestic wastewater - Ting Xu; Hui Yun; Yuru Zhao; Yue He; Siyu Chen; Ting Ma; Wenjie Zhang; Liang Peng; Xiangkai Li (Journal of Hazardous Materials, 2026)

A Porous Zn-Salen-Based Organic Ionic Polymer as a Robust Bifunctional Catalyst for CO2 Fixation via Epoxide Cycloaddition - Guo-Ling Li; Rui-Yao Qin; Meng-Meng Wang; Qing Li; Shijian Lu; Jin-Shui Su; Qi Zhang; Yun Zhao; Ran Zhang; Zhong-Hai Ni (Journal of Environmental Chemical Engineering, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Removal of antibiotics by an oleaginous green microalga Chromochloris zofingiensis under photoautotrophic, heterotrophic and mixotrophic conditions - Kai-Lu Cao; Juan Peng; Meng-Zhen Li; Lin-Yun Liao; Zi-Wen Song; Hong-Zhi He; Jun Zhao (Algal Research, 2026)

High-stability active thermal control for nanosatellite payload under multi-timescale disturbances via temperature response decomposition and energy-adaptive error fusion - Qi-Yuan Liu; Yun-Ze Li; Yan-Ao-Ming Xi; Kai-Feng Chang; Ya-Hui Chen; Ran Wei; Yu-Peng Zhou; Xin Zhao (Advances in Space Research, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Coordinated cross-system recovery framework for large-scale metro stations under extreme flooding - Hai-Yun Li; Huan-Feng Duan; Dong-Mei Zhang; Xu-Wei Zhao (Tunnelling and Underground Space Technology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Early thermal pulses drive interfacial pre-aging and plastisphere pre-shaping: An overlooked pre-conditioning pathway in PLA microplastic aging during composting - Yanping Zhang; Youzhao Wang; Chaoyue Zhao; Fuxin Yang; Xu Li; Shujie Hou; Bingzhen Li; Zhengnan Zhu; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Journal of Hazardous Materials, 2026)

Probing oxidation of hydroxy-polycyclic aromatic hydrocarbons at air-water interface in water microdroplets - Xiaohui Shi; Jiahui Huang; Siyu Zhu; Yuexin Zhang; Pei Liu; Bo Li; Hong Zhang; Yun Ju; Jing Zhao; Jie Jiang; Jing He (Journal of Hazardous Materials, 2026)

Heteroatom-induced d-p orbital hybridization enables efficient non-radical degradation in tetracycline wastewater - Zehui Fan; Wen Yang; Shuyi Yang; Xianyi Zhao; Chong Peng; Tiezhu Zhang; Yun Li; Tao E (Journal of Environmental Chemical Engineering, 2026)

Ion-specific phase behaviors of gluconate aerosols regulated by alkali metal counter-cations: a supramolecular network stiffness perspective - Mengyun Shi; Wenjing Li; Shufeng Pang; Fei Zhao; Yun-Hong Zhang (Journal of Environmental Sciences, 2026)

Magnetotactic bacteria antagonized lead toxicity: Distinct detoxification mechanisms in magnetosome-containing/deficient bacteria - Ruoyun Dong; Yuting Ding; Han Li; Yanan Zhao; Yuanyuan Wu; Chenxi Zhou; An Xu; Yun Liu (Journal of Environmental Sciences, 2026)

Quantifying the environmental and health benefits of ship emission control policies in Guangdong of China - Zhiruo Cheng; Yun Zhu; Zhaoxin Dong; Ji-cheng Jang; Zhiqiang You; Jia Xing; Bin Zhao; Jiabin Li; Ziyi Liu; Wang Chang (Environmental Pollution, 2026)

CHBP-loaded mesoporous polydopamine nanoparticles attenuate neuroinflammation and reprogram microglia-neuron crosstalk for spinal cord injury repair - Linyi Xiang; Jiacheng Zhang; Yuzhe Wu; Jingwei Shi; Yun Shu; Ruize Miu; Jiayi Zhao; Junsheng Zhu; Zhichao Tao; Yibo Geng; Haojie Zhang; Zhenglin Li; et al. (Chemical Engineering Journal, 2026)

A homogenized gridded climate dataset for China - Kaicun Wang; Hongze Cai; Yanyi He; Yun Li; Hanmeng Xia; Changjian Yin; Hongyong Yu; Runze Zhao; Zhengtai Zhang; Chunlüe Zhou (Science China Earth Sciences, 2026)

Hymenobacter Biocrusticola sp. nov., Isolated from Desert Biocrust - Yanying Zhao; Xinyue Yun; Kai Tang; Yumeng Li; Runze Bao; Fuying Feng (Current Microbiology, 2026)

Substrate type and structural complexity drive macrobenthic diversity of coral reefs in the South China Sea - Peng-Jin Zhu; Li-Sha Hu; Zhan-Wei Zhao; Hong-Qiang Yang; Min Hui; Ze-Lin Chen; Yun-Wei Dong (Coral Reefs, 2026)

A novel passive external surface heat flow balance strategy for high-temperature-stability nano CubeSat thermal design: concepts, models and thermal control effect evaluations - Yan-Ao-Ming Xi; Yun-Ze Li; Qi-Yuan Liu; Kai-Feng Chang; Xin Zhao; Yu-Peng Zhou; Ran Wei (Advances in Space Research, 2026)

Endothelial VEGFR2 insufficiency promotes the transition of lymphatic to hematopoietic transcriptional programs - Taotao Li; Xudong Cao; Fei Zhou; Xiujuan Li; Wenjuan Ma; Xiuyan Zhang; Haoyu Zhong; Beibei Xu; Man Chu; Xiwen Jia; Kai Ding; Xin Shen; et al. (Angiogenesis, 2026)

Two newly isolated compounds from Hansenia weberbaueriana and their anti-inflammatory potential - Jie Li; Su Hu; Li Huang; Li-Lian Zhao; Li-Jun Huang; Wei-Jun Dong; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

Association between aperiodic activity and impulsivity in individuals with methamphetamine use disorder - Yun Zhao; Jing Li; Jie Zhang; Ying Cheng; Zhihua Shen; Yongguang Wang (Psychopharmacology, 2026)

A previously undescribed 3,4-secodammarane derivative from Ailanthus altissima - Yu-Sha Shi; Li-Lian Zhao; Li Huang; Su Hu; De-Feng Peng; Zhuo-Hong Li; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

A new flavonol glycoside isolated from the stems and leaves of Astragalus membranaceus - Jia-Xin Zhao; Yun Zang; Pei Li; Jia-Ning Zhang; Si-Qi Yang; Hui-Feng Li; Yan Wang; Jin-Yan Tan; Ying-Li Wang; Yan-Gang Cheng (Natural Product Research, 2026)

Chemical composition of the endogenous fungus Fusarium sp. L-3 derived from Chinese Qinan agarwood - Ming-Li Han; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Na Xiao; You-Xing Zhao (Natural Product Research, 2026)

Two new monoterpene glycosides from the endophytic fungus Diaporthe nobilis and their cytotoxic effects - Ying Chen; Jian Wang; Cai-Lin Zhao; Xiu-Feng Yang; Jin Ye; Lin-Ping Zhang; Yun-Xiao Li; Fan-Wei Liu; Le Zhang; Bo Song (Natural Product Research, 2026)

Construction of Pt-TiOx interfacial sites via Pt-TiO2 metal-support interaction for efficient catalytic dehydrogenation of methylcyclohexane - Zhengjian Li; Mingzhi Wang; Shumin Liu; Huayue Yang; Yun Zhao; Lin Gu; Guangxu Chen (Science Bulletin, 2026)

PGDM: Physically guided diffusion model for land surface temperature downscaling - Huanyu Zhang; Bo-Hui Tang; Tian Hu; Yun Jiang; Zhao-Liang Li (Remote Sensing of Environment, 2026)

Benzylisoquinoline alkaloid dimers with antitumor activities from Thalictrum wangii B. Boivin - Qiong Jin; Xue-Meng Liu; Dao-Min Liu; Xiao-Lei Shi; Qiong Yang; Yun-Li Zhao; Li-Xing Zhao; Zhi Dai; Xiao-Dong Luo (Phytochemistry, 2026)

Undescribed and nephroprotective diterpenoids from Daphne genkwa - Hong-Bo Ye; Xian-Run Wu; Li Wang; Hui-Zhen Peng; Yu Duan; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2026)

Proteomic analysis of outer membrane vesicles derived from Vibrio parahaemolyticus causing translucent post-larvae disease - Lihan Wang; Shengwen Li; Dianli Zhao; Mengyu Duan; Yi Cao; Yun Wei; Mengqiang Wang (Journal of Invertebrate Pathology, 2026)

Corrigendum to “Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting” [J Hazard Mater 503 (2026) 141080] - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Ion trapping as an intrinsic physicochemical barrier limiting plant translocation and phytotoxicity of ionizable contaminants - Zhi-Yu Lu; Jia-Heng Zhao; Li Yuan; Yan-Yun Hu; Yi Hu; Cheng-Yuan Liu; Yang Pan; Chun-Chun Lv; Ke-Ke Qi; Wei Zhi; Guo-Ping Sheng (Journal of Environmental Sciences, 2026)

Operational optimization of deep borehole heat exchangers: Numerical evidence on cross-seasonal heat storage mitigating ground cold accumulation - Jiachen Wang; Chao Li; Chao Jiang; Liguo Zhao; Jiale Wu; Yun Wang (Geothermics, 2026)

An experimental and kinetic modeling study of the autoignition delay times of triethyl phosphite - Frederick Nii Ofei Bruce; Yuke Gao; Ruining He; Zhihan Zhu; Xin Wang; Yilin Zhao; Mengmeng Jia; Jiaxin Xie; Xin Bai; Yun Hin Taufiq-Yap; Chong-wen Zhou; Henry Curran; et al. (Fuel, 2026)

Establish a cultured meat model with adjustable muscle-to-fat ratios based on muscle satellite cells and fibroadipogenic progenitor cells in an optimized gelatin-mTG scaffold - Liu Shuqin; Tao Shaoying; Bo Chunjie; Du Zhiwen; Zhao Xiaoyu; Yun Yuan; Gao Yuxin; Liao Hongyi; Song Lishuang; Bai Chunling; Yang Lei; Li Guangpeng; et al. (Food Chemistry, 2026)

Tidal level seasonally modulates sediment organic carbon in seagrass meadows of tropical lagoon bays - Xiao-Ya Zhang; Hui-Jue Luo; Qian-Wei Li; Mu-Qiu Zhao; Zhen Ni; Yun-Feng Shi; Yin-Liu Wang; Yu-Chao Li (CATENA, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Shifting from concentration-based to health-oriented air pollution control in China - Zhaoxin Dong; Shuxiao Wang; Haotian Zheng; Fenfen Zhang; Shengyue Li; Yueqi Jiang; Jia Xing; Dian Ding; Dejia Yin; Qian Song; Bin Zhao; Yun Zhu; et al. (Science Bulletin, 2026)

Predictive wave compensation under saturation constraints via residual attention LSTM and quadratic programming - Dezhao Pang; Xuan Yun; Jingtao Li; Chen Zhang; Tieshi Zhao (Ocean Engineering, 2026)

Vacancy-regulated type-I 2D b-AsP/g-C3N4 heterojunction with local polarization electric field for efficient carbon dioxide photocatalytic reduction - Jiaqi Song; Yanjie Liang; Yong Ke; Yunyan Wang; Yun Li; Qingwei Wang; Feiping Zhao; Jia Zhou; Xiaoyu Huang; Xiaobo Min; Liyuan Chai; Cong Peng (Journal of Environmental Chemical Engineering, 2026)

2024 ice-snow storm caused substantial forest canopy degradation in central-eastern China: Evidence from ICESat-2 and multi-source observations - Bingjie Yu; Xinyan Zhong; Wenqiong Zhao; Xia Wang; Xiaodong Li; Fei Xiao; Yun Du; Yihang Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

An experimental study on the ignition and combustion characteristics of ultrafine boron particles - Ruining He; Xin Bai; Xuan Ren; Yilin Zhao; Xin Wang; Jinhu Liang; Fei Qin; Ce Sun; Taufiq Yap Yun Hin; Chong-Wen Zhou; Henry J Curran; Yang Li (Fuel, 2026)

DeepLrn-Source: Deep learning powered landslide source identification - Lu-Yu Ju; Ze-Ning Zhao; Shi-Hao Xiao; Yuan-En Pang; Jian He; Yun-Hong Lv; Ruo-Chen Jiang; Xin He; Li-Min Zhang (Engineering Geology, 2026)

CdS incorporation induced gate-opening in UiO-66-NH2 for photocatalysis - Qi Li; Bryan Kit Yue Ng; Zhao-Xue Luan; Ping-Luen Baron Ho; Daniel Woodside; Xiyu Zhang; Christopher Foo; Pu Zhao; Tai-Sing Wu; Yun-Liang Soo; Mingjie Li; Xin-Ping Wu; et al. (Chemical Engineering Journal, 2026)

A self-adaptive biomimetic cocoon regulating gut microbiota for enhanced prodrug activation in IBD therapy - Qingling Song; Junfei Yang; Chuangxi Zhou; Xiaocui Wu; Yunfei Li; Beiyang Xue; Liming Bai; Yun Zhang; Hongjuan Zhao; Lei Wang (Chemical Engineering Journal, 2026)

Radiative cooling coatings and natural ventilation in urban street canyons: Synergies and trade-offs - Cheng-Peng Ma; Yu-Fei Tang; Shang-Xian Zhao; Gui-Xiong Yang; Fu-Yun Zhao; Yuguo Li; Rongpeng Zhang (Building and Environment, 2026)

Intercellular Mitochondrial Transfer as Endogenous Neuroprotection: Mechanisms and Therapeutic Implications in Ischemic Stroke - Yun-Fan Zhang; Di Zhao; Jing-Jing Wei; Xiao Liang; Liu-ding Wang; Jia-Wei Wang; Li-bin Jiang; Ju-Ying Chen; Yun-Ling Zhang; Yue Liu (Translational Stroke Research, 2026)

Exosomal Protein Biomarkers for Predicting Early Neurological Deterioration Following Intravenous Thrombolysis in Acute Ischemic Stroke - Jiamin Li; Zixin Wang; Yingnan Zhou; Xinyi Wang; Qi Kong; Jiameng Li; Boyi Yuan; Yun Chen; Wan Wang; Jiapeng Zhao; Jinming Sheng; Haiping Zhao; et al. (Translational Stroke Research, 2026)

Impact of land use transition on ecosystem services in the Yangtze River economic belt and associated mechanism - Youzhi An; Mengsha Fan; Zhihao Tao; Peng Zhao; Hualin Chen; Da Li; Yun Wu; Qiuju Wu; Jin Sun; Feng Xu; Fengtai Zhang (Environment, Development and Sustainability, 2026)

Robust Noise Identification and Data Reconstruction for Marine Magnetotelluric Time-Domain Data using STA/LTA and Compressive Sensing with Orthogonal Matching Pursuit - Yun-sheng Zhao; Ming-zhen Zhang; Min-gui Cai; Yan Gao; Zhan-xiang He; Jian-ping Li (Applied Geophysics, 2026)

Microscopic Hydraulic–Mechanical Coupling Fracturing Behavior and Failure Mechanisms of Reservoir Rocks - Zhi Zhao; Zhi-Hong Li; Yun-Gang Duan; Liang-Fu Xie; Zheng Li; Guo-Feng Yu; Xiao-Ping Zhou (Rock Mechanics and Rock Engineering, 2026)

Talarombrevisone A, an β -aminopropionate with two polyketide units, isolated from an endophytic fungus Talaromyces brevis - Yun-He Tuo; Zhong-Duo Yang; Jian-Guo Chen; Cui-Juan Xu; Lin-bo Liu; Tian-Kun Zhao; Yue Li; Li-Bin Xia; Shuai Yu; Ai-Hong Zhao; Shuo Li (Natural Product Research, 2026)

Cross-system modeling and analysis of cascading failure propagation in large-scale metro stations under extreme flooding events - Hai-Yun Li; Dong-Mei Zhang; Huan-Feng Duan; Xu-Wei Zhao (Tunnelling and Underground Space Technology, 2026)

Chronic exposure to F-53B disrupts sperm quality and steroidogenic regulation in male rats - Xueying Wang; Aiqing Wang; Hao Xu; Shan Shan; Xiaohan Li; Yan Zhang; Jun Wang; Kexin Jiang; Hailin Tian; Yun Zhao (Toxicology Letters, 2026)

Positive Atlantic Multidecadal Oscillation–La Niña synergy enhances recent East Asian dust activity via hydrothermal anomalies - Ruibo Zhao; Xiaoming Feng; Changjia Li; Yun Yang; Lindsay C. Stringer; Bojie Fu (Science Bulletin, 2026)

Magnetic biochar-assisted high-solid anaerobic digestion of chicken manure: Focusing on its mitigation mechanisms of ammonia inhibition - Xiaoyong Li; Shilei Wang; Xi Wang; Yun He; Shuai Li; Shiru Li; Jinmeng Chen; Zhi Wang; Xiaoling Zhao; Yafan Cai; Jingliang Xu; Hanjie Ying (Fuel, 2026)

Simulation and prediction of post-harvest ripening processes for tomatoes with different ripeness levels based on electrical characteristics - Yun Wu; Zhenwei Chang; Yinhe Chen; Jieyu Xian; Yongnian Zhang; Zhao Li; Xiaochan Wang; Yinlong Zhu (Food Chemistry, 2026)

Targeting STING activation in antigen-presenting cells via natural polysaccharide-engineered vesicles for antitumor immunotherapy - Tian-Yang Wang; Lang Zhao; Geng-Hui Feng; Jing-Yun Su; Shao-Hua Zhuo; Yan-Mei Li (Chemical Engineering Journal, 2026)

Mutation of BrDAD1 affects flower opening and anther dehiscence by regulating jasmonate-mediated BrMYB108-BrSWEET15 module - Tianer Tang; Zifan Zhao; Shunuo Li; Shanshan Ren; Qingli Hou; Luyao Zhang; Chong Tan; Yun Zhang; Xueling Ye; Zhiyong Liu (Theoretical and Applied Genetics, 2026)

TaGα knockout in wheat causes early heading and short organ length, with dose-dependent effects through various pathways - Yun Li; Wenwen Zhao; Xinya Peng; Yunlong Liang; Ruiying Xue; Jianming Liu; Zhike Xu; Dong Cao; Baolong Liu (Theoretical and Applied Genetics, 2026)

Higher aridity in alpine grasslands discourages soil organic carbon accumulation by microorganisms - Jia Li; Xia Wang; Ya Rong Zhang; Ya Zhen Li; Meng Han Yuan; Yun Fei Zhao; Wen Hui Duan; Jie Yi Xia; Zi Yang Niu (Plant and Soil, 2026)

Antimicrobial polyketides from an endophytic fungus Arcopilus aureus HJ-7 from Ardisia mamillata Hance - Li-Qi Liang; Xian-Hua He; Chun-Yan Wei; Jing-Xian Zhao; Qian Wu; Min Liang; Jun Li; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2026)

Two new aromatic meroterpenoids from the fruiting bodies of Ganoderma calidophilum - Wei Liu; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Phytochemistry Letters, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Engineering yolk-shell nanoreactors for advanced catalytic ozonation: Dual optimization of confinement effects and metal synergy for enhanced antibiotic degradation - Haoxing Yun; Yingying Mao; Haocheng Jiang; Tian Tian; Wenhui Li; Chenyu Zhao; Chaohai Wang; Wenxian Wei; Weichuan Qiao; Ming Zhang (Journal of Environmental Chemical Engineering, 2026)

A new pair of lunar gabbroic meteorites record magma recharge at ∼ 3.0 Ga - Peiyi Li; Yun Jiang; Kai Zhao; Shiyong Liao; Xiaochao Che; Xinru Zhang (Geochimica et Cosmochimica Acta, 2026)

Research progress on the structure of edible fungi polysaccharides and their anti-obesity mechanisms via the regulation of intestinal microbiota and metabolites - Xin Wei; Weiya Rong; Liyang Jin; Limin Zhang; Daoqin Ren; Yue Jiang; Jinling Cao; Shaojun Yun; Feier Cheng; Wenfei Zhao; Yong Li; Mingchang Chang; et al. (Food Bioscience, 2026)

Corrigendum to “All-trans-retinoid acid (ATRA) suppresses chondrogenesis of rat primary hind limb bud mesenchymal cells by downregulating p63 and cartilage-specific molecules” [Environ. Toxicol. Pharmacol. 38(2) (2014) 460–468] - Yun-guo Wang; Peng Xie; Yun-gong Wang; Xue-dong Li; Tao-gen Zhang; Zhao-yong Liu; Quan Hong; Shi-xin Du (Environmental Toxicology and Pharmacology, 2026)

In situ cultivation and chromogenic screening: a dual approach for rapid discovery of PDE1 inhibitors from pinus-tree associated microbes - Cui-Juan Xu; Shuo Li; Zhong-Duo Yang; Lin-Bo Liu; Yun-He Tuo; Yong-Jiao Niu; Lei-Lei Chen; Jian-Guo Chen; Tian-Kun Zhao; Ai-Hong Zhao (World Journal of Microbiology and Biotechnology, 2026)

Effects and Possible Mechanisms of Dietary Bile Acids on the Liver of Spotted Sea Bass (Lateolabrax maculatus) - Ziyi Zhao; Yonghang Zhang; Haishen Wen; Yun Li; Hailiang Wang; Mengqun Liu; Kaiqiang Zhang; Xin Qi (Journal of Ocean University of China, 2026)

Predatory performances and adaptive strategies of Eocanthecona furcellata (Hemiptera: Pentatomidae) to the larvae of Phauda flammans (Lepidoptera: Phaudidae) - Jian-Zhong Ning; Da-Xing Lu; Xiong Zhao He; Xiao-Yun Wang; Kai Lin; Jun Li; Xia-Lin Zheng (Applied Animal Behaviour Science, 2026)

Nutrient levels drive the functional trait assembly for periphytic algae colonization in two plateau lakes - Yun Zhang; Bárbara Dunck; Jishu Guo; Wenfang Li; Yihan Zhao; Yanling Li; Yimin Huang; Wen Xiong; Kui Xu (Aquatic Sciences, 2026)

Daphnoretin as a potent sortase A inhibitor effectively disarms drug-resistant Staphylococcus aureus infections - Yun Sun; Tong Zhao; Dongbin Guo; Peitong Jiang; Xinyao Liu; Zhangyu Du; Luanbiao Sun; Yuan Gao; Han Gao; Li Wang; Bingmei Wang; Ming Yan (World Journal of Microbiology and Biotechnology, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

In vitro screening and in vivo evaluation of anti-virulence herbal compounds against Streptococcus agalactiae in tilapia (Oreochromis niloticus) - Ming-Li Xiang; Zi-Chen Zhao; Gui-Hua Li; Wei Tang; En-Peng Chen; Shui-Feng Qin; Yan Wang; Heng-Wei Deng; Zhi-Hong Zhong; Yun Sun; Wei-Liang Guo; Yong-Can Zhou (Aquaculture, 2026)

Effects of multi-environmental factors on rhizosphere microbial community structure of Paeonia lactiflora Pall. and its interaction mechanism with medicinal quality - Feifei Yang; Bingzhen Li; Shuwen Zhao; Yun Hu; Ming Li; Xiaoming Zhang; Yujie Song (Rhizosphere, 2026)

SiGSTU18 positively regulates saline-alkali tolerance in foxtail millet through glutathione metabolism and glutamic acid-mediated alleviation of oxidative stress and ion toxicity - Yun Li; Yuxue Zhao; Fuxing Xiang; Fangying Chen; Yanrui Xu; Xiaohu Lin; Jihan Cui; Yucui Han (Plant Science, 2026)

Ammonia-induced exosomal miRNA disrupts autophagy and promotes lung injury: Therapeutic potential of natural compounds - Yun Han; Shiying Li; Jian Yang; Felix Kwame Amevor; Md. Ahsanul Kabir; Xiaoling Zhao; Yingjie Wang (Journal of Hazardous Materials, 2026)

Controls on heavy metal variability in a coastal mountainous river: Impacts of tides, typhoons, and anthropogenic activities - Yalong Li; Ni Su; Yun Zhao; Ergang Lian; Chao Li; Juan Xu; Ping Yin; Shouye Yang (Journal of Geochemical Exploration, 2026)

Capsaicin, allicin, and 6-gingerol: Modulation of gut microbiota and impact on metabolic, immune, and neurobiological health in mice - Liyuan Yun; Shengnan Li; Tiantian Zhao; Jinpeng Zhang; Lalita Siriwattananon; Min Zhang (Food Research International, 2026)

Effects of wheat starch and gluten protein interaction on fried flour products during processing - Mengyue Li; Guifang Huang; Hao Cheng; David Julian McClements; Jianwei Zhao; Yun Ma; Zhengyu Jin; Long Chen (Food Hydrocolloids, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

A net-like colloid with peculiar CO2 sorption behavior formed by aggregation of organic ligand molecules in water - Jin Cai; Wan Chen; Hai Li; Xin Zheng; Han Tang; Ming-Ke Yang; Zi-Xuan Huang; Zi-Ying Zhao; Peng Xiao; Yun-Lei Peng; Xian-Ren Zhang; Long-Long Xie; et al. (Chemical Engineering Journal, 2026)

Molecular mechanisms of Aflatoxin B1-Induced renal injury and the detoxification potential of Taraxasterol: A review - Chenyuan Wang; Xinyu Zhao; Yansong Wang; Hanshuo Li; Yun Shi; Yilong Cui (Chemico-Biological Interactions, 2026)

Multi-omics evidence reveals acetogenesis as the primary metabolic bottleneck under ammonia stress - Yun Peng; Chunyan Lin; Hengyi Liu; Lei Li; Xuya Peng; Di Wu; Xiaofei Zhao (Bioresource Technology, 2026)

Highly Active Probiotic Yogurt Against Cyclophosphamide-Induced Immunosuppression in Mice by Regulating Immune Response and Gut Microbiota - Liyuan Yun; Jinpeng Zhang; Tiantian Zhao; Qian Li; Shuguang Fang; Xiaojuan Guo; Yanfeng Wu; YunJiao Zhao; Min Zhang (Probiotics and Antimicrobial Proteins, 2026)

Solidago canadensis alters rhizosphere bacterial communities of Artemisia argyi under warming and nitrogen deposition—invaded rhizospheres become similar to the invader's - Yong-Feng Wang; Yun-Long Zhang; Ying Li; Guang-Qian Ren; Shan-Shan Qi; Bi-Ying Zhao; Zhi-Cong Dai; Dao-Lin Du (Plant and Soil, 2026)

Nr4a2, A Key Factor Controlling the Development and Functional Maintenance of Forebrain Car3 Neurons - Yun-Chao Tao; Li Zhao; Qiong Zhang; Xi-Yue Liu; Wei-Tang Liu; Ze-Xuan Li; Ling Hu; Lei Zhang; Jia-Yin Chen; Yu-Qiang Ding; Ning-Ning Song (Neuroscience Bulletin, 2026)
Nr4a2 ( Nurr1 ) is well known to be vital for midbrain dopaminergic neurons. Recent single-cell RNA analyses reveal that Nr4a2 is expressed in lateral cerebral regions, within neurons named L4/L5/L6 IT Car3 . These neurons have attracted intense attention for the molecular mechanisms underlying their development and functions. We classified Car3 neurons into neocortical (Ncx- Car3 ), claustral (CLA- Car3 ), and dorsal endopiriform nucleus (dEn- Car3 ) subpopulations, focusing on the characterization of Ncx- Car3 neurons. These neurons exhibit distinct birthdates and migratory morphologies compared to CLA- and dEn- Car3 neurons, but share a common transcriptomic profile when Nr4a2 is deleted at the embryonic stage or in adulthood. Notably, Nr4a2 misexpression ectopically induces Car3 -enriched genes in vivo . Mice lacking Nr4a2 in Car3 ensembles during the embryonic stage or in adulthood display hyperactivity and reduced anxiety-like behaviors. Therefore, our results demonstrate that Nr4a2 is a key factor in regulating the development and functional maintenance of the forebrain Car3 neurons.

P- and S-Wave Poynting Vectors Derived from the Divergence and Curl Mode Separation for Elastic Wave Reverse Time Migration - Nan Hu; Min-gui Cai; Yang-guang Yin; Yun-sheng Zhao; Hao Li; Jun-wu Li; Bing-feng Zhou (Applied Geophysics, 2026)

Effects of temperature change pattern on the hatching of zooplankton resting eggs and community structure - Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Han Zhu; Yi-Long Xi (Hydrobiologia, 2026)

Spatial-temporal patterns and multi-scale drivers of allergenic pollen Fraxinus, Platanus and Humulus in the urban and suburban area of Beijing, China - Xiaoxin Qin; Jianqin Xu; Yiyin Li; Xiao Yun; Hongxing Zhang; Wenjun Liu; Xinyi Zhao; Nan Lin (Urban Forestry & Urban Greening, 2026)

Suffusion in shield tunnel surrounding soils under train vibration using an improved DEM-PNM coupling method - Si-Rui Chen; Dong-Mei Zhang; Xiao-Chuang Xie; Zhao-Geng Chen; Hui-Hao Chen; Hai-Yun Li (Tunnelling and Underground Space Technology, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Urban expansion drives both loss and compensation in city vegetation productivity - Xinyue Liu; Tianshan Zha; Charles P.-A. Bourque; Peng Liu; Hongxian Zhao; Tingshan Li; Xinhao Li; Yun Tian; Xin Jia (Journal of Environmental Sciences, 2026)

Riverbank line migration dynamics and channel evolution processes along the Tarim River in China - Yun Zhao; Lin Li; Quanli Zong; Kai Jin; Chunxia Liu; Peng Qin; Xiuzhi Zhu (Journal of Arid Environments, 2026)

Combustion dynamic characteristics of biodried products derived from sewage sludge biodrying - Xuewen Zhu; Yiren Zhang; Changheng Li; Mengying Yun; Zhong Zhao; Zhikun Zhang; Jiao Ma; Boxiong Shen; Wenwen Kong; Zhuozhi Wang (Fuel, 2026)

Insights into the delaying mechanism of taro-based yogurt on the retrogradation of the frozen part-baked bread: Starting with strain screening - Yun Li; Jinhui Wang; Mingyu Zhao; Cailin Kong; Jianhui Xiao; Jin Tu; Liya Niu (Food Research International, 2026)

Sugarcane polyphenols modulate gut microbiota and odor-associated metabolites during in vitro fecal fermentation of elderly - Hongye Li; Yun Bian; Yi Wu; Xueqing Hang; Mengqing Zhang; Luchuan Gao; Yifei Dong; Tanhang Mu; Wei Zhao (Food Bioscience, 2026)

Hydrological and water quality gradients shape the structure and network complexity of planktonic diatom community in river-lake confluence zones during flood regulation - Xing Liu; Zhenzhen Wang; Dandan Ding; Pan Yu; Yun Li; Guanpin Yang; Baohua Zhu; Yan Zhao; Janne Soininen; Kehou Pan (Environmental Research, 2026)

Hydrogen crossover in proton exchange membrane water electrolysis: Effects of membrane type, temperature and pressure - Yutong Zhao; Tongzhou Li; Wei Wang; Jun Chi; Wei Song; Yun Zhao; Hongmei Yu; Huisheng Wu; Zhigang Shao (Chemical Engineering Journal, 2026)

Injectable anti-inflammatory nanofiber hydrogel reprograms immunosuppressive tumor microenvironment via cascade-amplified immunogenic cell death - Ruo-Yun Zhang; Wei Yue; Yang Xuan; Long Qi; Lin-Lin Guo; Zhen-Zhen Zhu; Ming Yang; Zhang-Jie Pu; Guo-Qiang Li; Xin-Yi Mao; Ding Zhou; Zhao-Wei Zhang (Chemical Engineering Journal, 2026)

Preparation of multifunctional lignocellulosic microcapsules-protectants for high-efficiency green control of fusarium crown rot in wheat - Haonan Zhang; Yun Fang; Bin Yu; Zhengang Xie; Qiuyu Xiong; Donglai Zhang; Zifeng Yang; Zerui Li; Jingli Cheng; Jinhao Zhao (Chemical Engineering Journal, 2026)

Research progress on the chemical composition changes of traditional Chinese medicine before and after processing based on modern analytical techniques - Xuelin Zong; Yun Shi; Ying Zhao; Yuman Li; Rong Guo; Gengyi Shang; Chenfeng Zhang; Jinyang Shen; Xun Gao; Weidong Li; Kunming Qin (Phytochemistry Reviews, 2026)

Plasma MicroRNA and Protein Signature Associated with Obesity in the Chinese Han Population Using MicroRNA Omics and Proteomics Analysis of 1026 Subjects - Yun-Xia Xie; Jian-Ge Qiu; Zhao-Hui Yang; Chen Ding; Le-Ming Shi; Si-Jia Wang; Li Jin; Bing-Hua Jiang (Phenomics, 2026)

Contrasting temperature responses of photosynthesis and respiration amplify reduction in carbon sink under water stress conditions in a temperate semi-arid steppe - Xinhao Li; Tianshan Zha; Peng Liu; Xin Jia; Yun Tian; Hongxian Zhao; Jinshi Jian; Na Deng (Agricultural and Forest Meteorology, 2026)

Isolation and antibacterial activity of three new flavonol compounds from Sophora flavescens - Si-Han Wang; Xiang-Yu Zhao; Zhi-Kang Chen; Yun Gao; Xin-Min Li; Ya-Juan Gao; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2026)

Lanostane triterpenoids from the fruiting bodies of Ganoderma multipileum and their anti-inflammatory activities - Mei-Juan Li; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Natural Product Research, 2026)

Two new compounds isolated from an endophytic fungus Eutypella sp. XLE005 derived from Conus leopardus - Xin-Ming Li; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Du-Qiang Luo; You-Xing Zhao (Natural Product Research, 2026)

Cochliomycin H, a new 12-membered resorcylic acid lactone from sponge-derived fungus Curvularia sp. ZYX-Z-4 - Jiu-Jiu Zhou; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; You-Hua Liu; Zhao You-Xing (Natural Product Research, 2026)

Persteroid, a new steroid from the marine-derived fungus Penicillium sp. ZYX-Z-143 - Lu-Ting Dai; Li Yang; Zi-Peng Wang; Jiao-Cen Guo; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Zhi-Fang Yu; You-Xing Zhao (Natural Product Research, 2026)

Coupling iron oxide with iron single-atom catalyst promotes neutral electrochemical nitrate reduction from water - Jinshan Wei; Xihui Lu; Hexing Lin; Shao-Qing Liu; Xiaoxiao Wei; Meng Sun; Gang Liu; Chengzhi Hu; Liangjie Wang; Huazhang Zhao; Ya-yun Li (Water Research, 2026)

From inhalation to systemic damage: Decoding the mechanistic cascade of silica nanoparticle-induced multi-organ toxicity - Jia-Qi Ban; Li-Hong Ao; He-Qun Gu; Yun-Geng Wei; Qiong Tian; Xiu He; Hua Zhao; Jun Li (Toxicology, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Alstoniaschines A‒I, nine undescribed alkaloids from Alstonia scholaris and their potential medicinal effects on diabetic nephropathy - Wen-Jie Sun; Shi-Shi Qin; Xian-Run Wu; Yun-Li Zhao; Xu-Jie Qin; Xiao-Dong Luo (Phytochemistry, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

A carbon sink calculation model for concrete buildings considering time-variant environment - Jia-cheng Xu; Bei Li; Ye Tian; Ruo-yi Zhao; Guo-yi Zhang; Qiang Zeng; Cong-cong Ma; Bo-Tao Huang; Hong-jing Xue; Yun-jian Li; Qing Cai (Environmental Impact Assessment Review, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

Multiple bonds in quasi-solid copolymeric electrolyte for ultra-stable zinc ion batteries - Caixia Li; Hanqi Zhao; Jichao Geng; Yun Chen; Teng Yu; Haojie Liang; Xianxian Shi; Longwei Yin; Xiaobin Hui; Lei Wang (Chemical Engineering Journal, 2026)

Inversion of hourly NOx emissions through air quality monitoring data and deep learning response surface modeling - Ziyi Liu; Yun Zhu; Ji-cheng Jang; Zhaoxin Dong; Jia Xing; Bin Zhao; Jinying Li; Qipeng Wen; Dian Ding; Yujie Qin (Atmospheric Environment, 2026)

Load-Bearing Behavior of Composite Rock Strata Anchorage Systems Under Multi-factor Conditions and Uniform Confining Pressure - Pandong Zhang; Zhiqiang Zhao; Zilong Hui; Yao Li; Qinglong Yun; Kang Zhou (Rock Mechanics and Rock Engineering, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

Deep learning-based high precision 3D ultrasound imaging for large size organ - Enxiang Shen; Qiyue Zhou; Caozhe Li; Haoyang Wang; Jie Yuan; Yun Ge; Ying Chen; Kanglian Zhao; Weijing Zhang; Di Zhao; Zhibin Jin (Medical & Biological Engineering & Computing, 2026)

Global patterns and drivers of canopy storage capacity in different biomes - Meng-Di Wu; Zhi-Yun Jiang; Si-Yi Zhang; Yu-Jun Ma; Shui-Xia Li; Shu-Qin Han; Jin-Zhao Liu (Agricultural and Forest Meteorology, 2026)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Spatiotemporal variation of bacterial β-diversity under ecological water replenishment in a Yellow River Delta coastal river: Contributions and assembly mechanisms of rare and abundant subcommunities - Xing Liu; Dandan Ding; Yanfang Xu; Xiaoqiu Yu; Hao Dong; Yun Li; Guanpin Yang; Baohua Zhu; Yan Zhao; Kehou Pan (Marine Pollution Bulletin, 2025)

Chi-miR-146a promotes the propagation of Neospora caninum by targeting the TGF-β1/SMAD2 pathway - Jin-Ming Chen; Jing-Yu Li; Jia-Yi Jin; Xiao-Qi Bao; De-Liang Tao; Xiao-Yun Zhao; Jun-Ke Song; Xin Yang; Ying-Ying Fan; Guang-Hui Zhao (Veterinary Parasitology, 2025)

Different detoxification strategies of fruit borers adaptation to quercetin - Bing Bai; Huan-Juan Zhao; Bo-Kun Wang; Yu-Ting Li; Ping Gao; Yun-Tong Lv; Xue-Qing Yang (Pesticide Biochemistry and Physiology, 2025)

HPLC-UV guided isolation of anti-inflammatory polyacetylene glucosides from Carthamus tinctorius L. - Yong-Xiang Wang; Jia-Xu Bao; Ran Wang; Xian Zhang; Yun-Fang Zhao; Peng-Fei Tu; Hui-Xia Huo; Jun Li (Phytochemistry, 2025)

Spatiotemporal pattern of vegetation evolution in northeastern Tibetan Plateau during the Cenozoic and its climatic significance - Yun-Xia Jia; Wen-Chao Zhang; Li-Jun Tian; Zhi-Lin He; Zhao Wang; Qing-Chun Tian (Palaeoworld, 2025)

Unraveling the relationship between surface deformation and groundwater dynamics in karst terrains using multi-source remote sensing data - Songwei Gu; Yun Zhou; Yinghong Jing; Zhengjia Zhang; Jinshi Shao; Li Shuai; Jiangzhaoxia Chen; Yinjun Zhao; Xiaojun She; Yao Li (Journal of Hydrology, 2025)

Soil moisture estimation from satellite-derived temporal signals in the thermal domain with an improved parameterization scheme - Yun-Jing Geng; Pei Leng; Abba Aliyu Kasim; Xiaoning Song; Zhao-Liang Li (Journal of Hydrology, 2025)

Filamentous cyanobacterium Spirulina platensis mediates phosphate biomineralization for efficient fluoride immobilization and drives metabolic shift toward stress resistance and biomineralization - Linlin Cui; Zhilian Liu; Jun Suo; Yun Liu; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Journal of Hazardous Materials, 2025)

Simultaneous determination of three fluorinated pesticides and a metabolite in various food processing matrices and chronic dietary risk assessments - Tian Yang; Dandan Yun; Lin Li; Mengying Zhao; Jun Yan; Lin Yang; Zhiqiang Kong; Minmin Li (Food Chemistry, 2025)

Interactions between proteins and polyphenols in plant-based food: Insight of allergenicity and off-flavor reduction - Xinjue Lai; Yun Li; Weijie Lan; Lei Zhao; Kai Wang; Zhuoyan Hu; Xuwei Liu (Food Chemistry, 2025)

Proteomic insights into DEM-induced oxidative stress: Glycolytic and antioxidant synergy in beef colour stability - Cai-Yun Li; Wen-Jun Zhao; Ya-Ning Qu; Yu-Bin Zhang (Food Chemistry, 2025)

Exploring the toxicological network of bleomycin-induced pulmonary fibrosis: The role of long non-coding RNAs - Bingxin Li; Hongbin Shi; Yun Ma; Ruining Zhao; Haijun Zhang (Food and Chemical Toxicology, 2025)

Functional characterization of two Caspase-1 transcripts that associated with ASC and NLRC3 in apoptosis and inflammatory response in large yellow croaker Larimichthys crocea - Qiu Yu Hu; Kun Huang Han; Qiu Ye Huang; Wen Feng Cui; Qiao Yun Yang; Yi Dan Liu; Shang Qi Zhao; Xian Yuan Zeng; Ying Li; Wen Qi Zha; Yi Lei Wang; Yong Hua Jiang; et al. (Fish & Shellfish Immunology, 2025)

Three tetraspanins, Tspan1, Tspan2A and Tspan3 from Litopenaeus vannamei involved into Vibrio parahaemolyticus infection - Yi-Qian Zhang; Shuang-Shuang Luo; Xiu-Li Chen; Ai-Jin Wang; Chao-Jie Hou; Qing-Yun Liu; Min Peng; Chun-Ling Yang; Yan Lei; Wei-Lin Zhu; Hong Liu; Yong-Zhen Zhao; et al. (Fish & Shellfish Immunology, 2025)

In situ enhanced C O selective hydrogenation by hydrogen spillover effect over CeO2 modified Pt/SiC - Ji-Xiao Zhao; Yi Lu; Lei Li; Zhi-Feng Jiao; Xiang-Yun Guo (Chemical Engineering Journal, 2025)

DNMT1 inhibition improves the activity of memory-like natural killer cells by enhancing the level of autophagy - Yixun Li; Chong Guo; Fujia Zhang; Shenju Cheng; Yanhong Li; Shan Luo; Yun Zeng; Yaling Zhao; Kun Wu (Molecular Biology Reports, 2025)

IL-8 promotes pyroptosis through ERK pathway and mediates glucocorticoid resistance in chronic rhinosinusitis with nasal polyps - Wei Zhang; Yun Lei; Ting Zhang; Bo You; Jie Zhang; Yong Zhou; Shaocong Zhang; Xueru Li; Yuting Liu; Lianqin Shen; Jianmei Zhao; Jing Chen (Inflammation Research, 2025)

Knockout of SSIIa in waxy barley blocks starch biosynthesis and increases soluble sugar and Fructan accumulation - Yun Li; Ruiying Xue; Wenwen Zhao; Yanyan Jiang; Yongju Liu; Xinya Peng; Yunlong Liang; Dong Cao; Baolong Liu (Functional & Integrative Genomics, 2025)

TTI Medium Anisotropic Reverse Time Migration Imaging and Its Application in Oil and Gas Exploration in the Xihu Depression of the East China Sea - Shunli Gao; Peng Song; Yun Wei; Wenjun Wang; Jun Tan; Caixia Zhao; Shibo Mao; Jianghe Dong; Qingquan Li (Journal of Ocean University of China, 2025)

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

Plastispheres as unique niches for promoting turnover of dissolved organic matter in aquatic environments - Yan-Jun Liu; Zheng-Hao Li; Yan-Yun Hu; Jia-Heng Zhao; Li Yuan; Guo-Ping Sheng (Water Research, 2025)

Enhancement of nitrogen removal by Tubifex tubifex in saturated vertical flow constructed wetlands under antibiotic stress - Jiqiang Yang; Yani Zhang; Kees Jan van Groenigen; Zhangjun Liao; Dongyao Wang; Huan Yu; Xinyao Yan; Li Zhu; Jiamei Zhao; Lijun Liu; Hongmei Wang; Yun Chen (Journal of Environmental Management, 2025)

Cross-food-cultural study of metabolite differences in Asian spicy fermented pastes using combined CIL-LC-MS and GC–MS analysis - Jeonghyun Yun; Chi Zhao; Sunhee Kang; Pingping Zhou; Suyi Zhang; Chang-Won Cho; Zhihua Li; Jang-Eun Lee (Food Chemistry, 2025)

The function and application potential of L-theanine: From biotechnological production, biosynthesis, bioactivity to food industry - Jiayi Le; Lu Li; Caihong Wang; Qinglian Hu; Kan Shao; Yun Zhao; Yuanxiang Jin (Food Chemistry, 2025)

Amorphous MnO2 dispersing IrO2 for enhancing oxygen evolution reaction activity and stability at large current density in PEM water electrolysis - Wenzhuo Zhang; Jun Chi; Jiaxin Li; Yun Zhao; Zhigang Shao; Hongmei Yu (Chemical Engineering Journal, 2025)

Biochar-microorganisms hybrid enhanced anaerobic digestion: Innovative insight considering electron transfer potential and functional network of microorganisms - Yun He; Zhi Wang; Caihong Shen; Shilei Wang; Yiyang Liu; Xiaoyong Li; Xueke Bai; Junhao Zhao; Xiaoling Zhao; Xingyao Meng; Yafan Cai; Jingliang Xu; et al. (Bioresource Technology, 2025)

A novel acoustic barrier based on Chladni patterns and its optimal design - Qiao-Yun Wu; Qing-Jing Li; Lan Ding; Zhi-Feng Xu; Chun-Feng Zhao (Building and Environment, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

3D Magnetic resonance image denoising using nonlocal and nonconvex tensor train regularization - Li Wang; Yun Zhao; Liang Zhao; Bin Jiang; Qinling Xia (Medical & Biological Engineering & Computing, 2025)

Amplification effects of AM fungus and rhizobacteria on carbon efficiency in wheat-soil system under drought stress via priming rhizosphere activities - Muhammad Maqsood Ur Rehman; Ling Zhao; Sidra Khattak; Yun-Li Xiao; Awais Iqbal; Wasim Khan; Muhammad Abrar; Zheng-Guo Cheng; Shi-Sheng Li; Asfa Batool; Ying Zhu; You-Cai Xiong (Applied Soil Ecology, 2025)

Numerical Study on the Keying of Suction Embedded Plate Anchors with Chain Effects - Xue Li; Wei Yan; Yanbing Zhao; Yongye Li; Yan Zhang; Yun Lang (Journal of Marine Science and Engineering, 2025)
Suction embedded plate anchors are widely used in deepwater mooring systems, which can withstand significant vertical loading. During the installation, the mooring chain is tensioned and causes the anchor to rotate, which is known as keying. With a large deformation finite element approach of the coupled Eulerian–Lagrangian method, the chain effects are incorporated into the keying of suction embedded plate anchors. The effectiveness of the proposed method is verified by numerical results and centrifuge tests. The numerical study reveals that the installation angle of the chain has a significant effect on the loss of embedment, especially combined with the effects of load eccentricity and soil strength. The losses of embedment are 0.024~0.273 and 0.217~1.755 anchor width for the installation angles of 15° and 90°, respectively. The ultimate bearing capacity factor decreases with the increasing of load eccentricity and soil strength, because a cavity is formed at the anchor back. Empirical formulae are finally developed for engineers to rapidly estimate the embedment loss and ultimate pullout capacity of suction embedded plate anchors.

A remote sensing-based paradigm for revealing road ecological impacts in permafrost regions - Qingquan Sha; Jiawei Zhao; Lin Huang; Wei Cao; Jiahui Li; Liangxia Zhang; Yun Wang (Transportation Research Part D: Transport and Environment, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

A pair of lignans isolated from Trachelospermum jasminoides and their anti-inflammatory activity - Chen-Yi Yan; Miao Wang; Yu-Ting Mu; Li-Lian Zhao; Yu-Liang Guo; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2025)

Research and application mechanism of chlorination roasting for polymetallic minerals and waste - Zhi-yu Fan; Long Wang; Ren-yun Zhang; Yi-yong Wang; Ting-an Zhang; Xing-jian Wang; Ji-dong Li; Xin-xin Zhao; Wei-juan Li (Minerals Engineering, 2025)

Methane clumped isotopes of shallow gas hydrates in the Haima cold seeps, South China Sea: Implications for marine carbon cycling and sequestration - Haodong Chen; Jing Zhao; Qianyong Liang; Jiacheng Li; Junxi Feng; Xi Xiao; Zongheng Chen; Yun Li; Yongqiang Xiong (Marine and Petroleum Geology, 2025)

Simultaneous fluoride, calcium, and phosphorus removal by bacterial phosphate mineralization: Reaction pathways, mechanisms, and process optimization - Linlin Cui; Zhilian Liu; Jun Suo; Jue Kang; Yun Liu; Guanzhou Qiu; Hongbo Zhao; Li Shen (Journal of Environmental Chemical Engineering, 2025)

Highly selective hydrogenolysis of furfuryl alcohol to 1,5-pentanediol over an efficient Ni/PrOx catalyst - Yun Huang; Peipei Zhao; Kai Cui; Junwen Chen; Peng Wu; Xiaohong Li (Fuel, 2025)

Ceramic fiber aerogels based flexible solar steam generators enabling efficient thermal localization and high salt resistance - Yun Jiang; Yumin Liu; Lin Li; Zhibin Li; Pengzhang Li; Xianshu Qiao; Wenyan Zhao; Chuanjin Tian; Weiwei Sun; Yanhao Dong; Zhipeng Xie; Chang-An Wang (Desalination, 2025)

The dielectric permittivity modulation effect of phase engineering on SiC whiskers modified reduced graphene oxide composites - Yun-Tian Chen; Bo Cai; Chen-Ming Liang; Shu-Hao Yang; Pei-Yan Zhao; Wen-Ping Li; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

An ingenious structural design of NiCu-MOF bar-like nanosheet array: harnessing synergistic effects to attain exceptional ammonia oxidation performance - Guang-Lan Li; Yu-Hui Shi; Ri-Yang Huang; Tian-Ge Ma; Qian Zhuo; Ling Xu; Fei Jiang; Yu-Kun Zhai; Yong-Hou Xiao; Hong-Jiang Li; Yang Yan; Yun Zhao (Chemical Engineering Journal, 2025)

Contrasting patterns and drivers of soil microbial communities in high-elevation montane grasslands and deserts of the Qinghai-Tibetan plateau in China - Yulong Duan; Jianhua Zhao; Junbiao Zhang; Lilong Wang; Yun Chen; Xuyang Wang; Fasi Wu; Yuqiang Li (CATENA, 2025)

Transcriptomic evidence from peripheral blood reveals nonlinear gene expression trajectories of aging in female rhesus macaques - Chong-Jun Weng; Long-Bao Lv; Li-Qin Yang; Long Zhao; Zheng-Fei Hu; Si-Yu Ma; Yi-Jiang Li; Wen-Xian Xiao; Yun Wang; Xin-Tian Hu; Gong-Hua Li; Qing-Peng Kong (Science China Life Sciences, 2025)

Smartphone-integrated visual inspection for enhancing agricultural product quality and safety: a review - Lingyuan Xu; A. M. Abd El-Aty; Peipei Li; Jia Li; Jing Zhao; Xingmei Lei; Song Gao; Yun Zhao; Yongxin She; Fen Jin; Jing Wang; Shuting Wang; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Biocontrol efficiency and multiple mechanisms of Bacillus velezensis BV07 against postharvest green mold on citrus fruit - Chenyang Zhu; Juanying Huang; Mengyue Wu; GuangHao Li; Xiaoshuang Xia; Luning Zhao; Mahmoud Salah; Xinghua Zhou; Yun Wang (Postharvest Biology and Technology, 2025)

Resistance risk and mechanism of prochloraz in Fusarium solani - Xuewei Mao; Tangbo Cao; Liting Chen; Min Li; Xingchen Zhao; Hao Liu; Yun Duan; Li Wang; Lin Zhou (Pesticide Biochemistry and Physiology, 2025)

Nickel isotopic variations in Ni–Cu sulfide deposits: from theoretical predictions to natural observations - Zhuang Ma; Shui-Jiong Wang; Wenzhong Wang; Matthew J. Brzozowski; Yun Zhao; Shengchao Xue; Ruipeng Li; Shangguo Su; Jie Yang (Geochimica et Cosmochimica Acta, 2025)

Chitosan/PEO@Eu-MOF nanofiber membrane-based test strip for visual detection of tetracycline with smartphone-assisted analysis - Wei Pan; Zi-Han Zhu; Yan-Shen Zhao; Jie-Liu; Zhi-Guang Zhang; Gui-Xia Li; Tao Yu; Zhong-Zhi Han; Yun-Ze Long; Gui-Feng Yu (Chemical Engineering Journal, 2025)

Suspended microalgae biofilm particles driven by fluid shear force for high efficiency of livestock wastewater purification - Yun Huang; Zitao Zhao; Ai Song; Yabo Sun; Dongdong Li; Xianqing Zhu; Ao Xia; Xun Zhu; Qiang Liao (Chemical Engineering Journal, 2025)

Integrated multifunctional liquid metal enhanced hydrogel system for chronic infected wound with sinus tract treatment and monitoring - Chengxin Ruan; Jinxue Zhao; Jiale Jin; Dongdong Li; Dongyu Wang; Zhiyuan Luo; Peiyi Li; Apoorva Sinha; Tim-yun Michael Ong; Lidong Wu; Pengfei Lei (Chemical Engineering Journal, 2025)

Core-sheath-type TiO2@NH2-MIL-125(Ti) nanocone arrays for sensitive photoelectrochemical detection of carcinoembryonic antigen - Mengjia Zhou; Ziyan Cui; Yun Liu; Dan Wang; Yanzhou Li; Junwei Zhao; Wenwu You (Chemical Engineering Journal, 2025)

Mechano-kinetic integrated carbon coating enables fast-charging micro‑silicon anodes - Junwei Han; Xin Qin; Qian Xu; Lu Zhao; Debin Kong; Yun Cao; Fei Yang; Xia Hu; Yafei Wang; Mingxue Zuo; Huiyu Yu; Bocheng Yang; et al. (Chemical Engineering Journal, 2025)

Donor macrophage pyroptosis contributes to the development of aGVHD - Xueyan Sun; Qingyuan Qu; Qi Chen; Fengqi Liu; Haixia Fu; Yuxiu Chen; Menglin Li; Yun He; Xiaolu Zhu; Xiangyu Zhao; Yu Wang; Xiaojun Huang; et al. (Science China Life Sciences, 2025)

Rheinheimera fenheensis sp. nov., Isolated from Fenhe River Basin, China - Xuan Shao; Yun-Lin Peng; Jin-Hang Guo; Zhao-Tong Chen; Hua-Ming Zhong; Di Meng; Hong-Jian Hou; Xi-Ying Zhang; Yong Zhao; Yi Li (Current Microbiology, 2025)

Xanthine oxidase inhibitory constituents from the roots of Ampelopsis japonica - Yu-Lin Li; Fen Liu; Li-Yun Zhao; Han-Xiang Li; Aikebaier Jumai; Zhi-Fang Xu; Sheng-Xiang Qiu (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Antithrombotic macrocyclic sesquiterpene pyridine alkaloids from Tripterygium hypoglaucum - Qiong Jin; Jia-Shan Shen; Xian-Run Wu; Hui-Zhen Peng; Zi-Hao Fu; Li-Qiang Chen; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2025)

Remote sensing of root zone soil moisture: A review of methods and products - Abba Aliyu Kasim; Pei Leng; Yu-Xuan Li; Qian-Yu Liao; Yun-Jing Geng; Jianwei Ma; Yayong Sun; Xiaoning Song; Si-Bo Duan; Zhao-Liang Li (Journal of Hydrology, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Metabolomics analysis of osmotic tolerance enhancement mechanism of wheat gluten peptides on industrial yeast - Xiaofan Jin; Mingwei Shao; Jun Ding; Lingyun Li; Yun Chen; Haifeng Zhao (Food Chemistry, 2025)

Zinc-releasing adhesive oral patch for prevention of radiation-induced oral ulcerative mucositis - Xiang Li; Kai-Yan Wang; Wen Qin; Wei-Wei Yu; Xin-Yi Hao; Wen Niu; Xu-Fang Liu; Qing Liu; Jian-Hua Wei; Yao Zhao; Franklin R. Tay; Ling-Yun Xia; et al. (Chemical Engineering Journal, 2025)

Enlarged Perivascular Spaces (EPVS) Associated with Functional and Cognitive Outcome After Aneurysm Subarachnoid Hemorrhage (aSAH) - Haichao Wang; Qiuyue Yu; Wenyi Zhang; Shengqi Yao; Yun Zhang; Qiong Dong; Yichen Zhao; Jinxing Lin; Xueyuan Liu; Li Gong (Translational Stroke Research, 2025)

Biodegradation of Neonicotinoid Insecticides Thiacloprid and Thiamethoxam by Microorganisms: Metabolic Process, Metabolic Enzymes and Toxicity Assessments of their Metabolites - Yun-Xiu Zhao; Li-Wen Chen; Yue Shen; Hao Chen; Zi-Yan Yu; Chao Xing; Yi-Fei Chen; Peng-Fei Zhai; Jiu-Wei Song; Ju Yang (Current Microbiology, 2025)

Coupling Analysis of NMDS and PLS ‐ PM Approaches to Understanding β‐Diversity Trends - Yulong Duan; Junbiao Zhang; Evangelos Petropoulos; Jianhua Zhao; Rongliang Jia; Fasi Wu; Yun Chen; Lilong Wang; Xuyang Wang; Yulin Li; Yuqiang Li (Global Change Biology, 2025)
Our research further confirmed that the integrated analysis of NMDS and PLS‐PM methods effectively elucidates the trends in the divergence of bacterial and eukaryotic β‐diversity under soil acidification. image

Phage Therapy Enhances Survival, Immune Response, and Metabolic Resilience in Pacific White Shrimp (Litopenaeus vannamei) Challenged with Vibrio parahaemolyticus - Chao Zeng; Long Qi; Chao-Li Guan; Yu-Lin Chang; Yu-Yun He; Hong-Zheng Zhao; Chang Wang; Yi-Ran Zhao; Yi-Chen Dong; Guo-Fang Zhong (Fishes, 2025)
Acute hepatopancreatic necrosis disease (AHPND), caused by the bacterium Vibrio parahaemolyticus, is a major threat to global shrimp aquaculture. In this study, we evaluated the therapeutic effects of phage therapy in Litopenaeus vannamei challenged with AHPND-causing Vibrio parahaemolyticus. Phage application at various concentrations significantly improved shrimp survival, with the 1 ppm group demonstrating the highest survival rate. Enzymatic assays revealed that phage-treated shrimp exhibited enhanced immune enzyme activities, including acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM). In addition, antioxidant defenses such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and total antioxidant capacity (T-AOC) significantly improved, accompanied by reduced malondialdehyde (MDA) levels. Serum biochemical analyses demonstrated marked improvements in lipid metabolism, particularly reductions in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL), alongside higher levels of beneficial high-density lipoprotein (HDL). Transcriptomic analysis identified 2274 differentially expressed genes (DEGs), notably enriched in pathways involving fatty acid metabolism, peroxisome functions, lysosomes, and Toll-like receptor (TLR) signaling. Specifically, phage treatment upregulated immune and metabolic regulatory genes, including Toll-like receptor 4 (TLR4), myeloid differentiation primary response protein 88 (MYD88), interleukin-1β (IL-1β), nuclear factor erythroid 2-related factor 2 (Nrf2), and peroxisome proliferator-activated receptor (PPAR), indicating activation of innate immunity and antioxidant defense pathways. These findings suggest that phage therapy induces protective immunometabolic adaptations beyond its direct antibacterial effects, thereby providing an ecologically sustainable alternative to antibiotics for managing bacterial diseases in shrimp aquaculture.

Novel lineages of fungicolous Cordieritidaceae (Helotiales, Leotiomycetes) from southwest China - Feng-Ming Yu; Kandawatte Wedaralalage Thilini Chethana; Cui-Jin-Yi Li; Lei Lei; Jin-Rong Lu; Yi-Yun Guo; Qin-Yun Yang; Vinodhini Thiyagaraja; Qi Zhao (Mycological Progress, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Vibration damping and finite element analysis of a 10 MW jacket-type offshore wind turbine - Jigang Zhang; Haodong Sui; Zhehao Ma; Wenli Chen; Qingfeng Yan; Wei Li; Hongjian Xu; Fengbo Yu; Yun Niu; Junxian Zhao (Ocean Engineering, 2025)

Investigating pressure effects on oil stability in deep-buried strata via chemical kinetics - Jun Shi; Hua Wang; Huajun Gan; Zhao-Wen Zhan; Yun Li; Wenmin Jiang (Organic Geochemistry, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Effects of mono- and di-glycerides/phospholipids (MDG/PL) on the bioavailability of lutein and DHA in rats: more effective for lutein - Shu-zhen Huang; Huan-huan Yin; Fang Tian; Liang Wang; Wen-jing Wu; Xiang Li; Yanrong Zhao; Xiao-ya Wang; Yun Li; Megan Terp; Ying-yi Mao; Jin-yao Chen (Food Bioscience, 2025)

Development and evaluation of recombinant multi-epitopes vaccine against nervous necrosis virus - Chen Zhang; Wei-Nan Zhao; Xin-Xin Liu; Wen-Ye Song; Hai-Hua Peng; Min Yang; Peng-Fei Li; Jin-Qi Wei; Yong-Can Zhou; Yun Sun (Fish & Shellfish Immunology, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Successful application of microspore culture by adding kinetin and methylene blue to improve microspore embryogenesis in Chinese kale breeding - Haonan Li; Zhe Wang; Weina Zhou; Jinyan Li; Zifan Zhao; Chao Zheng; Zhiyong Liu; Yun Zhang (Protoplasma, 2025)

Preoperative Sleep Deprivation Exacerbates Anesthesia/Surgery-induced Abnormal GABAergic Neurotransmission and Neuronal Damage in the Hippocampus in Aged Mice - Yun Li; Siwen Long; Jiafeng Yu; Jingyu Feng; Shuqi Meng; Yize Li; Lina Zhao; Yonghao Yu (Molecular Neurobiology, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Vertical dynamic response of a pile in three-dimensional saturated soils considering construction disturbance - Chaofan Liu; Zhang-Long Chen; Yun Zhao; Jian-Ping Li; Wei Wang; Jiangtao Yi (Ocean Engineering, 2025)

Unveiling spatiotemporal patterns and key drivers of soil conservation from a “historical-future-intervention” perspective: A case study of the Danjiangkou Reservoir Area, China - Pengcheng Zhao; Lihui Wang; Xiaodi Zheng; Yang Li; Lijie Lu; Yunjie Yang; Jinliang Huang; Yun Du; Feng Ling (Journal of Environmental Management, 2025)

Rapid start-up and sustained performance of an anaerobic biofilm reactor for nitrogen removal in low C/N wastewater: Characterization and microbial community analysis of the PD/A process - Yuezhen Liang; Miao Liu; Rong Zhao; Kaiyu Hou; Xiaoqin Chen; Xiaojun Fan; Li Yu; Abuliti Abudula; Guoqing Guan; Yun Duan (Journal of Environmental Chemical Engineering, 2025)

In-situ hydrogen-mediated catalytic transfer hydrogenolysis of Kraft lignin for highly selective production of monomeric phenols - Han-Bing Gao; Bing-Hu Xie; Yue-Lun Wang; Le-Le Qiu; Yun-Peng Zhao; Jian Xiao; Mei Zhong; Jing Liang; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Recent duplications and rare structural variations revealed by comparative sequence analysis of low molecular weight glutenin subunits (LMW-GS) genes re-identified using LMWgsFinder in 26 genomes of the grass family - Shengli Zhang; Xiaojing Shan; Yun Wang; Tairui Lu; Daxing Xu; Han Gong; Yuchao Fan; Yuanyuan Guan; Junjie Zhao; Haili Sun; Dongfang Li; Haiyan Hu; et al. (Theoretical and Applied Genetics, 2025)

Simultaneous Prediction for Fracture Density and a New Fluid Influence Factor in Oil-Bearing Reservoirs - Yun Zhao; Xiaotao Wen; Chunlan Xie; Ziyu Qin; Yuqiang Zhang; Chenlong Li (Surveys in Geophysics, 2025)

Exploring the dosimetric advantages of a novel multi-modality radiotherapy platform in prostate cancer - Jie Duan; Qinghui Yun; Zhongfei Wang; Te Zhang; Xiaohuan Sun; Hua Yang; Weiwei Li; Wei Wang; Hongfei Sun; Liting Chen; Yue Gao; Zhiwei Wei; et al. (Physical and Engineering Sciences in Medicine, 2025)

Phytochemical investigation of Jie-Geng-Tang and regulatory role in the TNF-α pathway in mitigating pulmonary fibrosis using UPLC-Q-TOF/MS - Bingxin Li; Ruining Zhao; Xiaojie Jiang; Chang Liu; Yun Ma; Haijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Lifespan extension by rapamycin in Brachionus dorcas (Rotifera) is dose and developmental stage dependent - Ting Liu; Han-Bing Dong; Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Yi-Long Xi (Hydrobiologia, 2025)

Iron oxides accelerate soil electron transport to promote the degradation of organic pollutants: A review - Xin Yu; Yuewei Yang; Yun Zhang; Jialu Sun; Xiaolin Zhang; Xiaodong Zhao; Kai Wang; Tian Li; Xiaojing Li (Reviews in Environmental Science and Bio/Technology, 2025)

Research on Seismic Prediction Methods for Pore Pressure in the Canglangpu Formation Carbonate of JT1 Well Area in Sichuan Basin - Hu Zhao; Huan Yu; Hang Zhang; Jie-wei Zhang; Wen-hao Li; Heng Yang; Jing-yun Dai; Hong-yi An (Applied Geophysics, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

The outer membrane vesicles of Vibrio parahaemolyticus elicit innate immune responses in mud crab (Scylla paramamosain) - Qian Sun; Linying Yun; Kaichun Hu; Han Li; Pengfei Li; Yiyuan Lu; Runwu Gao; Ming Zhang; Ngoc Tuan Tran; Xiuli Chen; Yongzhen Zhao; Yueling Zhang; et al. (Aquaculture, 2025)

Decoupling soil pH and geography: Universal drivers of cadmium bioavailability in rice across terrains - Qiang Liu; Shuyue Liu; Danling Wang; Dawei Sun; Yun Ge; Songwei Zhang; Guanlin Li; Eun Hea Jho; Jin Chul Joo; Xin Zhao; Mao Ye; Jian Hu (Journal of Environmental Management, 2025)

High-value conversion of bio-dried products derived from municipal organic wastes: Activated carbon preparation and electrochemical assessment - Changheng Li; Mengying Yun; Xuewen Zhu; Jiao Ma; Zhikun Zhang; Wenwen Kong; Boxiong Shen; Zhong Zhao (Fuel, 2025)

Exploring the self-assembled gel behaviour of litchi pulp arabinan enriched pectic polysaccharides by small and large amplitude oscillatory shear - Dongwei Wang; Sonia S. Ferreira; Yun Li; Kai Wang; Lei Zhao; Xuwei Liu; Manuel A. Coimbra; Zhuoyan Hu (Food Hydrocolloids, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Nature of space-weathered rims on Chang'e-5 lunar soil grains - Zhi Cao; Xi Wang; Yun Chen; Chen Li; Sizhe Zhao; Yang Li; Yuanyun Wen; Qi He; Zhiyong Xiao; Xiongyao Li; Long Xiao; Jianzhong Liu (Earth and Planetary Science Letters, 2025)

Metformin-induced precise targeted inhibition of ischemic neuronal death by a programable endogenous ROS-responsive nanoprodrug - Xiaofeng Tan; Ying Li; Hao Jin; Yu Zhou; Wenjun Li; Yun Zhao; Jun Hai; Jinyao Li; Zhongxiong Fan; Lichao Yang (Chemical Engineering Journal, 2025)

Overexpression of Heme Oxygenase 1 Enhances the Neuroprotective Effects of Exosomes in Subarachnoid Hemorrhage by Suppressing Oxidative Stress and Endoplasmic Reticulum Stress - Qiongqiong Gao; Zhumin Su; Xiangxiong Pang; Jinshuo Chen; Ruixiang Luo; Xiaoyang Li; Chi Zhang; Yun Zhao (Molecular Neurobiology, 2025)

Association between multiple metals mixture and diabetic retinopathy in older adults with diabetes mellitus: a cross-sectional study in China - Shuren Ding; Yirong Xie; Feng Wang; Jieyi Liu; Hongya Li; Heng Su; Zhiqiang Zhao; Qing Wei; Shurong Pi; Fubin Chen; Qian Gu; Baixiang Xiao; et al. (Environmental Geochemistry and Health, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A SPH method to assess the dynamic behavior for multiconnected floating photovoltaic units consisting of non-uniform supporting frames in waves - Yun Pan; Junwei Hong; Dawen Xue; Xizeng Zhao; Min Luo; Can Liu; Lei Li (Ocean Engineering, 2025)

Improved mathematical model simulates methane production during anaerobic digestion of food waste under stable and unstable acidification conditions - Xiaofei Zhao; Yuxin Tang; Xinwei Tian; Maozheng He; Xuefang Li; Yun Peng; Lei Li; Shangyi Zhang (Journal of Environmental Chemical Engineering, 2025)

Self-solidification of As-containing bio-oxidation waste into cementitous materials: Performance enhancement via mechanochemical-activated recycled concrete fines - Hui Li; Wenxiao Guo; Yun Chen; Shiyu Zhang; Yingliang Zhao (Journal of Environmental Chemical Engineering, 2025)

Effects of Spartina alterniflora invasion on the structural dynamics of bacterial and diatom communities in the native Suaeda salsa zone - Xing Liu; Dandan Ding; Yihang Sun; Yun Li; Guanpin Yang; Yuhang Li; Baohua Zhu; Yan Zhao; Kehou Pan (Estuarine, Coastal and Shelf Science, 2025)

Effect of antibiotics on diverse aquatic plants in aquatic ecosystems - Yiting Li; Yani Zhang; Dongyao Wang; Jiamei Zhao; Huan Yu; Yun Chen; Jiqiang Yang (Aquatic Toxicology, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Soil Acidification Destabilizes Terrestrial Ecosystems via Decoupling Soil Microbiome - Yulong Duan; Junbiao Zhang; Evangelos Petropoulos; Jianhua Zhao; Rongliang Jia; Fasi Wu; Yun Chen; Lilong Wang; Xuyang Wang; Yulin Li; Yuqiang Li (Global Change Biology, 2025)
Soil microbiome is essential for terrestrial ecosystem preservation. β‐diversity information on the former, although dynamic due to its sensitivity to environmental conditions driven by climate change, is limited. Our knowledge becomes poorer for microbiomes subjected to environmental gradients, especially for those across multiple ecosystems—information important for biological conservation management. In this study, using next generation sequencing and machine learning at samples from 207 locations among 4300 km of transects that spanned among six typical terrestrial ecosystems of China, we established the divergent distance‐decay relationships between bacterial and eukaryotic communities in response to soil pH (pH as proxy of climate and edaphic conditions). The findings, pH‐decrease results in lower β‐diversity (convergent tendency) among the bacterial communities opposite to the eukaryotic ones (low pH—high β‐diversity (divergent tendency)). Meanwhile, competition between bacteria and eukaryotes intensifies at lower pH while the predominant genera and communities are re‐structured. Under these circumstances, potential soil acidification due to climate change or other factors could alter soil bacteria and eukaryotes into decoupling directions influencing ecosystems' stability. Thus, soil pH is a pivotal environmental variable that not only describes, but also controls, soil microbiome dynamics at a large scale under ongoing global changes; hence, a cornerstone variable for the biodiversity conservation of China's nature protected areas and not only.

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Role of Glucose Metabolism in the Effects of Serum Metals on Telomere Length: Findings in Chinese Diabetic Population - Shuren Ding; Qian Gu; Zhiqiang Zhao; Yirong Xie; Feng Wang; Jieyi Liu; Hongya Li; Heng Su; Qing Wei; Shurong Pi; Fubin Chen; Baixiang Xiao; et al. (Biological Trace Element Research, 2025)

Reconstruction of well-logging data using unsupervised machine learning-based outlier detection techniques (UML-ODTs) under adverse drilling conditions - Jing-Rui Chen; Rui-Zhao Yang; Ting-Ting Li; Yun-Di Xu; Zhi-Peng Sun (Applied Geophysics, 2025)

The impact and mechanisms of YL-IPA08, a potent ligand for the translocator protein (18 kDa) on protection against LPS-induced depression and cognitive dysfunction in rodents - Lin-yu Cui; Jing-yao Duan; Jiao-zhao Yan; Jing-ya Wang; Peng Ren; Li-ming Zhang; Wen-zhi Guo; Wei Dai; Yun-feng Li (Metabolic Brain Disease, 2025)

Comparison of the social gene expression network and social brain network: a resting-state functional magnetic resonance imaging study - Yi-Jing Zhang; Hao-Yun Zhao; Peng Li; Xiao Lin; Lin Lu (Brain Imaging and Behavior, 2025)

Astaxanthin ameliorates high-carbohydrate diet-induced ER stress, immunosuppression and hepatic glucose metabolism through AMPK/autophagy pathway in Channa argus - Mu-Yang Li; Yun-Zhuo Liu; Xiu-Mei Chen; Xiao-Tian Niu; Lu Chen; Lei Zhao; Gui-Qin Wang (Aquaculture, 2025)

Siegesoxylipin A‒J, previously undescribed phyto-oxylipins inhibition of methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococci from Sigesbeckia orientalis - Zhong-Shun Zhou; Wen-Biao Zu; Yan-Yan Zhu; Mei-Zhen Wei; Yue-Ming Jiang; Zhao-Jie Wang; Yun-Li Zhao; Xiao-Dong Luo (Phytochemistry, 2025)

A Gln alteration influences leaf morphogenesis by mediating gibberellin levels in tobacco - Qi-Li Mi; Hong-Tao Lv; Fei-Fei Huang; Li Xu; Zi-Ying Huang; Wen-Wu Yang; Mei-Yun Zou; Hai-Tao Huang; Wan-Li Zeng; Jia-Yin Zhao; Qing-Xian Chen; Yong-En Si-Tu; et al. (Journal of Plant Physiology, 2025)

Ultra-high pressure effectively inhibits the pro-inflammatory activity of thaumatin-like protein from Litchi chinensis: Insights from gut metabolism and theoretical investigation - Yun Li; Rongbo Zheng; Yu Wang; Danyue Zhao; Lei Zhao; Kai Wang; Zhuoyan Hu; Xuwei Liu (Food Research International, 2025)

Foxtail millet prolamin-pectin nanoparticles enhanced the stability and bioavailability of β-sitosterol - Yue Li; Yongxia Liu; Jiawei Qiao; Bao Xing; Junyan Yun; Jiahui Niu; Muwen Chen; Pu Yang; Shaojie Zhao; Lizhen Zhang (Food Research International, 2025)

Separator-SEI interactions: Unlocking new pathways for lithium metal battery stability - Shuyang Li; Wei Zhou; Junyu Hou; Fei Yan; Renzong Hu; Jie Zhao; Fang Fang; Jiafeng Ruan; Yun Song (Chemical Engineering Journal, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Study on the performance of electric double-layer capacitors based on lignocellulose gel polymer electrolytes with different pH values for Zn2+-lignocellulose coordination mechanism - Yanzhou Wang; Yun Huang; Xu Wang; Jin Bao; Chao Zou; Xichang Wang; Yunhe Zhang; Changjian Zhang; Zhongwei Zhao; Xing Li; Mingshan Wang; Yuanhua Lin; et al. (Chemical Engineering Journal, 2025)

An innovative approach for marine macro-organism monitoring: methodology and future perspectives of environmental DNA (eDNA) technology - Yun Jiang; Wencheng Zhao; Yiyi Zhu; Shanshan Ma; Min Li; Shuai Zhang; Keshu Zou (Marine Biology, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

Geochronology and geochemistry of igneous rocks in the Qinfang belt: Implications for spatio-temporal framework of Paleo-Tethys - Yue Qin; Yun Zhou; Xijun Liu; Yongshan Zhao; Zhenglin Li; Liya Yang; Chen Li; Yongfeng Cai (Lithos, 2025)

American ginseng fruit: Antioxidant capacity, bioactive components, and biosynthesis mechanism during development - Yujuan Zhang; Lijuan Hou; Jing Hu; Xianchang Wang; Shujing Guo; Hongqing Xie; Yun Zhou; Wen Ai; Lin Li; Xin Wang; Li Ren; Fangzhou Zhao; et al. (Food Research International, 2025)

Improving the physical stability of Lactobacillus plantarum LP90 during storage by mixing carboxymethylated dextran-whey protein conjugates and small-molecule sugars - Wen Li; Yunjiao Zhao; Shunqin Li; Liyuan Yun; Tao Wu; Min Zhang (Food Research International, 2025)

Exploring the effect of pH-shifting on the gel properties and interaction of heat-induced Flammulina velutipes polysaccharide-porcine myofibrillar protein for improving the quality of Flammulina velutipes-pork patties - Zheming Wang; Liang Li; Fengying Jia; Jiaman Wu; Wen Jin; Wenfei Zhao; Jinling Cao; Yanfen Cheng; Lei Shi; Shaojun Yun; Cuiping Feng (Food Chemistry, 2025)

Architectural coatings and temperature adaptive radiative cooling strategies applied in ten climate zones in China: Annual energy consumption reductions and potentials - Bin Li; Hong-Liang Zhang; Jun-Hao Chen; Ming-Ming Wu; Wei-Wei Wang; Fu-Yun Zhao; Yuguo Li (Energy and Buildings, 2025)

Enhancing the photodynamic efficacy of hypericin in antitumor treatment by inhibiting the cell integration stress response - Xiaoxian Hu; Peiye Wu; Yu Zhao; Yun Wang; Zhongrui Li; Chao Han (Chemical Engineering Journal, 2025)

Physical Exercise Improves the Neuronal Function in Ischemic Stroke Via Microglial CB2R/P2Y12 Signaling - Xiao-fei He; Xiao-feng Yang; Ge Li; Yun Zhao; Jing Luo; Jing-hui Xu; Hai-qing Zheng; Li-ying Zhang; Xi-quan Hu (Molecular Neurobiology, 2025)

Characterisation of granite joint structures and their influence on permeability in the Beishan Underground Research Laboratory, China - Xiaozhao Li; Wei Zeng; Zhicheng He; Jinlong Song; Lihua Hu; Peng Zhao; Yun Wu (Hydrogeology Journal, 2025)

Correction to: Distinct expression of three estrogen receptors in response to bisphenol A and nonylphenol in male Nile tilapias (Oreochromis niloticus) - Weiren Huang; Yong Zhang; Xiaoping Jia; Xilan Ma; Shuisheng Li; Yun Liu; Pei Zhu; Danqi Lu; Huihong Zhao; Wenna Luo; Shibai Yi; Xiaochun Liu; et al. (Fish Physiology and Biochemistry, 2025)

Water-saving irrigation practices in rice paddies reverse the impact of root aerenchyma on methane emissions - Siyu Li; Yajun Zhang; Jiamei Zhao; Kees Jan van Groenigen; Xinya Shen; Hao Zhang; Junfei Gu; Weiyang Zhang; Dafeng Hui; Yun Chen; Lijun Liu (Agriculture, Ecosystems & Environment, 2025)

Enhancing Physical Spatial Resolution of Synthetic Aperture Sonar Images Based on Convolutional Neural Network - Pan Xu; Dongbao Gao; Shui Yu; Guangming Li; Yun Zhao; Guojun Xu (Journal of Marine Science and Engineering, 2025)
The sonar image has limitations on the physical spatial resolution due to system configuration and underwater environment, which often leads to challenges for underwater targets detection. Here, the deep learning method is applied to enhance the physical spatial resolution of underwater sonar images. Specifically, the U-shaped end-to-end neural network which contains down-sampling and up-sampling parts is proposed to improve the physical spatial resolution limited by the array aperture. The single target and multiple cases are considered separately. In both cases, the normalized loss on the testing sets declines rapidly, and the predicted high-resolution images own great agreement with the ground truth eventually. Further improvements in resolution are focused on, that is, compressing the predicted high-resolution image to its physical spatial resolution limitation. The results show that the trained end-to-end neural network could map high resolution targets to the impulse responses at the same location and amplitude with an uncertain target number. The proposed convolutional neural network approach could give a practical alternative to improve the physical spatial resolution of underwater sonar images.

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Discovery of cycloheptapeptides phakefusins A−E from the marine sponge Phakellia fusca based on molecular networking - Ying Wu; Zhao-Ze Xu; Can Kong; Shuai-Shuai Zhang; Xin-Li Lin; Si Zhang; Li-Yun Liu; Fan Sun; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Seasonal changes of species- and guild-based benthic diatom communities in the transitional water zone of the Yellow River Delta - Xing Liu; Yan Zhao; Xiaoqiu Yu; Ying Song; Yun Li; Guanpin Yang; Yuhang Li; Baohua Zhu; Kehou Pan (Marine Environmental Research, 2025)

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

A forecasting tool for optimized emission control strategies to achieve short-term air quality attainment - Zhaoxin Dong; Shuxiao Wang; Yueqi Jiang; Jia Xing; Dian Ding; Fenfen Zhang; Dejia Yin; Qian Song; Jingyu An; Hongli Wang; Cheng Huang; Qian Wang; et al. (Journal of Environmental Management, 2025)

Why does distilled liquor (Baijiu) have a yellowish color: A comprehensive analysis - Jilei Wang; Qu Li; Yun Sun; Jingwen Liu; Zhao Jiang; Zhuoping Zheng; Li Liu; Xinhui Min; Yougui Yu; Qing Zheng (Food Chemistry, 2025)

Selective adsorption of SiC quantum dots to C = O bond promoting the catalytic hydrogenation of cinnamaldehyde - Zhi-Yuan Zheng; Zhi-Feng Jiao; Ji-Xiao Zhao; Xin-Chao Liu; Cai-Dong Song; Jia-Hang Li; Xiang-Yun Guo (Chemical Engineering Journal, 2025)

Triple modifications of Li-rich manganese-based cathode materials using LiMnPO4 one-step method - Jianan Hao; Jinyang Dong; Yuefeng Su; Kang Yan; Jiayu Zhao; Huiquan Che; Yun Lu; Ning Li; Bin Zhang; Ping Zhang; Feng Wu; Lai Chen (Chemical Engineering Journal, 2025)

Kv3.1 Interaction with UBR5 Is Required for Chronic Inflammatory Pain - Ying Zeng; Meng-Lan Sun; Di Liu; Yue Huang; Shan Xie; Ya-Xuan Zhao; Zi-Xuan Wu; Ya Liu; Gan Ma; Ling Xie; Yu-Tao Dang; Ling-Yun Hao; et al. (Molecular Neurobiology, 2025)

Corrigendum: Coral reefs of Pakistan: a comprehensive review of anthropogenic threats, climate change, and conservation status - Ishfaq Ahmad; Pu Guo; Mei-Xia Zhao; Yu Zhong; Xiao-Yun Zheng; Shu-Qi Zhang; Jian-Wen Qiu; Qi Shi; Hong-Qiang Yan; Shi-Chen Tao; Li-Jia Xu (Frontiers in Marine Science, 2024)

Atmospheric emissions of Fe-containing nanoparticles from industrial activities - Qiuting Yang; Lili Yang; Lingna Zheng; Hao Fang; Xue Li; Haogang Liu; Changzhi Chen; Jianghui Yun; Chenyan Zhao; Meng Wang; Guorui Liu; Minghui Zheng (Science of The Total Environment, 2024)

Remediation of Cd-As-Ni co-contaminated soil by extracellular polymeric substances from Bacillus subtilis: Dynamic improvements of soil properties and ecotoxicity - Yang Li; Lei Cheng; Baolin Yang; Yanan Zhao; Yuting Ding; Chenxi Zhou; Yuanyuan Wu; Ruoyun Dong; Yun Liu; An Xu (Science of The Total Environment, 2024)

Integrated analysis of radiomics, RNA, and clinicopathologic phenotype reveals biological basis of prognostic risk stratification in colorectal cancer - Xiaobo Chen; Yanqi Huang; Leonard Wee; Ke Zhao; Yun Mao; Zhenhui Li; Su Yao; Suyun Li; Yanting Liang; Xin Huang; Andre Dekker; Xin Chen; et al. (Science Bulletin, 2024)

Numerical study on wave propagating characteristics through an offshore pile-net enclosure structure - Yun-Peng Zhao; Lian-Xin Xin; Chao Ma; Ke-Zhao Fang; Yi-Xin Li; Chun-Wei Bi (Ocean Engineering, 2024)

Adsorption and recovery of berberine hydrochloride from wastewater by a novel magnesium-modified biochar: Toward resource utilization of waste dander - Yunyu Zhao; Shuyi Yang; Kexin Zhou; Junbo Wang; Cheng Ji; Yuanfei Wang; Liang Chen; Yun Li; Chong Peng; Tao E (Journal of Water Process Engineering, 2024)

Shortening the early diagnostic window of Hg2+-induced liver injury with a H2O2-activated fluorescence/afterglow imaging assay - Longxuan Li; Jia Li; Xin Liu; Xuan Zhao; Ao Zhang; Yun Deng; Cheng Peng; Zhixing Cao; Wim Dehaen; Yuyu Fang (Journal of Hazardous Materials, 2024)

Highly dispersed CuOx decorated ZnO photocatalyst for low-concentration methane removal - Yun Wang; Sheng Xu; Haiyuan Zhang; Yuyin Wang; Enmao Wang; Zeyu He; Jiahua Zhu; Xiaohua Lu; Lilong Zhang; Yang Bai; Kunfeng Zhao; Qingwei Gao; et al. (Journal of Environmental Chemical Engineering, 2024)

High hydrostatic pressure reduces inflammation induced by litchi thaumatin-like protein via altering active domain - Yun Li; Chuyuan Li; Fei Pan; Kai Wang; Shaoquan Weng; Min Zhao; Qian Li; Dongwei Wang; Lei Zhao; Xuwei Liu; Zhuoyan Hu (Food Chemistry, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Unlocking superior preservation: The synergy of lignin and zeolite in chitosan-based composite films for perishable foods - Zhan-Chao Li; Xi Chen; Jia-Li Zhang; Xiao-Ping Gao; Yan-Xia An; Li-Jie Wu; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Packaging and Shelf Life, 2024)

Regulating chiral nematic liquid crystal of hydroxypropyl methylcellulose coating on separator for High-Safety Lithium-Ion batteries - Xichang Wang; Yun Huang; Wenhao Ren; Chen Luo; Xi Xu; Yiheng Wang; Yanzhou Wang; Changjian Zhang; Zhongwei Zhao; Li Liu; Xing Li; Mingshan Wang; et al. (Chemical Engineering Journal, 2024)

Continuous peroxymonosulfate activation by a novel CoFe2O4-functionalized carbon fiber electroactive filter towards ultrafast and cost-effective decontamination: Performance, mechanism and application - Dengao Chang; Yi Luo; Siyuan Song; Yu Huang; Yalun Zhao; Yun Ou; Ziming Li; Xu Wang (Chemical Engineering Journal, 2024)

Crystallographic and biochemical analyses of a far-red allophycocyanin to address the mechanism of the super-red-shift - Li-Juan Zhou; Astrid Höppner; Yi-Qing Wang; Jian-Yun Hou; Hugo Scheer; Kai-Hong Zhao (Photosynthesis Research, 2024)

Melatonin Ameliorates Abnormal Sleep-Wake Behavior via Facilitating Lipid Metabolism in a Zebrafish Model of Parkinson’s Disease - Meng-Zhu Pang; Han-Xing Li; Xue-Qin Dai; Xiao-Bo Wang; Jun-Yi Liu; Yun Shen; Xing Xu; Zhao-Min Zhong; Han Wang; Chun-Feng Liu; Fen Wang (Neuroscience Bulletin, 2024)

Exploring the preventive effects of Jie Geng Tang on pulmonary fibrosis induced in vitro and in vivo: a network pharmacology approach - Bingxin Li; Xiaojie Jiang; Chang Liu; Yun Ma; Ruining Zhao; Haijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Similarities and differences in bacterial communities between the Pearl River (Guangzhou section) and its estuary - Longxin Wang; Wencheng Zhao; Yun Jiang; Li Liu; Jianwei Chen; Fang Zhao; Xiaoyong Zhang; Keshu Zou (Molecular Biology Reports, 2024)

A novel m.5906G > a variant in MT-CO1 causes MELAS/Leigh overlap syndrome - Zhimei Liu; Yaojun Xie; Xiaoting Lou; Xiaofei Zeng; Luyi Zhang; Meng Yu; Junling Wang; Jiuwei Li; Danmin Shen; Hua Li; Suzhou Zhao; Yuwei Zhou; et al. (Molecular Genetics and Genomics, 2024)

Discovery of novel Akt1 inhibitors by an ensemble-based virtual screening method, molecular dynamics simulation, and in vitro biological activity testing - Wen Zhang; Mei-Ling Hu; Xiu-Yun Shi; Xiang-Long Chen; Xue Su; Hua-Zhao Qi; Li Yuan; Hui Zhang (Molecular Diversity, 2024)

Pollinator-mediated selection on flowering start and corolla tube length differed between mating systems in a primrose species - Zhao-Li Tong; Yong-Peng Cha; Yin-Mei Ma; Yun Wu; Zhi-Qiang Zhang (Evolutionary Ecology, 2024)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Identification, functional analysis of chitin-binding proteins and the association of its single nucleotide polymorphisms with Vibrio parahaemolyticus resistance in Penaeus vannamei - Shuang-Shuang Luo; Xiu-Li Chen; Ai-Jin Wang; Qing-Yun Liu; Min Peng; Chun-Ling Yang; Di-Gang Zeng; Yong-Zhen Zhao; Huan-Ling Wang (Fish & Shellfish Immunology, 2024)

Malic acid additive with a dual regulating mechanism for high-performances aqueous zinc-ion batteries - Zhongwei Zhao; Yun Huang; Bingshu Guo; Xichang Wang; Yunhe Zhang; Xing Li; Mingshan Wang; Yuanhua Lin; Haijun Cao (Chemical Engineering Journal, 2024)

High mobility emissive BN-Embedded Dinaphthalenyl anthracene for organic light emitting transistors - Ze-Wei Lin; Pu Wang; Sheng-Hong Zhao; Yun-Tao Ding; Huanli Dong; Hao-Li Zhang (Chemical Engineering Journal, 2024)

Optimisation of extraction performance for uranium with covalent organic frameworks of β-ketoenamines with different functional groups - Jihe Zhao; Quan Cao; Lei Zhao; Fengwe Li; yangyang xin; Yanli Liu; Wansheng Zhang; Xiaolin shi; Meiyan Wu; Yongye Zhao; Yun Fa; Huizhou Liu (Chemical Engineering Journal, 2024)

Skeleton design engineering of covalent organic frameworks to enable in situ incorporation of coordination sites for improved extraction of uranyl ions - Jihe Zhao; Lei Zhao; Quan Cao; Guangying Fu; Fengwe Li; Huizhou Liu; Yun Fa (Chemical Engineering Journal, 2024)

From Skin to Gut: Understanding Microbial Diversity in Rana amurensis and R. dybowskii - Ming-he Yang; Hong Liu; Hao Wang; Zhao-ning Lu; Xiao-yun Han; Zhi-wen Luo; Li-gang Wu; Qing Tong (Current Microbiology, 2024)

Nrf2 deficiency exacerbated pulmonary pyroptosis in maternal hypoxia-induced intrauterine growth restriction offspring mice - Dan Chen; Ling-yun Man; Ying-ying Wang; Wei-ying Zhu; Hui-min Zhao; Sheng-peng Li; Yan-li Zhang; Shuai-chao Li; Ya-xian Wu; Ling-Ai; Qing-feng Pang (Reproductive Toxicology, 2024)

Large granitoid batholith formed by episodic reworking of the continental basement - Qi-Wei Li; Jun-Hong Zhao; Yun-Lai Dong; Yu-Qing Huang (Precambrian Research, 2024)

Deciphering assembly processes, network complexity and stability of potential pathogenic communities in two anthropogenic coastal regions of a highly urbanized estuary - Yiyi Zhu; Shanshan Ma; Yongjing Wen; Wencheng Zhao; Yun Jiang; Min Li; Keshu Zou (Environmental Pollution, 2024)

A novel dual functional gradient Zn(O,S)/Mg electron-selective contact for dopant‐free silicon solar cells with efficiencies approaching 21 % - Junfeng Zhao; Zhongqing Zhang; Shengpeng Xie; Fangfang Liu; Yongtai Zhen; Sen Li; Wenzhu Liu; Anjun Han; Liping Zhang; Zhengxin Liu; Yun Sun; Wei Liu (Chemical Engineering Journal, 2024)

Tailor-made the ultrathin nanosheet and acid site accessibility of mordenite zeolite for carbonylation of dimethyl ether - Feng Chen; Xiao-Bo Feng; Pan Deng; Li-Yun Zhang; Jing-Ping Zhao; Yu-Hui Wang; Bo-Yu Tao; Xiao-Yan Zhao; Jing-Pei Cao; Hong-Cun Bai (Chemical Engineering Journal, 2024)

Biochar accelerates methane production efficiency from Baijiu wastewater: Some viewpoints considering direct interspecies electron transfer - Yun He; Shilei Wang; Caihong Shen; Zhi Wang; Yiyang Liu; Xingyao Meng; Xiaoyong Li; Xiaoling Zhao; Jinmeng Chen; Jingliang Xu; Jiadong Yu; Yafan Cai; et al. (Chemical Engineering Journal, 2024)

Rock abrasiveness prediction based on multi-source physical, mechanical and mineralogical properties - Yun Wu; Long-Chuan Deng; Xiao-Zhao Li; Li-Yuan Yu; Jiang-Feng Liu; Jian Lin (Bulletin of Engineering Geology and the Environment, 2024)

Coral reefs of Pakistan: a comprehensive review of anthropogenic threats, climate change, and conservation status - Ishfaq Ahmad; Pu Guo; Mei-Xia Zhao; Yu Zhong; Xiao-Yun Zheng; Shu-Qi Zhang; Jian-Wen Qiu; Qi Shi; Hong-Qiang Yan; Shi-Chen Tao; Li-Jia Xu (Frontiers in Marine Science, 2024)
The coral reefs along Pakistan’s coastline are of ecological and economic significance. However, they are increasingly threatened by anthropogenic threats and climate change. These vulnerable ecosystems are declining due to various factors such as sedimentation, climate change, overfishing, destructive fishing practices, marine pollution, and tourism development. We found that 29%, 24%, 26%, 16% and 18% of the studies exceeding, marine pollution, overfishing/destructive fishing, coastal tourism, climate change and sedimentation, respectively; thus, indicating inadequate water quality status in part of Pakistan coastal water. These influences lead to several negative impacts, such as jeopardized coral health, decline in biodiversity, and the simplification of reef structures. In response to these threats, conservation efforts are imperative. This literature review provides an in-depth analysis of anthropogenic threats, climate change and the conservation of coral reefs in Pakistan. This review provides suggestions on how the country could better conserve its coral reef ecosystem. These include (1) initiatives such as establishing marine protected areas (MPAs), (2) encouraging sustainable fishing practices and reducing pollution, (3) developing the country as an ecotourism destination and implementing climate change adaptation measures, and (4) community engagement through awareness campaigns and fostering collaboration among, governmental organizations, non-governmental organizations (NGOs) and scientists. These comprehensive conservation policies address human-caused and other challenges, safeguarding their ecological, economic, and cultural relevance for future generations.

New insights into biologic interpretation of bioinformatic pipelines for fish eDNA metabarcoding: A case study in Pearl River estuary - Zhuoying Li; Wencheng Zhao; Yun Jiang; Yongjing Wen; Min Li; Li Liu; Keshu Zou (Journal of Environmental Management, 2024)

Simultaneous nitrification and denitrification in a hybrid activated sludge-membrane aerated biofilm reactor (H-MABR) for nitrogen removal from low COD/N interflow: A pilot-scale study - Hengyi Liu; Lei Li; Wenjie Ye; Boxuan Zhao; Yun Peng; Guotao Liu; Xiaofeng Gao; Xuya Peng (Journal of Environmental Management, 2024)

Geomechanical perspectives and reviews on the development and evolution of cross-scale discontinuities in the Earth's crust: Patterns, mechanisms and models - Sanbai Li; Zhijiang Kang; Moran Wang; Xi Zhang; Junliang Zhao; Xi-bing Li; Pengzhi Pan; Xin Luo; Hui Wu; Diyuan Li; Fengshou Zhang; Shunda Yuan; et al. (Gas Science and Engineering, 2024)

Self-hydrogen transfer hydrogenolysis of β-O-4 bonds in lignin model compounds over NiCu/Al2O3 catalyst - Fa-Peng Wu; Le-Le Qiu; Yun-Peng Zhao; Zong-Pin Fu; Jing Liang; Jian Xiao; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2024)

Highly efficient conversion of lignin bio-oil and derived phenols to cyclohexanols over low-loading Ni/C catalyst - Jin-Xuan Xie; Yun-Peng Zhao; Qiang Li; Le-Le Qiu; Fang-Jing Liu; Jing Liang; Jian Li; Jing-Pei Cao (Fuel, 2024)

Remediation of petroleum-contaminated site soil by bioaugmentation with immobilized bacterial pellets stimulated by a controlled-release oxygen composite - Sheng Zhao; Ling-ling Li; Yue-jie Wang; Zheng-wei Liu; Shuai Yang; Xiang Gao; Chang-yun Zhang; An-feng Yu (Environmental Pollution, 2024)

SA-DNA hydrogel microspheres for Ultra-Selective uranyl (VI) extraction from seawater - Wansheng Zhang; Yangyang Xin; Yun Fa; Fei Li; Yanli Liu; Mengqin Wu; Jihe Zhao; Hongwei Xu; Huizhou Liu (Chemical Engineering Journal, 2024)

The influence of hydrogeology and carbon sources on speleothem δ13C based on long-term monitoring in Furong Cave, southwest China - Jun-Yun Li; Ting-Yong Li; Hong-Chun Li; Christoph Spötl; Chao-Jun Chen; Jian Zhang; Yao Wu; Hua-Yan Li; Yue Jin; Min Zhao; Hong-Kai Li; Yan-Min Dong (Chemical Geology, 2024)

DC-YOLOv5-based target detection algorithm for cervical vertebral maturation - Man Jiang; Yun Hu; Jianxia Li; Huanzhuo Zhao; Tianci Zhang; Xiang Li; Leilei Zheng (Physical and Engineering Sciences in Medicine, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Zinc oxide/graphene oxide nanocomposites specifically remediated Cd-contaminated soil via reduction of bioavailability and ecotoxicity of Cd - Yang Li; Lei Cheng; Baolin Yang; Yuting Ding; Yanan Zhao; Yuanyuan Wu; Yaguang Nie; Yun Liu; An Xu (Science of The Total Environment, 2024)

Study on Plant-blanket to reduce heavy metal migration caused by precipitation and to improve the soil environment of pyritic tailings - Kangkai Lin; Jiannan Jian; Yumei Zhang; Yikai Liu; Shiyao Li; Yun Zhao; Heng Xu (Science of The Total Environment, 2024)

Strengthened oil-water separation by swirl vane hydrocyclone based on short-circuit flow regulation - Wei Zhao; Jian-ping Li; Tong Zhang; Aosong Wei; Shi-yun Li; Zi-heng Zhao; Xue-jing Yang; Xia Jiang; Hua-lin Wang (Journal of Water Process Engineering, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

Synergistically promoting the catalytic conversion of polysulfides via in-situ construction of Ni-MnO2 heterostructure on N-doped hollow carbon spheres towards high-performance sodium-sulfur batteries - Haoyu Zhao; Zuze Li; Mingzhe Liu; Suyu Ge; Kaixuan Ma; Qingze Jiao; Hansheng Li; Haijiao Xie; Yun Zhao; Caihong Feng (Chemical Engineering Journal, 2024)

Corrigendum to “Biomimetic redox-responsive prodrug micelles with diselenide linkage for platinum nanozymes augmented sonodynamic/chemo combined therapy of colon cancer” [Chem. Eng. J. 472 (2023) 144911] - Yuanru Zhao; Jingwen Xu; Yuanyuan Zhang; Feng Wu; Wei Zhao; Runqing Li; Yun Yang; Mingzhen Zhang; Yujie Zhang; Cheng Guo (Chemical Engineering Journal, 2024)

From characteristics to practical applications of skin temperature in thermal comfort research – A comprehensive review - Jiaqi Zhao; Rui Wang; Yeyu Wu; Chaoyi Zhao; Yun Qi; Sishi Li; Haihua Jiang; Bin Cao (Building and Environment, 2024)

Regulation of I1-imidazoline receptors on the sedation effect of dexmedetomidine in mice - Xiao Han; Zhi-fang Yang; Tai-yun Zhao; Guan-yi Lu; Zhi-yuan Wang; Ning Wu; Jin Li; Fei Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Metal recovery from industrial solid waste by ultrasonic-assisted hydrometallurgical leaching: a review - Jianfeng Ran; Yun Li; Xuxu Wang; Haisheng Duan; Ying Chen; Shaohua Yin; Shiwei Li; Libo Zhang; Jiaping Zhao (Environmental Chemistry Letters, 2024)

Heterometallic Eu/Zn-MOF-based ratiometric sensing platform: Highly sensitive fluorescence / second-order scattering identification of tetracycline analogs and its molecular informatization applications - Ya Jie Fan; Jiang Xue Dong; Tan Liu; Yan Qing Chang; Yong Sen Zhao; Yan Lei Li; Sai Mei Zhang; Song Yun Cao; Ming Su; Shi Gang Shen; Zhong Feng Gao (Analytica Chimica Acta, 2024)

Two new alkaloids from the endophytic fungus Schizophyllum sp. HM230 isolated from Vincetoxicum mongolicum Maxim - Zhuang Li; Bing-Wen Zhang; Li Jiang; He Wang; Qing-Yun Ma; Hong-Fei Wang; Jun Zhang; Feng-Li Chen; You-Xing Zhao; Du-Qiang Luo (Natural Product Research, 2024)

Metagenomic analysis of a thermophilic bacterial consortium and its use in the bioremediation of a petroleum-contaminated soil - Li Peng; Jinyu Hou; Yufeng Zhang; Beibei Wang; Yun Zhang; Ke Zhao; Qingling Wang; Peter Christie; Wuxing Liu; Yongming Luo (Chemosphere, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Joint effects about antibiotics combined using with antibiotics or phytochemicals on Aeromonas hydrophila - Yannei Liang; Haiqing Zhao; Yun Li; Fuqing Gao; Jing Qiu; Zhe Liu; Qiongyan Li (Marine Environmental Research, 2024)

Epimedin B exerts an anti-inflammatory effect by regulating the MAPK/NF-κB/NOD-like receptor signalling pathways - Li Liu; Yayun Zhong; Te Zheng; Jingcheng Zhao; Shumin Ding; Jinpeng Lv; Qian Xu; Yun Zhang (Fish & Shellfish Immunology, 2024)

A novel sustainable immunoassay for sensitive detection of atrazine based on the anti-idiotypic nanobody and recombinant full-length antibody - Jing Zhao; Peipei Li; A.M. Abd El-Aty; Lingyuan Xu; Xingmei Lei; Song Gao; Jia Li; Yun Zhao; Yongxin She; Fen Jin; Jing Wang; Bruce D. Hammock; et al. (Chemical Engineering Journal, 2024)

Preparation of co-doped biochar to improve electron transfer and modulate 1O2 generation: Unraveling the radical-unradical mechanism - Jingyang Zhang; Shuyi Yang; Kexin Zhou; Jiaqi Zhao; Junbo Wang; Na Li; Yuanfei Wang; Yun Li; Tao E (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Toward a solid microneedle patch for rapid and enhanced local analgesic action - Yue Liu; Ze Qiang Zhao; Ling Liang; Li Yue Jing; Jianhao Wang; Yun Dai; Bo Zhi Chen; Xin Dong Guo (Drug Delivery and Translational Research, 2024)

Association between outdoor air pollutants and risk of acute exacerbation of chronic obstructive pulmonary disease in Xi’an, China - Xinping Fan; Xueyan Jie; Fan Zou; Dan Wang; Hongju Da; Hongxin Li; Hongyan Zhao; Jin He; Jianghao Liu; Yiyi Lu; Yun Liu (Air Quality, Atmosphere & Health, 2024)

Neural network based on convolution and self-attention fusion mechanism for plant leaves disease recognition - Yun Zhao; Yang Li; Na Wu; Xing Xu (Crop Protection, 2024)

Zinc improves the developmental ability of bovine in vitro fertilization embryos through its antioxidative action - Yun Feng; Xin Zhao; Ziyun Ruan; Zhengda Li; Hongfang Mo; Fenghua Lu; Deshun Shi (Theriogenology, 2024)

Asp-tRNAAsn/Glu-tRNAGln amidotransferase A subunit-like amidase mediates the degradation of insecticide flonicamid by Variovorax boronicumulans CGMCC 4969 - Xue-Xiu Yu; Ke-Xin Chen; Pan-Pan Yuan; Yu-He Wang; Hua-Xiao Li; Yun-Xiu Zhao; Yi-jun Dai (Science of The Total Environment, 2024)

Three-phase Enriched Environment Improves Post-stroke Gait Dysfunction via Facilitating Neuronal Plasticity in the Bilateral Sensorimotor Cortex: A Multimodal MRI/PET Analysis in Rats - Yun Lu; Ziyue Lin; Mingcong Li; Yuming Zhuang; Binbin Nie; Jianfeng Lei; Yuanyuan Zhao; Hui Zhao (Neuroscience Bulletin, 2024)

Two new cytochalasins from the endophytic fungus Xylaria sp. GDGJ-77B - Zhao-Long Xu; Ben-Chao Li; Li-Li Huang; Liu-Xia Lv; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2024)

BDNF mimetics recover palmitic acid-induced injury in cardiomyocytes by ameliorating Akt-dependent mitochondrial impairments - Man-Ru Zhang; Bang-Yun Zuo; Yu-Chen Song; Dan-Dan Guo; Qing-Liu Li; Jin-Xiu Lyu; Hua Zhu; Jing Zhao; Peng-Zhou Hang (Toxicology and Applied Pharmacology, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Generation of a highly specific recombinant full-length antibody for detecting ethirimol in fruit and environmental water - Xingmei Lei; Peipei Li; A.M. Abd El-Aty; Jing Zhao; Lingyuan Xu; Song Gao; Jia Li; Yun Zhao; Yongxin She; Fen Jin; Jing Wang; Lufei Zheng; et al. (Journal of Hazardous Materials, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Soil inorganic carbon stock and its changes across the Tibetan Plateau during the 1980s–2020s - Honghong Lin; Xingwu Duan; Yifan Dong; Ronghua Zhong; Hua Zheng; Yun Xie; Li Rong; Haijuan Zhao; Shengzhao Wei (Global and Planetary Change, 2024)

hOGG1: A novel mediator in nitrosamine-induced esophageal tumorigenesis - De-Rong Tang; Cheng-Lin Li; Zhi-Yun Xu; Zhen-Zhong Zhang; Qian-Wei Wang; Jian-Qiang Zhao (Food and Chemical Toxicology, 2024)

Facile surface modification of cation exchange membranes via Debus-Radziszewski in-situ cross-linking for lithium extraction from salt-lakes - Xiang-Yun Xie; Hui-Qian Huo; Wen-Hao Zhang; Yan Zhao; Yan-Li Ji; Bart Van der Bruggen; Cong-Jie Gao (Chemical Engineering Journal, 2024)

Evaluation of the Efficacy of Stem Cells Therapy in the Periodontal Regeneration: A Meta-Analysis and Mendelian Randomization Study - Jing Hu; Ze-Yue Ou-Yang; Ya-Qiong Zhao; Jie Zhao; Li Tan; Qiong Liu; Min-yuan Wang; Qin Ye; Yao Feng; Meng-Mei Zhong; Ning-Xin Chen; Xiao-Lin Su; et al. (Stem Cell Reviews and Reports, 2024)

The treatment of petrochemical wastewater via ozone-persulfate coupled catalytic oxidation: mechanism of removal of soluble organic matter - Wenjing Guo; Chong Li; Junguang Zhao; Yun Ding; Qing Yang; Hongxun Guan (Environmental Science and Pollution Research, 2024)

Cadmium induced changes in rhizosphere microecology to enhance Cd intake by Ligusticum sinense cv. Chuanxiong - Yanluo Xie; Yun Zhao; Yi Li; Yang Wang; Jin Pei; Heng Xu (Journal of Hazardous Materials, 2024)

Tailoring whole slurry bioprocessing for sugary stovers to augment sugar production by integrating soluble and insoluble carbohydrates - Hossain M. Zabed; Suely Akter; Junhua Yun; Mostafa E. Elshobary; Sr Subroto Haldar; Mei Zhao; Faisal I. Chowdhury; Jia Li; Xianghui Qi (Journal of Cleaner Production, 2024)

Influential factors and interventions for repeated production violations in food enterprises - Empirical evidence from China - Tong Zhao; Taiping Li; Dan Liu; Yun Luo (Journal of Cleaner Production, 2024)

Simple synthesis, characterization and mechanism of Fe/Zr bimetallic-organic framework for Cr (VI) removal from wastewater - Yingxin Zhao; Xiaoyan Zhang; Weifeng Liu; Min Li; Yubing Chen; Yun Yang; Shuijin Yang (Journal of Environmental Chemical Engineering, 2024)

Investigation of hydrogen-propane hydrate formation mechanism and optimal pressure range via hydrate-based hydrogen storage - Pengfei Wang; Hao Long; Ying Teng; Yinglong Li; Yun Li; Jianbo Zhu; Heping Xie; Songbai Han; Yusheng Zhao; Jinlong Zhu (Fuel, 2024)

Hepatotoxicity induced in rats by chronic exposure to F–53B, an emerging replacement of perfluorooctane sulfonate (PFOS) - Xiaohan Li; Qian Zhang; Aiqing Wang; Shan Shan; Xueying Wang; Yarong Wang; Jianmei Wan; Ping Ning; Chengjiao Hong; Hailin Tian; Yun Zhao (Environmental Pollution, 2024)

Designing hollow mesoporous carbon sphere for high-rate supercapacitor in water-in-salt electrolyte - Liping Feng; Huichao Liu; Wenyan Zan; Sidian Li; Yunzhen Chang; Ying Zhang; Wenjing Hou; Yun Zhao; Sheng Zhu; Gaoyi Han (Chemical Engineering Journal, 2024)

Synergy of Mo doping and heterostructures in FeCo2S4@Mo-NiCo LDH/NF as durable and corrosion-resistance bifunctional electrocatalyst towards seawater electrolysis at industrial current density - Suyu Ge; Xueran Shen; Jiaxin Gao; Kaixuan Ma; Haoyu Zhao; Ruru Fu; Caihong Feng; Yun Zhao; Qingze Jiao; Hansheng Li (Chemical Engineering Journal, 2024)

Effects of heterovalent ions doping-induced oxygen octahedral distortion and defect chemical change on piezoelectric characteristics and thermal stability of PHT-PIN ceramics - Yun Qiao; Longlong Wang; Dongyan Zhang; Zhimin Li; Maolin Zhang; Li Jin; Mo Zhao; Yangxi Yan (Chemical Engineering Journal, 2024)

An untargeted metabolomics analysis of the components of heartwood and sapwood in 4 fast-growing Chinese fir (Cunninghamia lanceolata (Lamb.) Hook) clones - Xiaoqin Yang; Liping Li; Xiaorui Yu; Yun Liu; Sida Xie; Guolei Zhu; Junming Xu; Ping Zhao (Trees, 2024)

M2 macrophage-derived exosomes carry miR-142-3p to restore the differentiation balance of irradiated BMMSCs by targeting TGF-β1 - Chong Huang; Lu Zhao; Yun Xiao; Zihao Tang; Li Jing; Kai Guo; Lei Tian; Chunlin Zong (Molecular and Cellular Biochemistry, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Comparison of antioxidant capacity and immune response between low salinity tolerant hybrid and normal variety of Pacific white shrimp (Litopenaeus vannamei) - Yucong Ye; Bihong Zhu; Jiantao Yun; Ying Yang; Jiangtao Tian; Wenyue Xu; Xinglin Du; Yunlong Zhao; Yiming Li (Aquaculture International, 2024)

Paeoniflorin alleviated muscle atrophy in cancer cachexia through inhibiting TLR4/NF-κB signaling and activating AKT/mTOR signaling - Zixia Zhu; Cong Li; Xiaofan Gu; Xiaoting Wang; Gang Zhang; Meng Fan; Yun Zhao; Xuan Liu; Xiongwen Zhang (Toxicology and Applied Pharmacology, 2024)

Spatiotemporal variation in heatwaves and elderly population exposure across China - Yun Zhou; Songwei Gu; Hong Yang; Yao Li; Yinjun Zhao; Yuechen Li; Qingyuan Yang (Science of The Total Environment, 2024)

Source term estimation for continuous plume dispersion in Fusion Field Trial-07: Bayesian inference probability adjoint inverse method - Hong-Liang Zhang; Bin Li; Jin Shang; Wei-Wei Wang; Fu-Yun Zhao (Science of The Total Environment, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Thermal performance and ventilation analysis of a zigzag Trombe wall: Full numerical and experimental investigations - Hong-Liang Zhang; Bin Li; Dun-Ke Shi; Wei-Wei Wang; Fu-Yun Zhao (Energy and Buildings, 2024)

Designing and preparing supramolecular encapsulation systems based on fraxetin and cyclodextrins for highly selective detection of nicotine - Yun-Han Yang; Zhen Zhang; Qiu-Lian Bao; Fang Zhao; Ming-Kun Yang; Xin Tao; Yan Chen; Jun-Tong Zhang; Li-Juan Yang (Carbohydrate Polymers, 2024)

Improving categorical and continuous accuracy of precipitation forecasts by integrating Empirical Quantile Mapping and Bernoulli-Gamma-Gaussian distribution - Lingjie Li; Zhaode Yun; Yong Liu; Yintang Wang; Wenpeng Zhao; Yan Kang; Rui Gao (Atmospheric Research, 2024)

Investigation analysis of the acute asthma risk factor and phenotype based on relational analysis with outdoor air pollutants in Xi’an, China - Yiyi Lu; Xueyan Jie; Fan Zou; Dan Wang; Hongju Da; Hongxin Li; Hongyan Zhao; Jin He; Jianghao Liu; Xinping Fan; Yun Liu (Environmental Geochemistry and Health, 2024)

Performance enhancement of damaged RC structures with viscoelastic dampers: Damage assessment and optimal placement - Zhao-Dong Xu; Yuxuan Tao; Yun Yang; Yao-Rong Dong; Jin Duan; Shihua Li; Hao Wang; Shuai Wang (Soil Dynamics and Earthquake Engineering, 2024)

Basin-wide tracking of nitrate cycling in Yangtze River through dual isotope and machine learning - Fazhi Xie; Gege Cai; Guolian Li; Haibin Li; Xing Chen; Yun Liu; Wei Zhang; Jiamei Zhang; Xiaoli Zhao; Zhi Tang (Science of The Total Environment, 2024)

Advances in the study of silica nanoparticles in lung diseases - Li-Hong Ao; Yun-Geng Wei; Hong-Ru Tian; Hua Zhao; Jun Li; Jia-Qi Ban (Science of The Total Environment, 2024)

Lanostane triterpenoids from the fruiting bodies of Ganoderma amboinense - Li Yang; Guan-Hai Dong; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; You-Gen Wu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2024)

A modified methodology to substitute U-shape well using a single well with fracture network: Design and performance - Lin Jia; Kewen Li; Yun Han; Chi Zhang; Lipeng Zhao (Geothermics, 2024)

A neotype self-rectifying Cu3SnS4-MoO3 synaptic memristor for neuromorphic applications - Wenbin Wei; Hao Sun; Xiaofei Dong; Qiong Lu; Fangxia Yang; Yun Zhao; Jiangtao Chen; Xuqiang Zhang; Yan Li (Chemical Engineering Journal, 2024)

Visible-light-driven photo-Fenton oxidation enhanced by Fe/Bi-nanocrystal phase transformation as a universal way for various organic pollutants mineralization - Tulai Sun; Zi-Yan Jin; Bin Deng; Gan He; Qiong-Yu Wang; Mian Hu; Zhangliang Han; Zhaoke Zheng; Jun Zhao; Jimmy Yun; Jia Zhao; Yihan Zhu; et al. (Chemical Engineering Journal, 2024)

Metabolic engineering of Yarrowia lipolytica for high-level production of squalene - Ziying Liu; Mingkang Huang; Hong Chen; Xiangyang Lu; Yun Tian; Pengcheng Hu; Qiaoqin Zhao; Peiwang Li; Changzhu Li; Xiaojun Ji; Huhu Liu (Bioresource Technology, 2024)

Sustainable bio-manufacturing of D-arabitol through combinatorial engineering of Zygosaccharomyces rouxii, bioprocess optimization and downstream separation - Xiaolan Li; Hossain M. Zabed; Junhua Yun; Yufei Zhang; Mei Zhao; Cunsheng Zhang; Zhen Ouyang; Jia Li; Xianghui Qi (Bioresource Technology, 2024)

Analysis of the Immune Response by Standardized Whole-Blood Stimulation with Metabolism Modulation - Jialin Zhao; Xuling Han; Helian Li; Yali Luo; Yan Fang; Yun Wang; Jian Gao; Yiran Zhao; Jingxuan Han; Feng Qian (Phenomics, 2024)

The lncRNA lnc-TSI antagonizes sorafenib resistance in hepatocellular carcinoma via downregulating miR-4726-5p expression and upregulating KCNMA1 expression - Fengrong Chen; Jiong Jiang; Dong Liu; Hong Li; Lei Dong; Yahua Song; Ying Zhang; Jing Wang; Yun Qin; Gang Zhao (Journal of Molecular Histology, 2024)

Insight into the flame-retardant mechanism of different organic-modified layered double hydroxide for epoxy resin - Xiao-Hui Shi; Xue-Lin Li; Hong Shi; Qing-Yun Liu; Wei-Min Xie; Shi-Jie Wu; Nan Zhao; De-Yi Wang (Applied Clay Science, 2024)

Role of sleep in asthenospermia induced by di (2-ethyl-hexyl) phthalate - Xiao-lu Li; Xiao-yue Cai; Xia Ning; Yue-yue Liang; Yun Hong; Qi-meng Li; Die Hu; Yuan-zhuo Zheng; Yang Cai; Tao Xu; Ling-li Zhao (Environmental Science and Pollution Research, 2024)

Undescribed indole lactones from Alstonia scholaris protecting hepatic cell damage - Bin-Yuan Hu; Yun-Li Zhao; Ying-Jie He; Yan Qin; Xiao-Dong Luo (Phytochemistry, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Multiomics analyses of two Leonurus species illuminate leonurine biosynthesis and its evolution - Peng Li; Meng-Xiao Yan; Pan Liu; Dan-Jie Yang; Ze-Kun He; Yun Gao; Yan Jiang; Yu Kong; Xin Zhong; Sheng Wu; Jun Yang; Hong-Xia Wang; et al. (Molecular Plant, 2024)

Carbon emission scenarios of China's construction industry using a system dynamics methodology – Based on life cycle thinking - Zhao Zhang; Qiufeng Gao; Shuai Shao; Yun Zhang; Yining Bao; Li Zhao (Journal of Cleaner Production, 2024)

RuO2/CeO2 heterostructure anchored on carbon spheres as a bifunctional electrocatalyst for efficient water splitting in acidic media - Yun Wu; Rui Yao; Kaiyang Zhang; Qiang Zhao; Jinping Li; Guang Liu (Chemical Engineering Journal, 2024)

Multiple source tracking and identifications in urban regions with unstable wind flows: Particle swarm optimization methodologies and their benchmark solutions - Hong-Liang Zhang; Jun-Hao Chen; Bin Li; Wei-Wei Wang; Fu-Yun Zhao (Building and Environment, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Hierarchical and networked analysis of resilience factors in mountain communities in Southwest China - Yun-fei Zhao; Jian-min Cai; Lan Tang; Hai-bo Li; Shi-yu Hu; Hui-ge Xing (Natural Hazards, 2024)

Effects and mechanisms of resveratrol for prevention and management of cancers: An updated review - Si-Xia Wu; Ruo-Gu Xiong; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Cai-Ning Zhao; Ao Shang; Yun-Jian Zhang; Ren-You Gan; Hua-Bin Li (Critical Reviews in Food Science and Nutrition, 2023)

Revealing the driving factors for structure changes of regional water consumption: an empirical study of the middle route project of the South-to-North Water Diversion in China - Yuntong Zhao; Li Guo; Yun Li; Yixin Zhu; Zhe Cheng (Environment, Development and Sustainability, 2023)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

Arbuscular mycorrhizal fungi promote superior root trait combinations conducive to soil nutrient acquisition by natives relative to invaders - Kaiping Shen; Yuejun He; Tingting Xia; Yun Guo; Bangli Wu; Xu Han; Hongchun Chen; Yan Zhao; Jinting Li; Lu Gao; Xiaorun Hu; Li Wang (Rhizosphere, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Protective and immunomodulatory effects of mesenchymal stem cells on multiorgan injury in male rats with heatstroke - Yuyan Liu; Yun Li; Zihui Deng; Yan Zhao; Rui Yuan; Mengmeng Yang; Lu Wang; Yuan Fang; Dengfeng Ding; Feihu Zhou; Hongjun Kang (Journal of Thermal Biology, 2023)

Microplastics released from disposable medical devices and their toxic responses in Caenorhabditis elegans. - Tong Zhou; Jiajie Wu; Xi Hu; Zhenxiao Cao; Baolin Yang; Yang Li; Yanan Zhao; Yuting Ding; Yun Liu; An Xu (Environmental Research, 2023)

Rewiring Bacillus subtilis and bioprocess optimization for oxidoreductive reaction-mediated biosynthesis of D-tagatose - Guoyan Zhang; Yingfeng An; Hossain M Zabed; Junhua Yun; Amreesh Parvez; Mei Zhao; Cunsheng Zhang; Yuvaraj Ravikumar; Jia Li; Xianghui Qi (Bioresource Technology, 2023)

Structural characteristics of zooplankton communities in Hongze Lake driven by water environmental factors from 2016 to 2020 - Lixiao Ni; Haoyue Li; Lin Zhou; Jiahui Shi; Yun Nie; Feng Zhao; Shiyin Li (Environmental Monitoring and Assessment, 2023)

Simultaneous degradation of binary fluoroquinolone antibiotics by B and N in-situ self-doped guar gum hydrogel - Mingzhe Li; Mengling Ma; Ziwei Zhao; Mingkun Bao; Nan Zhang; Yun Zhou; Yian Zheng (Chemosphere, 2023)

Machine learning framework for intelligent aeration control in wastewater treatment plants: Automatic feature engineering based on variation sliding layer - Yu-Qi Wang; Hong-Cheng Wang; Yun-Peng Song; Shi-Qing Zhou; Qiu-Ning Li; Bin Liang; Wen-Zong Liu; Yi-Wei Zhao; Ai-Jie Wang (Water Research, 2023)

Environmental pollutants induce NLRP3 inflammasome activation and pyroptosis: Roles and mechanisms in various diseases - Yu Mou; Wenhao Liao; Yun Liang; Yuchen Li; Mei Zhao; Yaoyao Guo; Qin Sun; Jianyuan Tang; Zhilei Wang (Science of The Total Environment, 2023)

Lanostane triterpenoids with anti-proliferative and PTP1B/α-glucosidase inhibitory activities from the fruiting bodies of Ganoderma calidophilum - Li Yang; Ting-Ting Zhang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; Zhi-Fang Yu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2023)

Arsenic exposure and lung function decline in chronic obstructive pulmonary disease patients: The mediating influence of systematic inflammation and oxidative stress - Yun-Feng Liu; Min-Min Tang; Jing Sun; Jia-Fei Li; Ya-Lin Jiang; Hui Zhao; Lin Fu (Food and Chemical Toxicology, 2023)

Atomic pins bridging integrated surface to assist high-rate stability for Co-free Li-rich cathode - Yuefeng Su; Jiayu Zhao; Jinyang Dong; Qi Shi; Jianan Hao; Wenbo Li; Liying Bao; Yun Lu; Ning Li; Duanyun Cao; Lai Chen; Feng Wu (Chemical Engineering Journal, 2023)

Characterization of three new plant growth-promoting microbes and effects of the interkingdom interactions on plant growth and disease prevention - Yuan Tian; Yang Liu; Constantine Uwaremwe; Xia Zhao; Liang Yue; Qin Zhou; Yun Wang; Lam-Son Phan Tran; Weiqiang Li; Gaofeng Chen; Yuexia Sha; Ruoyu Wang (Plant Cell Reports, 2023)

High phytoplankton diversity in eutrophic states impedes lake recovery - Rong Wang; C. Patrick Doncaster; Wenxiu Zheng; Min Xu; Hui Yang; Yun Li; Yongjiu Cai; Yanjie Zhao; Enlou Zhang; Xiangdong Yang; Boqiang Qin (Journal of Biogeography, 2023)
Aim The widely observed positive response of productivity to biodiversity, known as the biodiversity‐productivity relationship (BPR), underpins nature‐based solutions for mitigating and adapting to global changes. Little is known of the role of such emergent processes in the restoration of damaged ecosystems. Here, we test for evidence of a BPR in degraded freshwater lakes, and its role in underpinning or undermining lake recovery from eutrophic states. Location Lower Yangtze and Huaihe river basins, China, East Asia. Taxa Freshwater phytoplankton; also macrophytes, fish, zooplankton and zoobenthos. Methods A systematic review of biodiversity studies was conducted to enumerate freshwater biodiversity change during eutrophication, encompassing 572 samples from 155 lakes in East China. Empirical samples were then taken of 93 phytoplankton communities from 38 lakes in ecologically degraded states of eutrophication. Samples were analysed for niche overlap in relation to biodiversity and productivity, and metrics of network structure indicative of community stability. Results Reviewed publications on eutrophication in East China lakes revealed losses in biodiversity of macrophytes, fishes, zooplankton and zoobenthos but not phytoplankton. Empirically sampled eutrophic lakes maintained high phytoplankton biodiversity through niche differentiation, and phytoplankton biodiversity correlated positively with biomass, in line with the expectations of BPR. Conclusions The positive effect of biodiversity on phytoplankton productivity in eutrophic lakes acts in opposition to the negative impacts on productivity induced by eutrophication‐management strategies of nutrient suppression. In degraded systems, the BPR contributes to sustaining productivity of lake phytoplankton communities, impeding recovery from a eutrophic state. This is a case of the BPR playing an undesirable role at the ecosystem level. Lake recovery programmes need to anticipate that the control of phytoplankton biomass will depend on reducing nutrients to a level sufficient to degrade the internal structure of the phytoplankton community.

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Expression of aldose reductase in mouse endometrial epithelial cells and its role in sperm capacitation - Yi Lei; Li Nie; Yun Long; Dan Zhao; Min Liu; Yi-cheng Wang; Xue-qin Zhang; Miao-miao Xu; Huan Liu; Jin-hu Zhang; Dong-zhi Yuan; Li-min Yue (Theriogenology, 2023)

Epicatechin promotes oocyte quality in mice during repeated superovulation - Yun Feng; Zhulian Wu; Xin Zhao; Mosinan Chen; Sijia Li; Canqiang Lu; Deshun Shi; Fenghua Lu (Theriogenology, 2023)

Dominant eccentricity cycles in paleoenvironmental variabilities recorded by pelagic sediments in the western Pacific during 15–11 Ma - Haifeng Wang; Xiguang Deng; Liang Yi; Guoqing Zhao; Yibing Li; Gongping Tu; Shijia Liu; Yinan Deng; Yong Yang; Yun Cai; Weiwei Chen; Gaowen He (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Distinct stochastic processes drive bacterial community assembly and co-occurrence patterns with common antibiotic resistance genes in two highly urbanised coastal ecosystems of the Pearl River Estuary - Keshu Zou; Yiyi Zhu; Yun Jiang; Shanshan Ma; Min Li; Wencheng Zhao; Jun Wang (Journal of Hazardous Materials, 2023)

Development of a recurrent spatiotemporal deep-learning method coupled with data fusion for correction of hourly ozone forecasts - Jie Li; Ji-cheng Jang; Yun Zhu; Che-Jen Lin; Shuxiao Wang; Jia Xing; Xinyi Dong; Jinying Li; Bin Zhao; Bingyao Zhang; Yingzhi Yuan (Environmental Pollution, 2023)

Single Ru atoms confined into MOF/C3N4 for dual improved photocatalytic carbon dioxide reduction and nitrogen fixation - Zhu Ding; Xusheng Li; Chenxu Kang; Sai Yan; Dandan Zhao; Houzhi Cai; Su-Yun Zhang; Yu-Jia Zeng (Chemical Engineering Journal, 2023)

Diode effects on street canyon ventilation in valley city: Temperature inversion and calm geostrophic wind - Jin Shang; Huai-Yu Zhong; Hong-Liang Zhang; Bin Li; Xiao-Xue Wang; Fu-Yun Zhao; Yuguo Li (Building and Environment, 2023)

A major QTL simultaneously increases the number of spikelets per spike and thousand-kernel weight in a wheat line - Conghao Zhao; Jieguang Zhou; Cong Li; Jianing You; Yanling Liu; Huaping Tang; Mei Deng; Qiang Xu; Yazhou Zhang; Qiantao Jiang; Guoyue Chen; Pengfei Qi; et al. (Theoretical and Applied Genetics, 2023)

FGF1 reduces cartilage injury in osteoarthritis via regulating AMPK/Nrf2 pathway - Yun-Xuan Li; Jun Shu; Nan-nan Kou; Han-Bo Chen; Li-Min Guo; Yong Yuan; Shao-Xuan He; Gang Zhao (Journal of Molecular Histology, 2023)

Population pharmacokinetics of topiramate in Chinese children with epilepsy - Shifeng Wei; Xingmeng Li; Qiang Zhang; Han Wu; Yun Wu; Zhigang Zhao; Shenghui Mei; Weixing Feng (European Journal of Clinical Pharmacology, 2023)

Modeling of breaching parameters for debris flow dams - He-chun Ruan; Hua-yong Chen; Xiao-qing Chen; Wan-yu Zhao; Jian-gang Chen; Tao Wang; Yao Jiang; Xi-an Wang; Xiang-ning Li; Xiao Li; Yun-han Yu (Journal of Mountain Science, 2023)

Real-time monitoring of endogenous cysteine in LPS-induced oxidative stress process with a novel lysosome-targeted fluorescent probe - Zhiqiang Yang; Jia Li; Sining Li; Jingxi Zhou; Zhixing Cao; Longxuan Li; Dongbin Zheng; Xuan Zhao; Wei Wang; Yun Deng; Yuyu Fang (Analytica Chimica Acta, 2023)

Interannual variation in gross ecosystem production and evapotranspiration in a temperate semiarid grassland undergoing vegetation recovery - Xinhao Li; Tianshan Zha; Peng Liu; Charles P.-A. Bourque; Xin Jia; Yun Tian; Chuan Jin; Xiaoshuai Wei; Xinyue Liu; Hongxian Zhao; Qingfeng Xu; Shaorong Hao (Agricultural and Forest Meteorology, 2023)

Pulmonary flora-modified diesel particulate matter induced lung injury via cGAS signaling pathway - Meng Sun; Tong Wang; Yemian Zhou; Qiao Liu; Mengzi Sun; Han Li; Yanan Zhao; Yun Liu; An Xu; Ying Liu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Effects of insulin-like growth factor 1, leukemia inhibitory factor, and basic fibroblast growth factor on goat oocyte maturation and early embryonic development in vitro - Zhao Gao-Ping; Shi Pei-Xin; Chang Qing; Wang Zi-Xin; Li Yun-Xia; Zhao Li-Xia; Sun Wei; Wu Meng; Bao Si-Qin; Cao Gui-Fang; Li Xi-He (Small Ruminant Research, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Association between phthalate exposure and obesity risk: A meta-analysis of observational studies - Qian Wu; Gang Li; Chen-Yang Zhao; Xiao-Lin Na; Yun-Bo Zhang (Environmental Toxicology and Pharmacology, 2023)

Phase behavior tuning enable high-safety and crack-free Ni-rich layered cathode for lithium-ion battery - Na Liu; Lai Chen; Haoyu Wang; Jiayu Zhao; Fei Gao; Jing Liu; Jinyang Dong; Yun Lu; Ning Li; Qi Shi; Yuefeng Su; Feng Wu (Chemical Engineering Journal, 2023)

Biomimetic redox-responsive prodrug micelles with diselenide linkage for platinum nanozymes augmented sonodynamic/chemo combined therapy of colon cancer - Yuanru Zhao; Jingwen Xu; Yuanyuan Zhang; Feng Wu; Wei Zhao; Runqing Li; Yun Yang; Mingzhen Zhang; Yujie Zhang; Cheng Guo (Chemical Engineering Journal, 2023)

Three new compounds isolated from the whole plants of Salsola collina pall - Wen-Zhi Wang; Zhao-Chun Zhan; Qing Tang; Ming Yan; Neng-Hua Chen; Hai-Yue Zhao; Hao-Yue Zhu; Huan-Qing Zhang; Zhong-Nan Wu; Hao-Yun Wang; Yu-Bo Zhang; Guo-Cai Wang; et al. (Natural Product Research, 2023)

Two lanostane triterpenoids with α -glucosidase inhibitory activity from the fruiting bodies of Ganoderma weberianum - De Xian Kong; Qing Yun Ma; Li Yang; Qing Yi Xie; Chun Ying Deng; Hao Fu Dai; Yan Hua; You Xing Zhao (Natural Product Research, 2023)

Metamorphic P–T evolution of the pelitic granulites from the Helanshan in the North China Craton revealed by phase equilibrium modeling and garnet trace elements: Implications for Paleoproterozoic collisional orogenesis - Xiao-Fei Xu; Long-Long Gou; Yun-Peng Dong; Cheng-Li Zhang; Xiao-Ping Long; Yu-Hang Zhao; Feng Zhou; Zhi-Bo Tian (Precambrian Research, 2023)

New insights into dry-coating-processed surface engineering enabling structurally and thermally stable high-performance Ni-rich cathode materials for lithium ion batteries - Feng Wu; Qi Shi; Lai Chen; Jinyang Dong; Jiayu Zhao; Haoyu Wang; Fei Gao; Jing Liu; Hongyun Zhang; Ning Li; Yun Lu; Yuefeng Su (Chemical Engineering Journal, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Metformin promotes ferroptosis and sensitivity to sorafenib in hepatocellular carcinoma cells via ATF4/STAT3 - Zongqiang Hu; Yingpeng Zhao; Laibang Li; Jie Jiang; Wang Li; Yuanyi Mang; Yang Gao; Yun Dong; Jiashun Zhu; Chaomin Yang; Jianghua Ran; Li Li; et al. (Molecular Biology Reports, 2023)
Background Hepatocellular carcinoma (HCC) is a common cancer worldwide, and sorafenib is a first-line drug for the treatment of advanced liver cancer. Resistance to sorafenib has become a major challenge in the treatment of hepatocellular carcinoma, however, studies have shown that metformin can promote ferroptosis and sorafenib sensitivity. Therefore, the aim of this study was to investigate the promotion of ferroptosis and sorafenib sensitivity by metformin via ATF4/STAT3 in hepatocellular carcinoma cells. Methods Hepatocellular carcinoma cells Huh7 and Hep3B and induced sorafenib resistance (SR) Huh7/SR and Hep3B/SR cells were used as in vitro cell models. Cells were injected subcutaneously to establish a drug-resistant mouse model. CCK-8 was used to detect cell viability and sorafenib IC 50 . Western blotting was used to detect the expression of relevant proteins. BODIPY staining was used to analyze the lipid peroxidation level in cells. A scratch assay was used to detect cell migration. Transwell assays were used to detect cell invasion. Immunofluorescence was used to localize the expression of ATF4 and STAT3. Results Metformin promoted ferroptosis in hepatocellular carcinoma cells through ATF4/STAT3, decreased sorafenib IC 50 , increased ROS and lipid peroxidation levels, decreased cell migration and invasion, inhibited the expression of the drug-resistant proteins ABCG2 and P-GP in hepatocellular carcinoma cells, and thus inhibited sorafenib resistance in hepatocellular carcinoma cells. Downregulating ATF4 inhibited the phosphorylated nuclear translocation of STAT3, promoted ferroptosis, and increased the sensitivity of Huh7 cells to sorafenib. Metformin was also shown in animal models to promote ferroptosis and sorafenib sensitivity in vivo via ATF4/STAT3. Conclusion Metformin promotes ferroptosis and sensitivity to sorafenib in hepatocellular carcinoma cells via ATF4/STAT3, and it inhibits HCC progression.

Scutellarin Acts via MAPKs Pathway to Promote M2 Polarization of Microglial Cells - Hao-Lun Chen; Li Yang; Xiao-Li-Na Zhang; Qiu-Ye Jia; Zhao-Da Duan; Juan-juan Li; Li-yang Zheng; Teng-teng Liu; Zhi Qi; Yun Yuan; Chun-Yun Wu (Molecular Neurobiology, 2023)

Inulin-type oligosaccharides of Morinda officinalis exerted antidepressant effects by reducing hippocampal inflammation - Zhao-Kai Lai; Yong-Yu Yin; Jiao-Zhao Yan; Qian-Qian Wei; Bin Wang; Yun-Feng Li; Li-Ming Zhang; Yu-Lu Wang (Metabolic Brain Disease, 2023)

Biodegradation of sulfoxaflor and photolysis of sulfoxaflor by ultraviolet radiation - Yun-Xiu Zhao; Ke-Xin Chen; Li Wang; Pan-Pan Yuan; Yi-Jun Dai (Biodegradation, 2023)

Climate and geochemistry at different altitudes influence soil fungal community aggregation patterns in alpine grasslands - Jia Li; Xia Wang; Jin Hong Wu; Yu Xin Sun; Yuan Ye Zhang; Yun Fei Zhao; Zheng Huang; Wen Hui Duan (Science of The Total Environment, 2023)

Chronic exposure to (2 R,6 R)-hydroxynorketamine induces developmental neurotoxicity in hESC-derived cerebral organoids - Zhulin Du; Zhenle Zang; Jing Luo; Tianyao Liu; Ling Yang; Yun Cai; Liuyongwei Wang; Dandan Zhang; Jinghui Zhao; Junwei Gao; Keyi Lv; Lian Wang; et al. (Journal of Hazardous Materials, 2023)

Supramolecular nanoassemblies-mediated GSH depletion boosts synergistic chemo- and photodynamic therapy for immunogenicity enhancement - Dun Wang; Wei Ma; Yun Huang; Wei Wang; Shuang Li; Hongbin Liu; Yuqi Zhao; Dongdong Peng; Cui-Yun Yu; Hua Wei (Chemical Engineering Journal, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Effect of lignocellulose/montmorillonite immobilized Bacillus sp. on monosodium glutamate wastewater - Bai-Yun Zhao; Xiao-Kai Liu; Xi-Lin Li; Li-Juan Zhou; Li Wang (Environmental Science and Pollution Research, 2023)

Intracellular electron competition in response to the oxygen pressure of the aerobic denitrification process in an O2-based membrane biofilm reactor (MBfR) for nitrate removal - Liang Feng; Fei-yun Sun; Jixian Yang; Di Cui; Zuo-hua Li; Shanshan Pi; He-Ping Zhao; Ang Li (Science of The Total Environment, 2023)

Two new α-pyrone derivatives from sponge-derived fungus Curvularia sp. ZYX-Z-4 - Qing-Hui Yan; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Ying Fu; You-Xing Zhao (Phytochemistry Letters, 2023)

Experimental and numerical investigations on the explosions nearby a free surface from both sides - Hao Tang; Zhao-Li Tian; Xin-Yang Ju; Ji-Tuan Feng; Yun-Long Liu; A-Man Zhang (Ocean Engineering, 2023)

Assessment of agricultural water resources carrying capacity and analysis of its spatio-temporal variation in Henan Province, China - Youming Zhang; Yun Gao; Yan Zhang; Zhijie Liang; Zulin Zhang; Yulong Zhao; Ping Li (Journal of Cleaner Production, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Tailoring porous three-dimensional (Co,Mn)(Co,Mn)2O4/PPy architecture towards high-performance cathode for aqueous zinc-ion batteries - Zuze Li; Yang Zheng; Qingze Jiao; Yun Zhao; Hansheng Li; Caihong Feng (Chemical Engineering Journal, 2023)

Superior triethylamine sensing platform based on MOF activated by carbon dots for photoelectric dual-mode in biphasic system - Xue-Chun Yang; Sha-Qi Fu; Qian-Li Li; Zheng Jiao; Jing-Tai Zhao; Yun Guo; Zhi-Jun Zhang; Song Gao; Ling-Li Cheng (Chemical Engineering Journal, 2023)

Reinforcing supramolecular hyaluronan hydrogels via kinetically interlocking multiple-units strategy - Ruofan Chen; Yujie Li; Yu Jin; Yawei Sun; Zhiyong Zhao; Yun Xu; Jiang-Fei Xu; Yuanchen Dong; Dongsheng Liu (Carbohydrate Polymers, 2023)

Discovery of seven-membered ring berberine analogues as highly potent and specific hCES2A inhibitors - Yun Yang; Yuan Xiong; Guanghao Zhu; Mengru Sun; Kun Zou; Yitian Zhao; Yong Zhang; Zhijian Xu; Yiming Li; Weiliang Zhu; Qi Jia; Bo Li; et al. (Chemico-Biological Interactions, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Large-scale characteristics of thermokarst lakes across the source area of the Yellow River on the Qinghai-Tibetan Plateau - Wen-hui Liu; Guang-hao Zhou; Hai-rui Liu; Qing-peng Li; Chang-wei Xie; Qing Li; Jian-yun Zhao; Qi Zhang (Journal of Mountain Science, 2023)

The sensitivity of mechanical properties and pore structures of Beishan granite to large variation of temperature in nuclear waste storage sites - Yun Wu; Li-Hua Hu; Jin Yu; Xiao-Zhao Li; Li-Ning Yang; Sen Xue; Kai Zhang (Environmental Science and Pollution Research, 2023)

Impact of commercial cooking on urban PM2.5 and O3 with online data-assisted emission inventory - Yingzhi Yuan; Yun Zhu; Che-Jen Lin; Shuxiao Wang; Yanghong Xie; Haixian Li; Jia Xing; Bin Zhao; Mengmeng Zhang; Zhiqiang You (Science of The Total Environment, 2023)

Colonic mechanism of serum NAD+ depletion induced by DEHP during pregnancy - Yun Hong; Xia Ning; Yue-yue Liang; Xiao-lu Li; Ya Cui; Wei Wu; Yang Cai; Shuai Zhao; Meng Zhu; Tian-xiao Zhong; Hua Wang; De-xiang Xu; et al. (Science of The Total Environment, 2023)

Combining mechanisms of black carbon and magnetic minerals in power plant fly ash - Meng Yao Li; Zhou Xin Peng; You Ying Chen; Shi Yun Xiao; Bo Wen Zhang; Yi Xin Shen; Sheng Kang Wang; Xue Song Wang; Zhao Xiang Han (Science of The Total Environment, 2023)

Isoquinoline alkaloids from Corydalis edulis Maxim. Exhibiting insulinotropic action - Zhi-Tian Peng; Hui-Xia Huo; Ling-Hui Chao; Yue-Lin Song; Di-Fa Liu; Zhang-Wei Wang; Yuan Zhang; Yun-Fang Zhao; Peng-Fei Tu; Jiao Zheng; Jun Li (Phytochemistry, 2023)

In-situ construction of hexagonal-star-shaped MnCo2S4@MoS2 boosting overall water splitting performance at large-current-density: Compositional-electronic regulation, functions, and mechanisms - Tiantian Ma; Xueran Shen; Qingze Jiao; Yun Zhao; Hansheng Li; Yaoyuan Zhang; Yuzhen Lv; Caihong Feng; Lin Guo (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Selection of the appropriate reference genes by quantitative real-time PCR in leopard coral groupers Plectropomus leopardus - Han Zhang; Haoran Yang; Pengsuo Li; Na Zhao; Xiaojuan Chen; Yongcan Zhou; Zhenjie Cao; Yun Sun (Journal of Oceanology and Limnology, 2023)

Thiomicrorhabdus marina sp.nov., an obligate chemolithoautotroph isolated from tidal zone sediment, and genome insight into the genus Thiomicrorhabdus - Xin-Yun Tan; Xin-Jiang Liu; Zhao Li; Fan Yu; Hui Yang; Zong-Jun Du; Meng-Qi Ye (Frontiers in Marine Science, 2023)
The contribution of microbes to the marine sulfur cycle has received considerable attention in recent years. In this study, a new Gram-stain-negative, aerobic sulfur-oxidizing bacterium, designated strain 6S2-11 T , was isolated from tidal zone sediment of the coast of Weihai, China. Strain 6S2-11 T was an obligate chemolithoautotroph utilizing thiosulfate as the energy source. Physiological and biochemical experiments, phylogenetic analysis, and comparative genomic analysis were done with strain 6S2-11 T . According to genomic analysis, strain 6S2-11 T owned a complete thiosulfate oxidation pathway and an untypical nitrogen metabolism pathway. Its relatively small genome also has multiple environmental adaptation mechanisms. The DNA G+C content of strain 6S2-11 T was 44.1%. Strain 6S2-11 T was observed to grow at 20-37°C (optimum, 35°C), pH 6.0-9.5 (optimum, pH 7.5), and 0.5-5% (w/v) NaCl (optimum, 2.5%). The major cellular fatty acids (>10%) of strain 6S2-11 T were Summed Feature 8 (C 18:1 ω7c/C 18:1 ω6c), C 16:0 and Summed Feature 3 (C 16:1 ω7c/C 16:1 ω6c). The comparison of 16S rRNA gene sequences indicated that strain 6S2-11 T was most closely to Thiomicrorhabdus xiamenensis G2 T (96.8%). Based on the results of phylogenetic analysis, the strain 6S2-11 T is a novel specie of the genus Thiomicrorhabdus , for which name Thiomicrorhabdus marina sp.nov. is proposed with the type strain 6S2-11 T (=MCCC 1H00523 T =KCTC 82994 T ).

Two new indole alkaloids isolated from a mangrove-derived fungus Colletotrichum sp. HD-1 - Dan He; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hong-Juan Zhu; Hao-Fu Dai; You-Gen Wu; Dong-Mei Yang; You-Xing Zhao (Phytochemistry Letters, 2023)

Combustion characteristics of three linear monohydric alcohols CH3(CH2)n-1OH (n = 16, 18, 22): Combined ignition experiments and molecular dynamics simulations - Xin Zhang; Yiming Zhao; Wenjuan Li; Yun Zhang; Siyu Xu; Sen Xu; Wen Zhou; Yizheng Fu; Yongan Feng; Weiguo Cao (Fuel, 2023)

Distributions of polychlorinated naphthalenes in beef from China and associated health risks - Shujun Dong; Jingguang Li; Lei Zhang; Su Zhang; Yun Zou; Yunfeng Zhao; Yongning Wu; Peilong Wang (Environmental Pollution, 2023)

The pivotal role of Ag species on porous nanosheets in the significant reduction of soot ignition temperature - Bing Cui; Kun Zhou; Miaomiao Hu; Tingyi Zhao; Yun-Quan Liu; Yan Li; Zhihui Shao; Mingqin Zhao (Chemical Engineering Journal, 2023)

In situ rapid and deep self-reconstruction of Fe-doped hydrate NiMoO4 for stable water oxidation at high current densities - Yijie Zhang; Rui Yao; Yun Wu; Qiang Zhao; Jinping Li; Guang Liu (Chemical Engineering Journal, 2023)

Canopy greenness, atmospheric aridity, and large rain events jointly regulate evapotranspiration partitioning in a temperate semiarid shrubland - Shaorong Hao; Xin Jia; Yanmei Mu; Tianshan Zha; Shugao Qin; Peng Liu; Yun Tian; Jiandong Qi; Hongxian Zhao; Xinhao Li (Agricultural and Forest Meteorology, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Ecotoxicity stress and bioaccumulation in Eisenia fetida earthworms exposed to vanadium pentoxide in soil - Shi-qing Zhao; Hong Ni; Ji Li; Shun-hao Ai; Xiao-nan Wang; Xiang-yun Gao; Qian-yun Xu; Zheng-tao Liu (Environmental Science and Pollution Research, 2023)

Evaluation of negative effect of Naphthenic acids (NAs) on physiological metabolism and polycyclic aromatic hydrocarbons adsorption of Phragmites australis - Hui Jia; Guang-xi Zhang; Yi-fan Wu; Wei-wei Dai; Quan-bin Xu; Shu Gan; Xiu-yun Ju; Zhao-zhong Feng; Rong-peng Li; Bo Yuan (Chemosphere, 2023)

Follicular fluid exosomes inhibit BDNF expression and promote the secretion of chemokines in granulosa cells by delivering miR-10b-5p - Chenfeng Yuan; Maosheng Cao; Lu Chen; Yun Zhao; Xue Chen; Caomeihui Shen; Chunjin Li; Xu Zhou (Theriogenology, 2023)

Strong binding of heavy metals in fayalite of copper smelting slags: Lattice site substitution - Fei Li; Sihai Zhang; Nengwu Zhu; Junyao Ke; Yun Zhao; Weiwen Ma; Pingxiao Wu (Science of The Total Environment, 2023)

Fractal characteristics of rocks and mesoscopic fractures at different loading rates - Yanming Lai; Kang Zhao; Zhiwei He; Xiang Yu; Yajing Yan; Qiang Li; Hai Shao; Xiangwei Zhang; Yun Zhou (Geomechanics for Energy and the Environment, 2023)

Concomitant oxidation of fatty acids other than DHA and EPA plays a role in the characteristic off-odor of fish oil - Yun-Qi Wen; Chang-Hu Xue; Hong-Wei Zhang; Li-Li Xu; Xiao-Han Wang; Shi-Jie Bi; Qian-Qian Xue; Yong Xue; Zhao-Jie Li; Joaquín Velasco; Xiao-Ming Jiang (Food Chemistry, 2023)

Comparison of tropomyosin released peptide and epitope mapping after in vitro digestion from fish (Larimichthys crocea), shrimp (Litopenaeus vannamei) and clam (Ruditapes philippinarum) through SWATH-MS based proteomics - LiLi Xu; Xiao Mei Zhang; Yun Qi Wen; Jin Long Zhao; Tong Cheng Xu; Ling Yong; Hong Lin; Hong Wei Zhang; Zhen Xing Li (Food Chemistry, 2023)

Phosphate-decorated Ni3Fe-LDHs@CoPx nanoarray for near-neutral seawater splitting - Tianshui Li; Xiuping Zhao; Marshet Getaye Sendeku; Xingheng Zhang; Ling Xu; Zhaolei Wang; Shiyuan Wang; Xinxuan Duan; Hai Liu; Wei Liu; Daojin Zhou; Haijun Xu; et al. (Chemical Engineering Journal, 2023)

Impacts of the long-term atmospheric trend on the seasonality of Antarctic sea ice - Fu Zhao; Xi Liang; Zhongxiang Tian; Chengyan Liu; Xichen Li; Yun Yang; Ming Li; Na Liu (Climate Dynamics, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Identification of marine natural product Pretrichodermamide B as a STAT3 inhibitor for efficient anticancer therapy - Rui Li; Yue Zhou; Xinxin Zhang; Lujia Yang; Jieyu Liu; Samantha M. Wightman; Ling Lv; Zhiqing Liu; Chang-Yun Wang; Chenyang Zhao (Marine Life Science & Technology, 2023)
The Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) regulates the expression of various critical mediators of cancer and is considered as one of the central communication nodes in cell growth and survival. Marine natural products (MNP) represent great resources for discovery of bioactive lead compounds, especially anti-cancer agents. Through the medium-throughput screening of our in-house MNP library, Pretrichodermamide B, an epidithiodiketopiperazine, was identified as a JAK/STAT3 signaling inhibitor. Further studies identified that Pretrichodermamide B directly binds to STAT3, preventing phosphorylation and thus inhibiting JAK/STAT3 signaling. Moreover, it suppressed cancer cell growth, in vitro, at low micromolar concentrations and demonstrated efficacy in vivo by decreasing tumor growth in a xenograft mouse model. In addition, it was shown that Pretrichodermamide B was able to induce cell cycle arrest and promote cell apoptosis. This study demonstrated that Pretrichodermamide B is a novel STAT3 inhibitor, which should be considered for further exploration as a promising anti-cancer therapy.

Two new tetrahydroisoquinoline alkaloids from Portulaca oleracea - Kai-Jun Tang; Yu Chen; Jing Li; Xu Tao; Lu-Ping Yang; Tian-Yun Jin; Jia-Shun Zhu; Yu Zhao; Tao Shen; Xiao-Ning Wang; Dong-Mei Ren; Lan Xiang (Phytochemistry Letters, 2023)

A method for estimating surface soil moisture from diurnal land surface temperature observations over vegetated regions: A preliminary result over an AmeriFlux site and the REMEDHUS network - Yun-Jing Geng; Pei Leng; Zhao-Liang Li (Journal of Hydrology, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Ability of ionic liquids to inhibit the formation of methane hydrate: Insights from molecular dynamics simulations - Yun Li; Shouheng Xiao; Bao Yuan; Pengfei Wang; Baifa Zhang; Qinqin Su; Xiaomeng Wang; Songbai Han; Jinlong Zhu; Yusheng Zhao (Gas Science and Engineering, 2023)

Highly stabilized single-crystal P2-type layered oxides obtained via rational crystal orientation modulation for sodium-ion batteries - Fengping Zhang; Yao Lu; Yun Guo; Chunliu Li; Yan Liu; Maofeng Yang; Binyu Zhao; Wenwei Wu; Xuehang Wu (Chemical Engineering Journal, 2023)

Efficient selective adsorption of cytokine IL-6 and other middle-macromolecular toxins in the serum of uremia patients with specially designed porous hollow carbon spheres - Xiaohuan Zhao; Chong Wang; Boyang Xu; Jie Liang; Keyang Li; Yiqing Guo; Ming Gong; Yun Zhao; Yilun Huang; Yuehong Li; Ming Zhao; Daming Zhuang; et al. (Chemical Engineering Journal, 2023)

Evaluation of physicochemical properties, bacterial community, and product fertility during rice straw composting supplemented with different nitrogen-rich wastes - Shi-Peng Wang; Xiao-Xing Li; Zhao-Yong Sun; Wen-Liang Shuai; Zi-Yuan Xia; Cai-Yun Xie; Min Gou; Yue-Qin Tang (Bioresource Technology, 2023)

Experimental and Numerical Investigations on Rock Breaking of TBM Disc Cutter Based on a Novel Platform with Rotational Cutting - Long-Chuan Deng; Fu-Bing Zhang; Xiao-Zhao Li; Chi Zhang; Yu-Kun Ji; Yun Wu (Rock Mechanics and Rock Engineering, 2023)

Subculture and Etiolation Treatment Promotes Rooting Ability of Upper Branches of Black Locust Crown - Jie Zhang; Ye Zhao; Anan Duan; Wei Wang; Yuhan Sun; Li Dong; Sen Cao; Xiuyu Li; Xiaodi Liu; Chao Han; Saleem Uddin; Wei Bi; et al. (Forest Science, 2023)
The black locust (Robinia pseudoacacia L.) is an economically and ecologically important tree worldwide. However, maturation and position effects affect its asexual reproduction. Despite etiolation treatment and successive subcultures promoting the plant cutting’s rooting rate, whether the promoting effects of aging (upper) branches and young (lower) branches are consistent is unknown. Therefore, we evaluated the relevant rooting ability indicators of tree age effect and its location effect in 26-year-old R. pseudoacacia trees and the current-year branches of different parts. Branches of the upper and lower parts of these trees underwent accelerated germination to generate shoots as explants. We subjected the tissue culture–generated shoots to an etiolation treatment to investigate how the treatment and subculture time affected the rooting ability of the shoot explants induced by different parts of the black locust branch. Tissue culture shoots subjected to the etiolation treatment exhibited a 2–3 day shorter rooting time. Shoots from the upper crown organs achieved a rejuvenation effect, which manifested as enhanced rooting capacity. Our study results provide a theoretical basis for maintaining the juvenility and consistency of clones. Besides having theoretical and practical value, our study also guides the selection of suitable propagation materials for production.

Generation of fast growth Nile tilapia (Oreochromis niloticus) by myostatin gene mutation - You Wu; Tengfei Wu; Lanying Yang; Yun Su; Chenhua Zhao; Lu Li; Jing Cai; Xiangyan Dai; Deshou Wang; Linyan Zhou (Aquaculture, 2023)

Analysis of iron in-use stocks: Evidence from the provincial and municipal levels in China - Qiang Yue; Xicui Chai; Feng Zhao; Junhao He; Yun Li; Heming Wang (Resources Policy, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

A chemometric study on the identification of 5-methylfurfural and 2-acetylfuran as particular volatile compounds of oxidized fish oil based on SHS-GC-IMS - Yun-Qi Wen; Hong-Wei Zhang; Chang-Hu Xue; Xiao-Han Wang; Shi-Jie Bi; Li-Li Xu; Qian-Qian Xue; Yong Xue; Zhao-Jie Li; Joaquín Velasco; Xiao-Ming Jiang (Food Chemistry, 2023)

Improving the viability of Lactobacillus plantarum LP90 by carboxymethylated dextran-whey protein conjugates: The relationship with glass transition temperature - Wen Li; Yunjiao Zhao; Yuan Zhao; Shunqin Li; Liyuan Yun; Zijian Zhi; Rui Liu; Tao Wu; Wenjie Sui; Min Zhang (Food Hydrocolloids, 2023)

Inversion of 137Cs emissions following the fukushima accident with adaptive release recovery for temporal absences of observations - Sheng Fang; Xinwen Dong; Shuhan Zhuang; Zhijie Tian; Yungang Zhao; Yun Liu; Yuanyuan Liu; Li Sheng (Environmental Pollution, 2023)

Identifying the impact of Fe nanoparticles encapsulated by nitrogen-doped carbon to Fe single atom sites for boosting oxygen reduction reaction toward Zn-air batteries - Wen-Jun Niu; Ying-Yun Yan; Ru-Ji Li; Wei-Wei Zhao; Jiang-Lei Chen; Ming-Jin Liu; Bingni Gu; Wen-Wu Liu; Yu-Lun Chueh (Chemical Engineering Journal, 2023)

Water-assistant ultrahigh fluorescence enhancement in perovskite polymer-encapsulated film for flexible X-ray scintillators - Yue Li; Qian-Li Li; Yan Li; Yun-Ling Yang; Shao-Lin Zhang; Jingtai Zhao; Jieqiong Wan; Zhijun Zhang (Chemical Engineering Journal, 2023)

High-level production of d-arabitol by Zygosaccharomyces rouxii from glucose: Metabolic engineering and process optimization - Xiaolan Li; Yufei Zhang; Hossain M. Zabed; Junhua Yun; Guoyan Zhang; Mei Zhao; Yuvaraj Ravikumar; Xianghui Qi (Bioresource Technology, 2023)

Elevated systemic immune inflammation level increases the risk of total and cause-specific mortality among patients with chronic kidney disease: a large multi-center longitudinal study - Wenguang Lai; Yun Xie; Xiaoli Zhao; Xiayan Xu; Sijia Yu; Hongyu Lu; Haozhang Huang; Qiang Li; Jun-Yan Xu; Jin Liu; Shiqun Chen; Yong Liu (Inflammation Research, 2023)

Shifts in periphyton research themes over the past three decades - Yihan Zhao; Yun Zhang; Jishu Guo; Jun Wang; Yanling Li (Environmental Science and Pollution Research, 2023)

Phosphorus Fertigation Conferred Lodging Tolerance and Improved Grain Quality in Chenopodium quinoa via Enhanced Root Proliferation and Stalk Strength - Yan Deng; Li Zhao; Sumera Anwar; Li-Guang Zhang; Fahad Shafiq; Hong-Xia Guo; Li-Xia Qin; Mei-Xia Wang; Chuang-Yun Wang (Journal of Soil Science and Plant Nutrition, 2022)

Magma evolution and mineralization of the Baixintan magmatic Ni–Cu sulfide deposit in Eastern Tianshan, Northwestern China - Yu Yan; Yun Zhao; Chunji Xue; Jiancai Pang; Lu Wang; Jia Chen; Yihao Liu; Huamin Li (International Journal of Earth Sciences, 2022)

Protective Effects of Sepia Ink Melanin on Hepatic Tissue in Streptozotocin-Induced Diabetic Mice - Xiaopeng Wang; Meng Han; Hui Dong; Yun Zhao; Weiwei Song; Chunlin Wang; Changkao Mu; Ronghua Li (Journal of Ocean University of China, 2022)

Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp ( Carassius auratus red var) after Aeromonas hydrophila challenge - Ning‐Xia Xiong; Xu‐Ying Kuang; Zi‐Xuan Fang; Jie Ou; Shi‐Yun Li; Jia‐Hui Zhao; Jin‐Fang Huang; Ke‐Xin Li; Rou Wang; Lan‐Fen Fan; Sheng‐Wei Luo; Shao‐Jun Liu (Journal of Fish Diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.

The Role of Pericytes in the Articular Environment—a Review - Stefano Negri; Zhao Li; Yiyun Wang; Masnsen Cherief; Qizhi Qin; Jiajia Xu; Mario Armando Gomez Salazar; Ginny Ching-Yun Hsu; Aaron W. James (Current Tissue Microenvironment Reports, 2022)

Stable isotopes of water as a tracer for revealing spatial and temporal characteristics of groundwater recharge surrounding Qinghai Lake, China - Dong-sheng Li; Bu-li Cui; Yun-duo Zhao; Feng-lin Zuo (Journal of Mountain Science, 2022)

Coastal aquaculture farms for the sea cucumber Apostichopus japonicus provide spawning and first-year nursery grounds for wild black rockfish, Sebastes schlegelii: A case study from the Luanhe River estuary, Bohai bay, the Bohai Sea, China - Min Xu; Zun-li Qi; Zun-lei Liu; Wei-min Quan; Qi Zhao; Yun-ling Zhang; Hui Liu; Lin-lin Yang (Frontiers in Marine Science, 2022)
Aquaculture farms are known to attract wild organisms from nearby areas. Sea cucumber Apostichopus japonicus aquaculture farms in Bohai Bay, the Bohai Sea, China, might provide spawning and nursery grounds for wild black rockfish Sebastes schlegelii populations. To identify the above, we studied the variation in the numbers of S. schlegelii larvae (and length-categories as a percentage of the natural population) via ichthyoplankton surveys by months from January to October 2020, and assessed the food web structure and energy flow distribution of the farm and trophic links of S. schlegelii natural stock by using Ecopath modeling in July 2016 to August 2017. Larvae with a length between 3.90-5.80 mm were observed in the farm in May 2020, the juveniles with an estimated trophic level of 4.31. Juveniles used the farms as first-year nursery ground, and then they swam into deeper waters in August of the following year. MTI analysis showed increasing biomass of S. schlegelii might result in a decrease in the biomass of crustacea, and had positive and negative impacts on mollusk and Hexagrammos otakii biomass. We argued that aquacultural infrastructures constructed by artificial reefs could be used as a fisheries management tool to enhance S. schlegelii stocks and that monitoring of other marine organisms, such as oysters, Rapana venosa , Charybdis japonica , and Asterias spp. etc., was necessary to maintain sustainable exploitations of aquacultural farm ecosystems. A paucity of knowledge surrounding the interactions between aquaculture farms and wild organisms needs furthermore researches.

Neuroprotection of Oral Edaravone on Middle Cerebral Artery Occlusion in Rats - Li-Qin Zhao; Ankit Parikh; Yun-Xia Xiong; Qing-Yan Ye; Ying-Guo; Xin-Fu Zhou; Hai-Yun Luo (Neurotoxicity Research, 2022)

Physiological and Molecular Analyses of Low-Salinity Stress Response in the Cuttlefish (Sepia pharaonis) Juveniles - Hongwei Xin; Kunlan Wu; Yimeng Yuan; Yun Zhao; Weiwei Song; Chunlin Wang; Changkao Mu; Ronghua Li (Journal of Ocean University of China, 2022)

Autism spectrum disorder-like behavior induced in rat offspring by perinatal exposure to di-(2-ethylhexyl) phthalate - Yao Li; Yun Zhao; Yu Lu; Xianxian Lu; Yingdan Hu; Qiulin Li; Menglei Shuai; Rui Li (Environmental Science and Pollution Research, 2022)

Investigation of the mechanism of Shen Qi Wan prescription in the treatment of T2DM via network pharmacology and molecular docking - Piaopiao Zhao; Xiaoxiao Zhang; Yuning Gong; Weihua Li; Zengrui Wu; Yun Tang; Guixia Liu (In Silico Pharmacology, 2022)

The study of schizogenous formation of secretory ducts in Ferula ferulaeoides (Steud.) Korov. - Meng-meng Liu; Yuan-yuan Zhao; Ying Ma; Shuang-shuang Liu; Jia-qi Yao; Ya-ping Chi; Hui-fang Li; Kai Liao; Yun Zhu (Protoplasma, 2022)

Photosynthesis-Related Proteins Play Crucial Role During Senescence Stage in Flue-Cured Tobacco Plants: A Combine iTRAQ-PRM Study - Conglian He; Shubin Sun; Yun Tang; Chenggang He; Pengfei Li; Tianyang Xu; Gaokun Zhao; Congming Zou; Zhonglong Lin; Yi Chen (Journal of Plant Growth Regulation, 2022)

Effects of thermal treatment on the macroscopic physical properties and microstructure of Beishan fine-grained granite - Zu-Xi Liu; Yun Wu; Xiao-Zhao Li; Zhen Huang; Jian Lin; Xiao-Hua Pan (Bulletin of Engineering Geology and the Environment, 2022)

Functional characterization of CD49f+ hepatic stem/progenitor cells in adult mice liver - Ziqi Guo; Shiming Pu; Yun Li; Xiaoxia Wang; Suying Hu; Hongxia Zhao; Cheng Yang; Zuping Zhou (Journal of Molecular Histology, 2022)

An integrated analysis of single-cell and bulk transcriptomics reveals EFNA1 as a novel prognostic biomarker for cervical cancer - Xiaopeng Shen; Meng Li; Yang Lei; Shan Lu; Sufen Wang; Zhongxian Liu; Chunguang Wang; Yun Zhao; Ao Wang; Chao Bi; Guoping Zhu (Human Cell, 2022)

Validation of Doppler Wind Lidar during Super Typhoon Lekima (2019) - Shengming Tang; Yun Guo; Xu Wang; Jie Tang; Tiantian Li; Bingke Zhao; Shuai Zhang; Yongping Li (Frontiers of Earth Science, 2022)

Individual exposure to ambient PM2.5 and hospital admissions for COPD in 110 hospitals: a case-crossover study in Guangzhou, China - Jie-Qi Jin; Dong Han; Qi Tian; Zhao-Yue Chen; Yun-Shao Ye; Qiao-Xuan Lin; Chun-Quan Ou; Li Li (Environmental Science and Pollution Research, 2022)
Few studies have evaluated the short-term association between hospital admissions and individual exposure to ambient particulate matter (PM 2.5 ). Particularly, no studies focused on hospital admissions for chronic obstructive pulmonary disease (COPD) at the individual level. We assessed the short-term effects of PM 2.5 on hospitalization admissions for COPD in Guangzhou, China, during 2014–2015, based on satellite-derived estimates of ambient PM 2.5 concentrations at a 1-km resolution near the residential address as individual-level exposure for each patient. Around 40,002 patients with COPD admitted to 110 hospitals were included in this study. A time-stratified case-crossover design with conditional logistic regression models was applied to assess the effects of PM 2.5 based on a 1-km grid data of aerosol optical depth provided by the National Aeronautics and Space Administration on hospital admissions for COPD. Further, we performed stratified analyses by individual demographic characteristics and season of hospital admission. Around 10 μg/m 3 increase in individual-level PM 2.5 was associated with an increase of 1.6% (95% confidence interval [CI]: 0.6%, 2.7%) in hospitalization for COPD at a lag of 0–5 days. The impact of PM 2.5 on hospitalization for COPD was greater significantly in males and patients admitted in summer. Our study strengthened the evidence for the adverse effect of PM 2.5 based on satellite-based individual-level exposure data.

Effect of Temperature on Macroscopic and Microscopic Properties of Sandstone From Qidong Coal Mine - Long-Chuan Deng; Xiao-Zhao Li; Ying-Chao Wang; Yun Wu; Zhen Huang; Chun-lu Jiang (Rock Mechanics and Rock Engineering, 2022)

Retraction Note to: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2022)

Eco-geological environment quality assessment based on multi-source data of the mining city in red soil hilly region, China - Fei-fei Zhao; Man-chao He; Yun-tao Wang; Zhi-gang Tao; Chun Li (Journal of Mountain Science, 2022)

Identification of bacterial blight resistance genes in rice landraces from Yunnan Province, China - Caimei Zhao; Fuyou Yin; Ling Chen; Dingqin Li; Suqin Xiao; Qiaofang Zhong; Bo Wang; Xue Ke; Jian Fu; Xiang Li; Yue Chen; Lingxian Wang; et al. (Australasian Plant Pathology, 2022)
Bacterial blight (BB), a serious bacterial disease caused by pathogen Xanthomonas oryzae pv. oryzae ( Xoo ) affects rice growth and yield. Yunnan Province is regarded as a center of rice diversity in China and indeed the world, and has abundant rice landrace resources, which may offer prospective candidate donors in rice improvement and breeding. In this study, a set of 200 rice landraces were evaluated to determine their resistance to 10 pathogenic Xoo strains resistance by the leaf-clipping method. The results indicated that the tested rice landraces had different resistance levels against different Xoo strains. Multiple comparisons showed that the Xoo strain PXO99 was virulent to the tested rice landraces. Sixty-six rice landraces conferred resistance against at least one Xoo strain. These resistant rice landraces screened were then performed the presence of 14 cloned BB resistance genes by closely linked molecular markers and designed specific primers. The results showed that none of these resistant accessions contained xa13 , Xa21 , Xa27 , and Xa45(t) homologous fragments, while 9, 24, 4, 7, 9, 15, 1, 5, 4 and 27 accessions contained Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa7 , Xa10 , Xa23 and xa25 homologous fragments, respectively. Sequence analysis further revealed that nucleotide variations around functional nucleotide polymorphisms region were observed within these accessions containing the Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa10 , Xa23 and xa25 homologous fragments. These results along with phenotypic resistance spectrum supported that these accessions carried nine resistance homologous genes. Only one accession (Qishanggu_Wenshan) carried the Xa7 resistance gene. We also found that some resistant rice landraces, especially Xilandigu_Baoshan, and Laoyaling_Lincang without the above resistance genes, which mediated broad spectrum resistance to multiple Xoo strains, were identified as potential sources for breeding rice lines resistance to BB.

Prediction of the vibration waveform of surface particles under the action of tunnel cutting blast - Yun He Li; Hai Long Wang; Yan Zhao; Jie Dong (Arabian Journal of Geosciences, 2022)

The combined effect of nitrogen deprivation and overexpression of malic enzyme gene on growth and lipid accumulation in Phaeodactylum tricornutum - Ruihao Zhang; Baohua Zhu; Changchao Tu; Yun Li; Yan Zhao; Kehou Pan (Journal of Applied Phycology, 2021)

A novel thermophilic β-carotene 15,15′-monooxygenase with broad substrate specificity from the marine bacterium Candidatus Pelagibacter sp. HTCC7211 - Zhangde Long; Yuzhe Zhao; Yun Xue; Min Wang; Jigang Li; Zan Su; Jiansheng Sun; Qibin Liu; Hong Liu; Duobin Mao; Tao Wei (Biotechnology Letters, 2021)

Tolerance Comparison Among Selected Spirulina Strains Cultured Under High Carbon Dioxide and Coal Power Plant Flue Gas Supplements - Qianqian Zhao; Guiyong Jin; Qiuke Liu; Kehou Pan; Baohua Zhu; Yun Li (Journal of Ocean University of China, 2021)

Alkaloids with acetylcholinesterase inhibitory activity from Corydalis racemosa (Thunb.) Pers - Hui-Na Yao; Zhi-Tian Peng; Yun-Feng Zhang; Di-Fa Liu; Bing-Feng Huang; Peng-Fei Tu; Yun-Fang Zhao; Hui-Xia Huo; Jun Li (Natural Product Research, 2021)

Triculata A, a novel compound from Tricyrtis maculata (D. Don) J. F. Macbr. with biological properties - Li Ren; Yun-Ze Wang; Wei Zhang; Rui Zhou; Ming Zhao; Zhi-Shu Tang; Jing Sun; Dong-Bo Zhang (Natural Product Research, 2021)

Silencing of ATG4D suppressed proliferation and enhanced cisplatin-induced apoptosis in hepatocellular carcinoma through Akt/Caspase-3 pathway - Jing-Yuan Zhao; Xiao-Yun Li; Tian-De Liu; Bo Liang; Yong Huang; Wen Li (Molecular and Cellular Biochemistry, 2021)

Directional arrangement of phyllite fragments in phyllite talus slope at the eastern margin of the Tibetan Plateau - Yu-hao Wan; Xiao-yan Zhao; Si-xiang Ling; Jin Li; Cai-yun Zeng; Wünnemann Bernd (Journal of Mountain Science, 2021)

Echinicola salinicaeni sp. nov., a novel bacterium isolated from saltern mud - Han Zhao; Chun-Yi Song; Rui Yin; Yan-Jun Yi; Shuai-Ting Yun; Ying-Xiu Li; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2021)

Protective effects of tetramethylpyrazine on dysfunction of the locus coeruleus in rats exposed to single prolonged stress by anti-ER stress mechanism - Yun Hou; Meifeng Li; Yinchuan Jin; Feibo Xu; Shaohua Liang; Chen Xue; Kaili Wang; Wei Zhao (Psychopharmacology, 2021)

Humoral immune durability of IgG for anti-SARS-CoV-2 in the normal pregnant women in Wuhan, China - Hongwen Ma; Jing Peng; Ruobing Li; Xuan Zheng; Shiyao Wu; Heng Yin; Min Li; Liu Qin; Fei Tang; Yun Zhao (Immunologic Research, 2021)

Influence of elevation on bioregionalisation: A case study of the Sino‐Himalayan flora - Yun Liu; Jian‐Fei Ye; Hai‐Hua Hu; Dan‐Xiao Peng; Li‐Na Zhao; Li‐Min Lu; Wajid Zaman; Zhi‐Duan Chen (Journal of Biogeography, 2021)
Aim Elevation is an important factor that influences bioregionalisation in mountainous areas, but its effects are not well known. Taking the Sino‐Himalayan flora as a case, we aimed to test the effect of elevation on bioregionalisation and provide a regionalisation scheme of the Sino‐Himalayan flora. Location The Sino‐Himalaya (East Himalaya, the Hengduan Mountains and the Yunnan Plateau in China). Taxon Angiosperms. Methods We compiled distribution data and elevation ranges of angiosperms in the Sino‐Himalaya and adjacent areas and reconstructed a species‐level phylogenetic tree of 19,313 angiosperm species. The area was divided into 398 grid cells, each 1 × 1°. Nine datasets of different elevation ranges were then used to delineate the flora of the Sino‐Himalaya and adjacent areas using the phylogenetic dissimilarity approach. Results A comparison of nine regionalisation schemes of the Sino‐Himalayan flora based on different elevation range datasets revealed that more than half of grid cells were allocated to more than one subregion. Most of these grid cells were located in areas with a wide range of elevation and/or at the boundaries between subregions. After revising the subregion allocations of eight shifting grid cells, we generated a phylogeny‐ and elevation‐based regionalisation scheme of three regions, comprising eight subregions, for the Sino‐Himalayan flora. Main conclusions By integrating phylogenetic and elevational information, the Sino‐Himalaya can be divided into three floristic regions: the Yunnan Plateau region, the Hengduan Mountains region and the East Himalaya region. Our study provides novel insights into the regionalisation of the flora and highlights the importance of incorporating elevation data in the bioregionalisation of areas with a broad elevational range.

Regression analysis of the blasting vibration effect in cross tunnels - Yan Zhao; Ren-liang Shan; Hai-long Wang; Xiao Tong; Yun-he Li (Arabian Journal of Geosciences, 2021)

The NDR kinase–MOB complex FgCot1‐Mob2 regulates polarity and lipid metabolism in Fusarium graminearum - Na Liu; Jing Wang; Yingzi Yun; Jinli Wang; Chaoyun Xu; Siqi Wu; Luona Xu; Baohua Li; Ilana Kolodkin‐Gal; Dawood H. Dawood; Youfu Zhao; Zhonghua Ma; et al. (Environmental Microbiology, 2021)
Summary Members of the NDR (nuclear Dbf2‐related) protein‐kinase family are essential for cell differentiation and polarized morphogenesis. However, their functions in plant pathogenic fungi are not well understood. Here, we characterized the NDR kinase FgCot1 and its activator FgMob2 in Fusarium graminearum , a major pathogen causing Fusarium head blight (FHB) in wheat. FgCot1 and FgMob2 formed a NDR kinase–MOB protein complex. Localization assays using FgCot1‐GFP or FgMob2‐RFP constructs showed diverse subcellular localizations, including cytoplasm, septum, nucleus and hyphal tip. Δ Fgcot 1 and Δ Fgmob 2 exhibited serious defects in hyphal growth, polarity, fungal development and cell wall integrity as well as reduced virulence in planta . In contrast, lipid droplet accumulation was significantly increased in these two mutants. Phosphorylation of FgCot1 at two highly conserved residues (S462 and T630) as well as five new sites synergistically contributed its role in various cellular processes. In addition, non‐synonymous mutations in two MAPK (mitogen‐activated protein kinase) proteins, FgSte11 and FgGpmk1, partially rescued the growth defect of Δ Fgmob2 , indicating a functional link between the FgCot1–Mob2 complex and the FgGpmk1 signalling pathway in regulating filamentous fungal growth. These results indicated that the FgCot1–Mob2 complex is critical for polarity, fungal development, cell wall organization, lipid metabolism and virulence in F. graminearum .

Mesozoic intracontinental deformation of the Alxa Block in the middle part of Central Asian Orogenic Belt: A review - Jin Zhang; Yannan Wang; Junfeng Qu; Beihang Zhang; Heng Zhao; Long Yun; Tianyi Li; Pengfei Niu; Fengjun Nie; Jie Hui; Yiping Zhang (International Geology Review, 2021)

Integrated transcriptome and miRNA sequencing approaches provide insights into salt tolerance in allotriploid Populus cathayana - Tong Qiu; Kang Du; Yanchun Jing; Qingqing Zeng; Zhao Liu; Yun Li; Yongyu Ren; Jun Yang; Xiangyang Kang (Planta, 2021)

Soil macropore networks derived from X-ray computed tomography in response to typical thaw slumps in Qinghai-Tibetan Plateau, China - Zhi-Guang Yang; Xia Hu; Xiao-Yan Li; Zhou Gao; Yun-Duo Zhao (Journal of Soils and Sediments, 2021)

Genome-wide association study of grain shapes in Aegilops tauschii - Xinpeng Zhao; Linlin Lv; Jiahui Li; Feifei Ma; Shenglong Bai; Yun Zhou; Dale Zhang; Suoping Li; Chun-peng Song (Euphytica, 2021)

Construction of a Full-Length Transcriptome Resource for the Chinese Sucker (Myxocyprinus asiaticus), a Rare Protected Fish, Based on Isoform Sequencing (Iso-Seq) - Hailong Ge; Haoyu Zhang; Qingyuan Zhao; Fang Li; Haoran Gu; Siying Liu; Haibo Yang; Yun Li; Zhijian Wang (Frontiers in Marine Science, 2021)

Effect of temperature on physical, mechanical and acoustic emission properties of Beishan granite, Gansu Province, China - Yun Wu; Xiao-Zhao Li; Zhen Huang; Sen Xue (Natural Hazards, 2021)

Gut microbiome alterations and its link to corticosteroid resistance in immune thrombocytopenia - Yanan Wang; Fengqi Liu; Gaochao Zhang; Yan Su; Xueyan Sun; Qi Chen; Chencong Wang; Haixia Fu; Yun He; Xiaolu Zhu; Xiao Liu; Meng Lv; et al. (Science China Life Sciences, 2021)

The optimal number of embryo cells for effective pregnancy and decrease of multiple pregnancy rate in frozen-thawed embryo transfer - Xu-Li Zhu; Zhi-Ming Zhao; Yuan-Jie Du; Liang Zhou; Yue Wang; Qing-Yun Sun; Gui-Min Hao; Bu-Lang Gao (Human Cell, 2021)

Effects of temperature and acid solution on the physical and tensile mechanical properties of red sandstones - Zhen Huang; Wei Zeng; Yun Wu; Shijie Li; Qixiong Gu; Kui Zhao (Environmental Science and Pollution Research, 2021)

Exploring and quantifying the relationship between instantaneous wind speed and turbidity in a large shallow lake: case study of Lake Taihu in China - Wenhao Ding; Jinxiao Zhao; Boqiang Qin; Tingfeng Wu; Senlin Zhu; Yun Li; Shikai Xu; Shiping Ruan; Yong Wang (Environmental Science and Pollution Research, 2021)

Correction to: P2Y12 receptor upregulation in satellite glial cells is involved in neuropathic pain induced by HIV glycoprotein 120 and 2',3'-dideoxycytidine - Zhihua Yi; Lihui Xie; Congfa Zhou; Huilong Yuan; Shuai Ouyang; Zhi Fang; Shanhong Zhao; Tianyu Jia; Lifang Zou; Shouyu Wang; Yun Xue; Bing Wu; et al. (Purinergic Signalling, 2021)

Description of the reservoir along strike-slip fault zones in China T-Sh oilfield, Tarim Basin - Rui Zhao; Shang Deng; Lu Yun; Huixi Lin; Teng Zhao; Chen Yu; Qiangfu Kong; Qiang Wang; Huili Li (Carbonates and Evaporites, 2021)

Pharaoh Cuttlefish, Sepia pharaonis, Genome Reveals Unique Reflectin Camouflage Gene Set - Weiwei Song; Ronghua Li; Yun Zhao; Herve Migaud; Chunlin Wang; Michaël Bekaert (Frontiers in Marine Science, 2021)
Sepia pharaonis , the pharaoh cuttlefish, is a commercially valuable cuttlefish species across the southeast coast of China and an important marine resource for the world fisheries. Research efforts to develop linkage mapping, or marker-assisted selection have been hampered by the absence of a high-quality reference genome. To address this need, we produced a hybrid reference genome of S. pharaonis using a long-read platform (Oxford Nanopore Technologies PromethION) to assemble the genome and short-read, high quality technology (Illumina HiSeq X Ten) to correct for sequencing errors. The genome was assembled into 5,642 scaffolds with a total length of 4.79 Gb and a scaffold N 50 of 1.93 Mb. Annotation of the S. pharaonis genome assembly identified a total of 51,541 genes, including 12 copies of the reflectin gene, that enable cuttlefish to control their body coloration. This new reference genome for S. pharaonis provides an essential resource for future studies into the biology, domestication and selective breeding of the species.

Expression of G9a in Auditory Cortex Is Downregulated in a Rat Model of Age-Related Hearing Loss - Qian Li; Yang-hong Xiang; Xiao-jun Liang; Yun Zhang; Peng-peng Zhao; Min Wang; Xiao-min Bao; Xian-bai Zhu; An-chun Deng (Journal of Molecular Neuroscience, 2021)

Formaldehyde-induced hematopoietic stem and progenitor cell toxicity in mouse lung and nose - Yun Zhao; Laura C. Magaña; Haiyan Cui; Jiawei Huang; Cliona M. McHale; Xu Yang; Mark R. Looney; Rui Li; Luoping Zhang (Archives of Toxicology, 2021)

A Continuous Pump Location Optimization Method for Water Pipe Network Design - Bohong Wang; Yongtu Liang; Wei Zhao; Yun Shen; Meng Yuan; Zhimin Li; Jian Guo (Water Resources Management, 2021)

Isoorientin exerts a urate-lowering effect through inhibition of xanthine oxidase and regulation of the TLR4-NLRP3 inflammasome signaling pathway - Meng-Fei An; Ming-Yue Wang; Chang Shen; Ze-Rui Sun; Yun-Li Zhao; Xuan-Jun Wang; Jun Sheng (Journal of Natural Medicines, 2021)

A Novel Fluorescent Probe Based on Pyrazole-Pyrazoline for Fe (III) Ions Recognition - Ying-Peng Zhang; Xiang-Fang Li; Yun-Shang Yang; Jing-Li Wang; Yu-Chen Zhao; Ji-Jun Xue (Journal of Fluorescence, 2021)

Evaluation of the stability of vegetated slopes according to layout and temporal changes - Yun-peng Li; Chao Hu; Li Jian; Ran Zhao; Chen Li (Journal of Mountain Science, 2021)

Insights into a giant landslide-prone area on the eastern margin of the Tibetan Plateau, China - Bo Zhao; Yun-sheng Wang; Jia Li; Jian-lin Wang; Chen-xiao Tang (Journal of Mountain Science, 2021)

Paenibacillus turpanensis sp. nov., isolated from a salt lake of Turpan city in Xinjiang province, north-west China - Li Yang; Hua-Wei Huang; Yun Wang; Ya-Rong Kou; Min Yin; Yu Li; Xue-Qian Wang; Gui-Fang Zhao; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Removal of Cadmium from Contaminated Groundwater Using a Novel Silicon/Aluminum Nanomaterial: An Experimental Study - Hanghang Zhao; Fengmin Song; Fengmei Su; Yun Shen; Peiyue Li (Archives of Environmental Contamination and Toxicology, 2021)

Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Neonatal curcumin treatment restores hippocampal neurogenesis and improves autism-related behaviors in a mouse model of autism - Hongyu Zhong; Rui Xiao; Ruotong Ruan; Hui Liu; Xin Li; Yun Cai; Jinghui Zhao; Xiaotang Fan (Psychopharmacology, 2020)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

An approach for water-inrush risk assessment of deep coal seam mining: a case study in Xinlongzhuang coal mine - Qixiong Gu; Zhen Huang; Shijie Li; Wei Zeng; Yun Wu; Kui Zhao (Environmental Science and Pollution Research, 2020)

A high-resolution melting analysis method for the effective discrimination of three Sepia species - Yun Zhao; Weiwei Song; Ronghua Li; Chunlin Wang; Changkao Mu (Journal of Consumer Protection and Food Safety, 2020)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

JAB1 promotes palmitate-induced insulin resistance via ERK pathway in hepatocytes - Yun Zhao; Suxian Ma; Xingna Hu; Min Feng; Rong Xiang; Min Li; Chenxiao Liu; Ting Lu; Aijie Huang; Jiaqi Chen; Mian Wu; Honghong Lu (Journal of Physiology and Biochemistry, 2020)

The peptidyl-prolyl isomerases FKBP15-1 and FKBP15-2 negatively affect lateral root development by repressing the vacuolar invertase VIN2 in Arabidopsis - Jun Wang; Wenjie Sun; Xiuzhen Kong; Chunyan Zhao; Jianfu Li; Yun Chen; Zhengyin Gao; Kaijing Zuo (Planta, 2020)

LncRNA NFIA-AS2 promotes glioma progression through modulating the miR-655-3p/ZFX axis - Jun Xin; Yu-Hong Zhao; Xi-Yun Zhang; Li-Qiang Tian (Human Cell, 2020)

Deformation and Failure Characteristics of Overburden Under Thin Bedrock and Thick Alluvium: A Case Study in Baodian Coal Mine - Yun Wu; Zhen Huang; Xiao-Zhao Li; Chun-Lu Jiang (Geotechnical and Geological Engineering, 2020)

Postchemotherapy hippocampal functional connectivity patterns in patients with breast cancer: a longitudinal resting state functional MR imaging study - Yun Feng; Dilihumaer Tuluhong; Zhao Shi; Li Juan Zheng; Tao Chen; Guang Ming Lu; Shaohua Wang; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Fumonisin B1 Affects the Biophysical Properties, Migration and Cytoskeletal Structure of Human Umbilical Vein Endothelial Cells - Xue Zhao; Yun Wang; Jiang-Li Liu; Jian-Hua Zhang; Shi-Chao Zhang; Yan Ouyang; Jiang-Tao Huang; Xiao-Yan Peng; Zhu Zeng; Zu-Quan Hu (Cell Biochemistry and Biophysics, 2020)

Directional seismic response to the complex topography: A case study of 2013 Lushan Ms 7.0 earthquake - Bo Zhao; Yun-sheng Wang; Li-jun Su; Yong-hong Luo; Jing Zhang (Journal of Mountain Science, 2020)

Lignin synthesized by CmCAD2 and CmCAD3 in oriental melon (Cucumis melo L.) seedlings contributes to drought tolerance - Wei Liu; Yun Jiang; Chenghui Wang; Lili Zhao; Yazhong Jin; Qiaojuan Xing; Meng Li; Tinghui Lv; Hongyan Qi (Plant Molecular Biology, 2020)

Benzophenone glycosides from the pericarps of Aquilaria yunnanensis S. C. Huang - Hui Sun; Yun-Feng Zhang; Hui-Xia Huo; Peng-Wei Guan; Chao-Chao Wang; Hui-Na Yao; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2020)

Lignin – An underutilized, renewable and valuable material for food industry - Jianming Tao; Sheng Li; Fayin Ye; Yun Zhou; Lin Lei; Guohua Zhao (Critical Reviews in Food Science and Nutrition, 2020)

Effect of different carboxymethyl cellulose structure parameters on tartrates stability of red wine: viscosity and degree of substitution - Haiyan Ding; Ruiting Hou; Yun Li; Beibei Zhang; Baobao Zhao; Kun Liu (Food Additives & Contaminants: Part A, 2020)

Genome-wide identification of the NPR1-like gene family in Brassica napus and functional characterization of BnaNPR1 in resistance to Sclerotinia sclerotiorum - Zheng Wang; Lu-Yue Ma; Xiao Li; Feng-Yun Zhao; Rehman Sarwar; Jun Cao; Yu-Long Li; Li-Na Ding; Ke-Ming Zhu; Yan-Hua Yang; Xiao-Li Tan (Plant Cell Reports, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

GelMA combined with sustained release of HUVECs derived exosomes for promoting cutaneous wound healing and facilitating skin regeneration - Danyang Zhao; Zhencheng Yu; Yun Li; Yu Wang; Qingfeng Li; Dong Han (Journal of Molecular Histology, 2020)

Coupled data assimilation and parameter estimation in coupled ocean–atmosphere models: a review - Shaoqing Zhang; Zhengyu Liu; Xuefeng Zhang; Xinrong Wu; Guijun Han; Yuxin Zhao; Xiaolin Yu; Chang Liu; Yun Liu; Shu Wu; Feiyu Lu; Mingkui Li; et al. (Climate Dynamics, 2020)

Correction to: Resveratrol prevents atrial fibrillation by inhibiting atrial structural and metabolic remodeling in collagen-induced arthritis rats - Yun Zhang; Song Zhang; Zonghong Liu; Xinbo Zhao; Yue Yuan; Li Sheng; Yue Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Reduction of Human DNA Contamination in Clinical Cerebrospinal Fluid Specimens Improves the Sensitivity of Metagenomic Next-Generation Sequencing - Xin-Chao Ji; Lin-Fu Zhou; Chao-Yang Li; Ya-Jun Shi; Meng-Li Wu; Yun Zhang; Xiao-Fei Fei; Gang Zhao (Journal of Molecular Neuroscience, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Retraction Note to: Effects of dietary glycerol monolaurate on productive performance, egg quality, serum biochemical indices, and intestinal morphology of laying hens - Min-jie Zhao; Hai-ying Cai; Meng-yun Liu; Ling-li Deng; Yang Li; Hui Zhang; Feng-qin Feng (Journal of Zhejiang University-SCIENCE B, 2020)

Next-generation sequencing technology as a powerful detection and semi-quantitative method for herpes simplex virus type 1 in pediatric encephalitis - Lin-lin Liu; Ling-yun Guo; Jie Dong; Wen-hua Huang; Li Zhao; Bing Liu; Xi-xi Zhang; Yong-qiang Jiang; Gang Liu (Journal of NeuroVirology, 2020)

Litorilituus lipolyticus sp. nov., isolated from intertidal sand of the Yellow Sea in China, and emended description of Colwellia asteriadis - Ang Liu; Yan-Jiao Zhang; Qing-Jie Xue; Hui Wang; Yuan-Yuan Yang; Feng Du; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2020)

Estimating the Hydraulic Conductivity of Deep Fractured Rock Strata from High-pressure Injection Tests - Zhen Huang; Shijie Li; Kui Zhao; Yun Wu; Wei Zeng; Hongwei Xu (Mine Water and the Environment, 2020)

Paraherquamide J, a new prenylated indole alkaloid from the marine-derived fungus Penicillium janthinellum HK1-6 - Yao-Yao Zheng; Nan-Xing Shen; Zhao-Yang Liang; Li Shen; Min Chen; Chang-Yun Wang (Natural Product Research, 2020)

Three-dimensional reconstruction of Picea wilsonii Mast. pollen grains using automated electron microscopy - Weiwei Shen; Lingyu Ma; Xi Zhang; Xixia Li; Yuanyuan Zhao; Yanping Jing; Yun Feng; Xueke Tan; Fei Sun; Jinxing Lin (Science China Life Sciences, 2020)

Nocardia panacis sp. nov., a novel actinomycete with antiphytopathogen activity isolated from the rhizosphere of Panax notoginseng - Jia-Yun Hu; Lei Li; Guang Peng; Yi-Qing Li; Li-Hua Xu; Hui-Lin Guan; Li-Xing Zhao; Cui-Ping Miao (Antonie van Leeuwenhoek, 2020)

Effects of different 2A peptides on transgene expression mediated by tricistronic vectors in transfected CHO cells - Yan-mei Li; Meng Wang; Tian-yun Wang; Yong-ge Wei; Xiao Guo; Chun-liu Mi; Chun-peng Zhao; Xiang-xiang Cao; Yuan-yuan Dou (Molecular Biology Reports, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

The synergetic effect of pelvic rotation and X-ray offset on radiographic angles of the acetabular cup - Jing-Xin Zhao; Xiu-Yun Su; Zhe Zhao; Ruo-Xiu Xiao; Guo-Fei Sun; Li-Cheng Zhang; Pei-Fu Tang (Medical & Biological Engineering & Computing, 2019)

RETRACTED ARTICLE: Effects of dietary glycerol monolaurate on productive performance, egg quality, serum biochemical indices, and intestinal morphology of laying hens - Min-jie Zhao; Hai-ying Cai; Meng-yun Liu; Ling-li Deng; Yang Li; Hui Zhang; Feng-qin Feng (Journal of Zhejiang University-SCIENCE B, 2019)

Complete genome sequences of five prunus necrotic ringspot virus isolates from Inner Mongolia of China and comparison to other PNRSV isolates around the world - Shuang Song; Ping-ping Sun; Ya-han Chen; Qiang Ma; Xiao-yun Wang; Ming-min Zhao; Zheng-nan Li (Journal of Plant Pathology, 2019)

Flavivirga rizhaonensis sp. nov., a marine bacterium isolated from intertidal sand - Ang Liu; Hong-Mei Liu; Feng Du; Shuang Wang; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Qing-Jie Xue; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2019)

Correction to: SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Re-examining the role of ventral tegmental area dopaminergic neurons in motor activity and reinforcement by chemogenetic and optogenetic manipulation in mice - Man-Yi Jing; Xiao Han; Tai-Yun Zhao; Zhi-Yuan Wang; Guan-Yi Lu; Ning Wu; Rui Song; Jin Li (Metabolic Brain Disease, 2019)

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

Assessment of slope construction risk uncertainty based on index importance ranking - Daming Lin; Ping Chen; Jilei Ma; Yun Zhao; Tao Xie; Renmao Yuan; Lin Li (Bulletin of Engineering Geology and the Environment, 2019)

Effective and economical column-based method for RNA isolation from animal cells - Qiaoge Niu; Maosheng Cao; Shuxiong Chen; Yun Zhao; Lu Chen; Chunjin Li; Xu Zhou (Biotechnology Letters, 2019)

A novel astrovirus identified in wild rhesus monkey feces in China - Yun-yun Xin; Li-li Li; Yuan-yun Ao; Zhi-ping Xie; Jin-song Li; Zhao-jun Duan; Jie-mei Yu; Bing Zhang (Archives of Virology, 2019)

Non-lipopeptide fungi-derived peptide antibiotics developed since 2000 - Pengchao Zhao; Yun Xue; Jinghua Li; Xin Li; Xiangyang Zu; Zhanqin Zhao; Chunshan Quan; Weina Gao; Shuxiao Feng (Biotechnology Letters, 2019)

Aldosterone stimulation mediates cardiac metabolism remodeling via Sirt1/AMPK signaling in canine model - Guang-zhong Liu; Song Zhang; Yan-yan Li; Yong-wu Liu; Yun Zhang; Xin-bo Zhao; Yue Yuan; Jia-wei Zhang; Zulfiia Khannanova; Yue Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Methane emissions responding to Azolla inoculation combined with midseason aeration and N fertilization in a double-rice cropping system - Ya-Dong Yang; He-Shui Xu; Deng-Yun Li; Jing-Na Liu; Jiang-Wen Nie; Zhao-Hai Zeng (Environmental Science and Pollution Research, 2019)

CO2 capture by ionic liquid membrane absorption for reduction of emissions of greenhouse gas - Jian-Gang Lu; Xiang Li; Yun-Xia Zhao; Hong-Lu Ma; Li-Fan Wang; Xin-Yi Wang; Yu-Fan Yu; Ting-Yu Shen; Hao Xu; Yu-Ting Zhang (Environmental Chemistry Letters, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Experimental investigation of fracture propagation and inrush characteristics in tunnel construction - Zhen Huang; Wei Zeng; Yun Wu; ShiJie Li; Kui Zhao (Natural Hazards, 2019)

Influence of shrub roots on soil macropores using X-ray computed tomography in a shrub-encroached grassland in Northern China - Xia Hu; Xiao-Yan Li; Lan-Lan Guo; Yong Liu; Pei Wang; Yun-Duo Zhao; Ya-Qian Cheng; Yan-Li Lyu; Lian-You Liu (Journal of Soils and Sediments, 2019)

β-Glucanase specific expression in the intestine of transgenic pigs - Li-zeng Guan; Shuai Zhao; Gang Shu; Qing-yan Jiang; Geng-yuan Cai; Zhen-fang Wu; Qian-yun Xi; Yong-liang Zhang (Transgenic Research, 2019)

Distribution characteristics of the additional vertical stress on a shaft wall in thick and deep alluvium: a simulation analysis - Yun Wu; Shu-yun Zhu; Xiao-zhao Li; Hui Zhang; Zhen Huang (Natural Hazards, 2019)

Landslide integrated characteristics and susceptibility assessment in Rongxian county of Guangxi, China - Li-ping Liao; Ying-yan Zhu; Yan-lin Zhao; Hai-tao Wen; Yun-chuan Yang; Li-hua Chen; Shao-kun Ma; Ying-zi Xu (Journal of Mountain Science, 2019)

Cancer-associated fibroblasts promote the stemness of CD24+ liver cells via paracrine signaling - Yawen Li; Ronghua Wang; Si Xiong; Xiju Wang; Zhenxiong Zhao; Shuya Bai; Yun Wang; Yuchong Zhao; Bin Cheng (Journal of Molecular Medicine, 2019)

Ferret badger rabies in Zhejiang, Jiangxi and Taiwan, China - Jing-Hui Zhao; Li-Feng Zhao; Fei Liu; Hong-Yun Jiang; Ji-Li Yang (Archives of Virology, 2019)

Resveratrol prevents atrial fibrillation by inhibiting atrial structural and metabolic remodeling in collagen-induced arthritis rats - Yun Zhang; Song Zhang; Zonghong Liu; Xinbo Zhao; Yue Yuan; Li Sheng; Yue Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Confluentibacter flavum sp. nov., Isolated from the Saline Lake - Yu. Li; Xin-Jun Hou; Xia Shen; Shuai-Bo Han; Zhao Ju; Zhe Zhao; Xiao-Yun Yu; Min Wu; Cong Sun (Current Microbiology, 2018)

Calcium store refilling and STIM activation in STIM- and Orai-deficient cell lines - Sisi Zheng; Lijuan Zhou; Guolin Ma; Tian Zhang; Jindou Liu; Jia Li; Nhung T. Nguyen; Xiaoyan Zhang; Wanjie Li; Robert Nwokonko; Yandong Zhou; Fukuan Zhao; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Regulatory Effect of General Anesthetics on Activity of Potassium Channels - Yan Li; Jie Xu; Yun Xu; Xiao-Yun Zhao; Ye Liu; Jie Wang; Guang-Ming Wang; Yan-Tian Lv; Qiong-Yao Tang; Zhe Zhang (Neuroscience Bulletin, 2018)

Gram-negative bacilli-derived peptide antibiotics developed since 2000 - Yun Xue; Mengya Wang; Pengchao Zhao; Chunshan Quan; Xin Li; Lina Wang; Weina Gao; Jinghua Li; Xiangyang Zu; Dongliao Fu; Shuxiao Feng; Ping Li (Biotechnology Letters, 2018)

Chromium malate alleviates high-glucose and insulin resistance in L6 skeletal muscle cells by regulating glucose uptake and insulin sensitivity signaling pathways - Weiwei Feng; Yangyang Ding; Weijie Zhang; Yao Chen; Qian Li; Wei Wang; Hui Chen; Yun Feng; Ting Zhao; Guanghua Mao; Liuqing Yang; Xiangyang Wu (BioMetals, 2018)

Identification of Neoscytalidium dimidiatum causing canker disease of pitaya in Hainan, China - Min Xu; Yun Peng; Zhao Qi; Zhen Yan; Lu Yang; Meng-Die He; Qing-Xiu Li; Cheng-Li Liu; Yun-Ze Ruan; Shuang-Shuang Wei; Jun Xie; You-Quan Xia; et al. (Australasian Plant Pathology, 2018)

Declining hailstorm frequency in China during 1961–2015 and its potential influential factors - Wenhui Zhao; Jianping Guo; Zhanyu Yao; Yuxing Yun; Shuo Jia; Weijian Wang; Pei Zhang; Hui Xu; Huan Liu; Liangshu Gao; Yanluan Lin; Mingxin Li; et al. (International Journal of Climatology, 2018)
Based on 55 years (from 1961 to 2015) of ground‐based hailstorm and atmospheric sounding observations, the climatological characteristics of hailstorms in China, along with potential influencing factors, were analysed. We found that hailstorms exhibit large spatial and temporal variability, with the peak occurring in spring in south China, and in summer in north China. The Tibetan Plateau (TTP) is a region with high hailstorm frequency. Overall, the frequency of hailstorms has decreased over the 55 years, although there was an increase from 1961 to 1985. In terms of diurnal variability, while hailstorm frequency peaks in the afternoon in most of China, it peaks during the night or early morning in southwest China. The magnitude of the peak increased during the 1960s and 1970s, and then decreased afterwards. Hailstorms are negatively correlated with daily mean temperature but are positively correlated with diurnal temperature range, convective available potential energy (CAPE) and totals–totals index. The increase of hailstorms during the period from 1961 to 1985 is mainly correlated with the increase in CAPE over the TTP region, while the decrease of hailstorms afterwards is correlated with all four convective parameters. The finding has significant implications for the potential impact of increasing greenhouse gases on climatological changes in hailstorm.

Sexual characteristics of male guppies Poecilia reticulata serve as effect biomarkers of estrogens - Hua Tian; Yun Li; Wei Wang; Fei Zhao; Su Gao; Shaoguo Ru (Journal of Oceanology and Limnology, 2018)

Experimental infection of Marmota monax with a novel hepatitis A virus - Jie-mei Yu; Li-li Li; Guang-cheng Xie; Cui-yuan Zhang; Yuan-yun Ao; Zhao-jun Duan (Archives of Virology, 2018)

Heterogeneous expression of the cotton R2R3-MYB transcription factor GbMYB60 increases salt sensitivity in transgenic Arabidopsis - Fu-Chun Xu; Hui-Li Liu; Yun-Yun Xu; Jing-Ruo Zhao; Ya-Wei Guo; Lu Long; Wei Gao; Chun-Peng Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Effects of cold acclimation on the survival, feeding rate, and non-specific immune responses of the freshwater red claw crayfish (Cherax quadricarinatus) - Dong-Lei Wu; Zhi-Quan Liu; You-Hui Huang; Wei-Wei Lv; Ming-Hai Chen; Yi-Ming Li; Yun-Long Zhao (Aquaculture International, 2018)

Polyphasic taxonomic characterisation of a novel strain as Pararhizobium haloflavum sp. nov., isolated from soil samples near a sewage treatment tank - Xia Shen; Yu Li; Zhe Zhao; Yi-Fan Han; Wen-Wu Zhang; Xiao-Yun Yu; Chong-Ya Zhang; Cong Sun; Min Wu (Antonie van Leeuwenhoek, 2018)

P2Y12 receptor upregulation in satellite glial cells is involved in neuropathic pain induced by HIV glycoprotein 120 and 2′,3′-dideoxycytidine - Zhihua Yi; Lihui Xie; Congfa Zhou; Huilong Yuan; Shuai Ouyang; Zhi Fang; Shanhong Zhao; Tianyu Jia; Lifang Zou; Shouyu Wang; Yun Xue; Bing Wu; et al. (Purinergic Signalling, 2018)

Characteristics of polycyclic aromatic hydrocarbons in PM2.5 emitted from different cooking activities in China - Yun-Chun Li; Jia-Qian Qiu; Man Shu; Steven Sai Hang Ho; Jun-Ji Cao; Ge-Hui Wang; Xian-Xiang Wang; Xiao-Qing Zhao (Environmental Science and Pollution Research, 2018)

Soybean and cottonseed meals are good candidates for fishmeal replacement in the diet of juvenile Macrobrachium nipponense - Yu-Juan Huang; Nan-Nan Zhang; Wu-Jiang Fan; Yan-Yan Cui; Samwel Mchele Limbu; Fang Qiao; Yun-Long Zhao; Li-Qiao Chen; Zhen-Yu Du; Dong-Liang Li (Aquaculture International, 2018)

Cultivation of seaweed Gracilaria lemaneiformis enhanced biodiversity in a eukaryotic plankton community as revealed via metagenomic analyses - Zhao Yang Chai; Zhi Li He; Yun Yan Deng; Yu Feng Yang; Ying Zhong Tang (Molecular Ecology, 2018)
Plankton diversity reflects the quality and health of waters and should be monitored as a critical feature of marine ecosystems. This study applied a pair of 28S r RNA gene‐specific primers and pyrosequencing to assess the effects of large‐scale cultivation of the seaweed Gracilaria lemaneiformis on the biodiversity of eukaryotic plankton community in the coastal water of Guangdong, China. With 1 million sequences (2,221 operational taxonomic units [ OTUs ]) obtained from 51 samples, we found that the biodiversity of eukaryotic plankton community was significantly higher in the seaweed cultivation area than that in the nearby control area as reflected in OTU richness, evenness (Shannon–Wiener index) and dominance (Simpson index) for total plankton community and its four subcategories when Gracilaria biomass reached the maximum, while no such a significant difference was observed before seaweed inoculation. Our laboratory experiment using an artificial phytoplankton community of nine species observed the same effects of Gracilaria exposure. Principal component analysis and principal coordinates analysis showed the plankton community structure in cultivation area markedly differed from the control area when Gracilaria biomass reached its maximum. Redundancy analysis showed that G. lemaneiformis was the critical factor in controlling the dynamics of eukaryotic plankton communities in the studied coastal ecosystem. Our results explicitly demonstrated G. lemaneiformis cultivation could enhance biodiversity of plankton community via allelopathy, which prevents one or several plankton species from blooming and consequently maintains a relatively higher biodiversity. Our study provided further support for using large‐scale G. lemaneiformis cultivation as an effective approach for improving costal ecosystem health.

The lateralized arcuate fasciculus in developmental pitch disorders among mandarin amusics: left for speech and right for music - Xizhuo Chen; Yanxin Zhao; Suyu Zhong; Zaixu Cui; Jiaqi Li; Gaolang Gong; Qi Dong; Yun Nan (Brain Structure and Function, 2018)

Blood Mercury, Arsenic, Cadmium, and Lead in Children with Autism Spectrum Disorder - Huamei Li; Hui Li; Yun Li; Yujie Liu; Zhengyan Zhao (Biological Trace Element Research, 2018)

Phytoactinopolyspora halotolerans sp. nov., a halotolerant actinobacterium isolated from a saline soil in Xinjiang, northwest of China - Yang Ji; Wei-Xun Chunyu; En-Yuan Li; Zhang-Gui Ding; Min Yin; Yu-Rong Zhao; Yun Wang; Shu-Kun Tang (Antonie van Leeuwenhoek, 2018)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Erratum to: Role of dopamine projections from ventral tegmental area to nucleus accumbens and medial prefrontal cortex in reinforcement behaviors assessed using optogenetic manipulation - Xiao Han; Man-yi Jing; Tai-yun Zhao; Ning Wu; Rui Song; Jin Li (Metabolic Brain Disease, 2017)

Role of dopamine projections from ventral tegmental area to nucleus accumbens and medial prefrontal cortex in reinforcement behaviors assessed using optogenetic manipulation - Xiao Han; Man-yi Jing; Tai-yun Zhao; Ning Wu; Rui Song; Jin Li (Metabolic Brain Disease, 2017)

Estimation of Heavy-Metal Contamination in Soil Using Remote Sensing Spectroscopy and a Statistical Approach - Kai Liu; Dong Zhao; Jun-yong Fang; Xia Zhang; Qing-yun Zhang; Xue-ke Li (Journal of the Indian Society of Remote Sensing, 2017)

Parental attendance of Chestnut Thrush reduces nest predation during the incubation period: compensation for low nest concealment? - Yun-Biao Hu; Qing-Shan Zhao; Ying-Qiang Lou; Li-Jun Chen; Manuel Antonio González; Yue-Hua Sun (Journal of Ornithology, 2017)

Sediment recycling and indication of weathering proxies - Yulong Guo; Shouye Yang; Chao Li; Lei Bi; Yun Zhao (Acta Geochimica, 2017)

A new sucrosephenylpropanoid ester from Polygonum pubescens Blume - Qiang Liu; Bin Li; Jianping Zhao; Shabana I. Khan; Wen-Bin Liu; Ting Zeng; Cai-Yun Peng; Xiong Cai; Qinghua Peng; Huiyong Huang; Ikhlas A. Khan; Wei Wang (Natural Product Research, 2017)

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua - Ya-Nan Zhang; Long-Wa Zhang; Da-Song Chen; Liang Sun; Zhao-Qun Li; Zhan-Feng Ye; Mei-Yan Zheng; Jin-Bu Li; Xiu-Yun Zhu (Molecular Genetics and Genomics, 2017)

Erratum to: The effect of sinomenine in diabetic neuropathic pain mediated by the P2X3 receptor in dorsal root ganglia - Shenqiang Rao; Shuangmei Liu; Lifang Zou; Tianyu Jia; Shanhong Zhao; Bing Wu; Zhihua Yi; Shouyu Wang; Yun Xue; Yun Gao; Changshui Xu; Guilin Li; et al. (Purinergic Signalling, 2017)

The effect of sinomenine in diabetic neuropathic pain mediated by the P2X3 receptor in dorsal root ganglia - Shenqiang Rao; Shuangmei Liu; Lifang Zou; Tianyu Jia; Shanhong Zhao; Bing Wu; Zhihua Yi; Shouyu Wang; Yun Xue; Yun Gao; Changshui Xu; Guilin Li; et al. (Purinergic Signalling, 2017)

Distribution of heavy metals in maize and mudflat saline soil amended by sewage sludge - Yan-Chao Bai; Wen-Gang Zuo; Hai-Tao Zhao; Li-Juan Mei; Chuan-Hui Gu; Yong-Xiang Guan; Xu-Kui Wang; Min-Jing Gu; Cai-Yun Zang; Yu-Hua Shan; Ke Feng (Journal of Soils and Sediments, 2017)

RETRACTED ARTICLE: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Furofuran lignan glucosides from the leaves of Vitex negundo var. cannabifolia - Yue-Ting Li; Man-Man Li; Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Dao-Ran Pang; Jiao Zheng; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Role of the SPS Gene Families in the Regulation of Sucrose Accumulation in Sugarcane - Dong-Liang Huang; Cui-Xian Qin; Yi-Yun Gui; Li-Han Zhao; Zhong-Liang Chen; Miao Wang; Yue Sun; Qing Liao; Yang-Rui Li; Prakash Lakshmanan (Sugar Tech, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

Anti-neuroinflammatory constituents from the fungus Penicillium purpurogenum MHZ 111 - Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Yi Ren; Dan Dong; Jiao Zheng; Ting Liu; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Variation in accumulation and translocation of di-n-butyl phthalate (DBP) among rice (Oryza sativa L.) genotypes and selection of cultivars for low DBP exposure - Quan-Ying Cai; Pei-Yun Xiao; Hai-Ming Zhao; Huixiong Lü; Qiao-Yun Zeng; Yan-Wen Li; Hui Li; Lei Xiang; Ce-Hui Mo (Environmental Science and Pollution Research, 2017)

Hybrid electrooxidation and adsorption process for the removal of ammonia in low concentration chloride wastewater - Jing Ding; Qing-Liang Zhao; Jun Zhang; Jun-Qiu Jiang; Wei Li; Hang Yu; Li-Kun Huang; Yun-Shu Zhang (Environmental Science and Pollution Research, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Improvement of anti-nutritional effect resulting from β-glucanase specific expression in the parotid gland of transgenic pigs - Li-zeng Guan; Jin-shun Cai; Shuai Zhao; Yu-ping Sun; Jing-lan Wang; Yong Jiang; Gang Shu; Qing-yan Jiang; Zhen-fang Wu; Qian-yun Xi; Yong-liang Zhang (Transgenic Research, 2017)

The dynamics of landscape-scale ecological connectivity based on least-cost model in Dongshan Island, China - Li-yun Wu; Dong-jin He; Wei-bin You; Zhi-rong Ji; Yong Tan; Li-li Zhao (Journal of Mountain Science, 2017)

Chemical constituents from the roots of Ampelopsis delavayana and their antibacterial activities - Shuang-Xi Mei; Xu-Hong Li; Li-Guo Yang; Xiao-Hui Li; Jia-Ying Xie; Qi Yao; Mei Su; Tao Cui; Jing-Kun Wang; Zhao-Yun Zhu (Natural Product Research, 2017)

Oleoylethanolamide attenuates apoptosis by inhibiting the TLR4/NF-κB and ERK1/2 signaling pathways in mice with acute ischemic stroke - Hao Zhou; Wu-shuang Yang; Ying Li; Tong Ren; Lu Peng; Han Guo; Jin-feng Liu; Yu Zhou; Yun Zhao; Li-chao Yang; Xin Jin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Inhibitory Effect of Endomorphin-2 Binding to the μ-Opioid Receptor in the Rat Pre-Bötzinger Complex on the Breathing Activity - Jian Qi; Hui Li; Ting-Bao Zhao; Ya-Cheng Lu; Ting Zhang; Jin-Lian Li; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2017)

Two new compounds from Trollius chinensis Bunge - Ya Jie-Shi; Lin Wei-Sang; Rui Yan; Qiang Zhao; Yang Zhang; Gui Yun-Zhao; Yun Cong-Li; Xue Chen; Chong Yu-Zhang; Hua Qiao; Guo Gang-Zhang (Journal of Natural Medicines, 2017)

Distribution and health risk assessment of dissolved heavy metals in the Three Gorges Reservoir, China (section in the main urban area of Chongqing) - Xin Zhao; Ting-Yong Li; Tao-Tao Zhang; Wei-Jun Luo; Jun-Yun Li (Environmental Science and Pollution Research, 2017)

Oxidized graphene-aggravated allergic asthma is antagonized by antioxidant vitamin E in Balb/c mice - Shuai Shang; Jinquan Li; Yun Zhao; Zhuge Xi; Zhisong Lu; Baizhan Li; Xu Yang; Rui Li (Environmental Science and Pollution Research, 2017)

cPKCγ-Modulated Autophagy in Neurons Alleviates Ischemic Injury in Brain of Mice with Ischemic Stroke Through Akt-mTOR Pathway - Haiping Wei; Yun Li; Song Han; Shuiqiao Liu; Nan Zhang; Li Zhao; Shujuan Li; Junfa Li (Translational Stroke Research, 2016)

Agmatine Prevents Adaptation of the Hippocampal Glutamate System in Chronic Morphine-Treated Rats - Xiao-Fei Wang; Tai-Yun Zhao; Rui-Bin Su; Ning Wu; Jin Li (Neuroscience Bulletin, 2016)

Genome-wide identification and functional analysis of the TIFY gene family in response to drought in cotton - Ge Zhao; Yun Song; Caixiang Wang; Hamama Islam Butt; Qianhua Wang; Chaojun Zhang; Zuoren Yang; Zhao Liu; Eryong Chen; Xueyan Zhang; Fuguang Li (Molecular Genetics and Genomics, 2016)

Joint AVO inversion in the time and frequency domain with Bayesian interference - Zhao-Yun Zong; Xing-Yao Yin; Kun Li (Applied Geophysics, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Nitrogen removal via simultaneous partial nitrification, anammox and denitrification (SNAD) process under high DO condition - Zhaoming Zheng; Jun Li; Jing Ma; Jia Du; Wei Bian; Yun Li; Yanzhuo Zhang; Baihang Zhao (Biodegradation, 2016)

Mineralization time and tectonic setting of the Zhengguang Au deposit in the Duobaoshan ore field, Heilongjiang Province, NE China - Yu-Jie Hao; Yun-Sheng Ren; Ming-Xin Duan; Xuan Zhao; Qun Yang; Kuang-Yin Tong; Chao Li (Arabian Journal of Geosciences, 2016)

Dietary lipid concentrations influence growth, liver oxidative stress, and serum metabolites of juvenile hybrid snakehead (Channa argus × Channa maculata) - Peng-Fei Zhao; Fa-Jian Li; Xiao-Ru Chen; Yong-Jun Chen; Shi-Mei Lin; Lu Zhang; Yun Li (Aquaculture International, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Chemical characteristics of rainwater in Sichuan basin, a case study of Ya’an - Yun-Chun Li; Meng Zhang; Man Shu; Steven Sai Hang Ho; Zi-Fang Liu; Xian-Xiang Wang; Xiao-Qing Zhao (Environmental Science and Pollution Research, 2016)

Illumina-based analysis of the rhizosphere microbial communities associated with healthy and wilted Lanzhou lily (Lilium davidii var. unicolor) plants grown in the field - Qianhan Shang; Guo Yang; Yun Wang; Xiukun Wu; Xia Zhao; Haiting Hao; Yuyao Li; Zhongkui Xie; Yubao Zhang; Ruoyu Wang (World Journal of Microbiology and Biotechnology, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Factors Associated with Thrombolysis Outcome in Ischemic Stroke Patients with Atrial Fibrillation - Qiuyun Zhao; Xiaobo Li; Wanli Dong; Min Ye; Yongjun Cao; Meijuan Zhang; Qiantao Cheng; Junshan Zhou; Guofang Chen; Ming Yu; Shanshan Hong; Xiue Wei; et al. (Neuroscience Bulletin, 2016)

Autophagy Promotes Peripheral Nerve Regeneration and Motor Recovery Following Sciatic Nerve Crush Injury in Rats - Hai-cheng Huang; Li Chen; Hai-xing Zhang; Sheng-fa Li; Pei Liu; Tian-yun Zhao; Chuan-xiang Li (Journal of Molecular Neuroscience, 2016)
Autophagy maintains cellular homeostasis by stimulating the lysosomal degradation of cytoplasmic structures, including damaged organelles and dysfunctional proteins. The role of autophagy in the renewal and regeneration of injured peripheral nerves remains poorly understood. The current study investigated the role of autophagy in peripheral nerve regeneration and motor function recovery following sciatic nerve crush injury in rats by stimulating or suppressing autophagy and detecting the presence of autophagosomes and LC3-II expression by electron microscopy and Western blotting, respectively. Neurobehavioral function was tested by CatWalk gait analysis 1, 2, 3, and 6 weeks after injury, and the expression of neurofilament (NF)-200 and myelin basic protein (MBP) at the injury site was examined by immunocytochemistry. Apoptosis at the lesion site was determined by the terminal deoxynucleotidyl transferase dUTP nick end labeling assay. Treatment of injured rats with the autophagy inducer rapamycin increased the number of autophagosomes and LC3-II expression while reducing the number of apoptotic cells at the lesion; this was associated with an upregulation of MBP and NF-200 expression and increased motor function recovery as compared to sham-operated rats and those that were subjected to crush injury but untreated. The opposite effects were observed in rats treated with the autophagy inhibitor 3-methyladenine. These data indicate that the modulation of autophagy in peripheral nerve injury could be an effective pharmacological approach to promote nerve regeneration and reestablish motor function.

Mechanisms of Intracellular Calcium Homeostasis in MC3T3-E1 Cells and Bone Tissues of Sprague-Dawley Rats Exposed to Fluoride - Xiao-qin Duan; Yan-hui Li; Xiu-yun Zhang; Zhi-tao Zhao; Ying Wang; Huan Wang; Guang-sheng Li; Ling Jing (Biological Trace Element Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Clinical validation of a novel real-time human papillomavirus assay for simultaneous detection of 14 high-risk HPV type and genotyping HPV type 16 and 18 in China - Hui Yang; Lie-Jun Li; Long-Xu Xie; Zhao-Yun Luo; Min Lu; Min Lin; Xiang-bin Zheng; Yue Huang; Li-Ye Yang (Archives of Virology, 2016)

The effect of different feeding rates on growth, feed efficiency and immunity of juvenile Penaeus monodon - Jin Niu; Xu Chen; Yun-Qiang Zhang; Li-Xia Tian; Hei-Zhao Lin; Jun Wang; Yun Wang; Yong-Jian Liu (Aquaculture International, 2016)

Serum Levels of Thioredoxin Are Associated with Stroke Risk, Severity, and Lesion Volumes - Meng-Hai Wu; Fang-Yu Song; Li-Ping Wei; Zhao-Yun Meng; Zhi-Qiang Zhang; Qin-De Qi (Molecular Neurobiology, 2016)

Responses of soil fungal community to the sandy grassland restoration in Horqin Sandy Land, northern China - Shao-Kun Wang; Xiao-An Zuo; Xue-Yong Zhao; Yu-Qiang Li; Xin Zhou; Peng Lv; Yong-Qing Luo; Jian-Ying Yun (Environmental Monitoring and Assessment, 2016)

Association of Serum Ferritin Level with Risk of Incident Abnormal Glucose Metabolism in Southwestern China: a Prospective Cohort Study - Fangli Zhou; Zhuoxian Zhao; Li Tian; Tianpeng Zheng; Yun Gao; Tao Chen; Fangfang Yan; Haoming Tian (Biological Trace Element Research, 2016)

Role of Rho Kinase and Fasudil on Synaptic Plasticity in Multiple Sclerosis - Chan Chen; Jie-Zhong Yu; Qiong Zhang; Yong-Fei Zhao; Chun-Yun Liu; Yan-Hua Li; Wan-Fang Yang; Cun-Gen Ma; Bao-Guo Xiao (NeuroMolecular Medicine, 2015)

Subcellular distribution and chemical forms of cadmium in a dark septate endophyte (DSE), Exophiala pisciphila - Fangdong Zhan; Yongmei He; Yuan Li; Tao Li; Yun-Ya Yang; Gurpal S. Toor; Zhiwei Zhao (Environmental Science and Pollution Research, 2015)

Evaluation of 90-day Repeated Dose Oral Toxicity, Glycometabolism, Learning and Memory Ability, and Related Enzyme of Chromium Malate Supplementation in Sprague-Dawley Rats - Weiwei Feng; Huiyu Wu; Qian Li; Zhaoxiang Zhou; Yao Chen; Ting Zhao; Yun Feng; Guanghua Mao; Fang Li; Liuqing Yang; Xiangyang Wu (Biological Trace Element Research, 2015)

Transcriptome profiling of trichome-less reveals genes associated with multicellular trichome development in Cucumis sativus - Jun-Long Zhao; Yun-Li Wang; Dan-Qing Yao; Wen-Ying Zhu; Long Chen; Huan-Le He; Jun-Song Pan; Run Cai (Molecular Genetics and Genomics, 2015)

Promoter analysis and RNA interference of CYP6ab4 in the silkworm Bombyx mori - Guo-Dong Zhao; Yi-Ling Zhang; Yun-Lei Liu; Bing Li; Yu-Hua Chen; Ya-Xiang Xu; Qing-You Xia; Wei-De Shen; Zheng-Guo Wei (Molecular Genetics and Genomics, 2015)

A new lignan with hypoglycemic activity from Tadehagi triquetrum - Jiani Wu; Cai yun Zhang; Tingting Zhang; Dan Zhao; Ni An; Youbin Li; Nailiang Zhu; Shuai Wang; Feng Chen; Xiaopo Zhang (Natural Product Research, 2015)

Simultaneous detection of IgG and IgM antibodies against a recombinant polyprotein PstS1-LEP for tuberculosis diagnosis - Jun-Li Li; Xiang-Yu Huang; Hong-Bing Chen; Xin-Jing Wang; Chuan-Zhi Zhu; Ming Zhao; Qing-De Song; Hai-Yan Huang; Li Xiao; Xiu-Yun He (Infectious Diseases, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Protective effect of L-carnitine in cyclophosphamide-induced germ cell apoptosis - Bin Zhu; Yan-fei Zheng; Yue-ying Zhang; Yun-song Cao; Lei Zhang; Xin-gang Li; Teng Liu; Zhao-zhu Jiao; Qi Wang; Zhi-gang Zhao (Journal of Zhejiang University-SCIENCE B, 2015)

Investigating the MicroRNAomes of Two Developmental Phases of Dendrocalamus latiflorus (Poaceae: Bambusoideae) Inflorescences - Xu-Yao Zhao; Xiao-Yan Wang; Lei Zhao; Xue-Mei Zhang; Si-Yun Chen; Peng-Fei Ma; Xiang-Yang Hu; De-Zhu Li; Zhen-Hua Guo (Plant Molecular Biology Reporter, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Palaeo-sea-ice changes on the North Icelandic shelf during the last millennium: Evidence from diatom records - LongBin Sha; Hui Jiang; YanGuang Liu; MeiXun Zhao; DongLing Li; ZhenLou Chen; Yun Zhao (Science China Earth Sciences, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Pretreatment with lipopolysaccharide attenuates diethylnitrosamine-caused liver injury in mice via TLR4-dependent induction of Kupffer cell M2 polarization - Xianjing Li; Zhuo Wang; Yulian Zou; Ermei Lu; Jingjing Duan; Hongbao Yang; Qijin Wu; Xiaona Zhao; Yun Wang; Linjun You; Ling He; Tao Xi; et al. (Immunologic Research, 2015)

Fluoride Affects Calcium Homeostasis by Regulating Parathyroid Hormone, PTH-Related Peptide, and Calcium-Sensing Receptor Expression - Ying Wang; Xiao-qin Duan; Zhi-tao Zhao; Xiu-yun Zhang; Huan Wang; Da-wei Liu; Guang-sheng Li; Ling Jing (Biological Trace Element Research, 2015)

Pitavastatin calcium improves endothelial function and delays the progress of atherosclerosis in patients with hypercholesterolemia - Jing Zhao; Hui-min Yan; Ya Li; Jia Wang; Lu Han; Zhi-hao Wang; Meng-xiong Tang; Wei Zhang; Yun Zhang; Ming Zhong (Journal of Zhejiang University-SCIENCE B, 2015)

Regional integrated environmental modeling system: development and application - Shuyu Wang; Congbin Fu; Helin Wei; Yun Qian; Zhe Xiong; Jinming Feng; Deming Zhao; Li Dan; Zhiwei Han; Bingkai Su; Ming Zhao; Yaocun Zhang; et al. (Climatic Change, 2015)

The Therapeutic Potential of Rho Kinase Inhibitor Fasudil Derivative FaD-1 in Experimental Autoimmune Encephalomyelitis - Yong-Fei Zhao; Xiang Zhang; Zhi-Bin Ding; Xing-Wang Yang; Hui Zhang; Jie-Zhong Yu; Yan-Hua Li; Chun-Yun Liu; Qing Zhang; Hong-Zhen Zhang; Cun-Gen Ma; Bao-Guo Xiao (Journal of Molecular Neuroscience, 2015)

Complications and Adverse Effects Associated with Intraoperative Nerve Monitoring During Thyroid Surgery Under General Anesthesia - Peng Chen; Feng Liang; Long-yun Li; Guo-qing Zhao (Cell Biochemistry and Biophysics, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Complete genome sequence of a novel human papillomavirus identified by metagenomic analysis from a child with diarrhea in China - Jie-mei Yu; Guoyan Zhao; Yuan-yun Ao; Li-li Li; David Wang; Zhao-jun Duan (Archives of Virology, 2015)

Rapid evaluation of reference evapotranspiration in Northern China - Shao-hua Zhao; Yong-hui Yang; Feng Zhang; Xin-xin Sui; Yun-jun Yao; Na Zhao; Qiuxiao Zhao; Chun-qiang Li (Arabian Journal of Geosciences, 2015)

Preparation and Optimization of Resveratrol Nanosuspensions by Antisolvent Precipitation Using Box-Behnken Design - Jifu Hao; Yun Gao; Jing Zhao; Jimei Zhang; Qiankui Li; Zhongxi Zhao; Jiyong Liu (AAPS PharmSciTech, 2015)

Tolerance and Antioxidant Response of a Dark Septate Endophyte (DSE), Exophiala pisciphila, to Cadmium Stress - Fangdong Zhan; Yongmei He; Tao Li; Yun-ya Yang; Gurpal S. Toor; Zhiwei Zhao (Bulletin of Environmental Contamination and Toxicology, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Fluoride Affects Calcium Homeostasis and Osteogenic Transcription Factor Expressions Through L-type Calcium Channels in Osteoblast Cell Line - Xiao-qin Duan; Zhi-tao Zhao; Xiu-yun Zhang; Ying Wang; Huan Wang; Da-wei Liu; Guang-sheng Li; Ling Jing (Biological Trace Element Research, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Two new truffles species, Tuber alboumbilicum and Tuber pseudobrumale from China - Shu-Hong Li; Lin-Yong Zheng; Cheng-Yi Liu; Yun Wang; Lin Li; Yong-Chang Zhao; Xiao-Lei Zhang; Mei Yang; Hai-Kuan Xiong; Yuan Qing; Li Wang; De-Qun Zhou (Mycological Progress, 2014)

ClC-3 deficiency protects preadipocytes against apoptosis induced by palmitate in vitro and in type 2 diabetes mice - Yun-Ying Huang; Xiong-Qin Huang; Li-Yan Zhao; Fang-Yun Sun; Wen-Liang Chen; Jie-Yi Du; Feng Yuan; Jie Li; Xue-Lian Huang; Jie Liu; Xiao-Fei Lv; Yong-Yuan Guan; et al. (Apoptosis, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

Antenatal taurine supplementation increases taurine content in intrauterine growth restricted fetal rat brain tissue - Fang Li; Hui-Yun Teng; Jing Liu; Hua-Wei Wang; Li Zeng; Li-Fang Zhao (Metabolic Brain Disease, 2014)

Establishment of Rat Model of Central Venous Catheter (CVC): Associated Infection and Evaluation of the Virulence of Bacterial Biofilms - Lian-Hua Ye; Yun-Chao Huang; Feng-Li Guo; Xin Liu; Guang-Qiang Zhao; Lin-Can Duan; Cong-Guo Jin (Cell Biochemistry and Biophysics, 2014)

Early channel transurethral resection of the prostate for patients with urinary retention after brachytherapy - You-yun Zhang; Zhi-gen Zhang; Yan-lan Yu; Yi-cheng Chen; Kang-xin Ni; Ming-chao Wang; Wei-ping Zhao; Faisal Rehman; Shaw P. Wan; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2014)

Effects of Mercury on Oxidative Stress and Gene Expression of Potential Biomarkers in Larvae of the Chinese Rare Minnow Gobiocypris Rarus - Zhi-Hua Li; Lu Chen; Yan-Hua Wu; Ping Li; Yun-Feng Li; Zhao-Hui Ni (Archives of Environmental Contamination and Toxicology, 2014)

Mapping QTLs for potassium-deficiency tolerance at the seedling stage in wheat (Triticum aestivum L.) - Yong Zhao; Xiao-yun Li; Shu-hua Zhang; Jie Wang; Xue-fang Yang; Ji-chun Tian; Yan Hai; Xue-ju Yang (Euphytica, 2014)

Prelaunch calibration and primary results from in-orbit calibration of the atmospheric correction microwave radiometer (ACMR) on the HY-2A satellite of China - Zhenzhan Wang; Dehai Zhang; Yun Li; Jin Zhao (International Journal of Remote Sensing, 2014)

Role of Ras, ERK, and Akt in glucocorticoid-induced differentiation of embryonic rat somatotropes in vitro - Wen Ming Lv; Yan Zhao; Guang Yang; Shi Yun Dong; Guang Hui Zhang; Yu Zhang; Guo Zhong Li; Yu Cheng (Molecular and Cellular Biochemistry, 2014)

Mapping Soil Particle Size Fractions Using Compositional Kriging, Cokriging and Additive Log-ratio Cokriging in Two Case Studies - Xiao-Lin Sun; Yun-Jin Wu; Hui-Li Wang; Yu-Guo Zhao; Gan-Lin Zhang (Mathematical Geosciences, 2014)

M1 muscarinic acetylcholine receptor in Alzheimer’s disease - Shangtong Jiang; Yanfang Li; Cuilin Zhang; Yingjun Zhao; Guojun Bu; Huaxi Xu; Yun-Wu Zhang (Neuroscience Bulletin, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Screening wheat genotypes for resistance to black point and the effects of diseased kernels on seed germination - Qiao-Yun Li; Zhao Qin; Yu-Mei Jiang; Chun-Cai Shen; Zong-Biao Duan; Ji-Shan Niu (Journal of Plant Diseases and Protection, 2014)

ABCD2 Score May Discriminate Minor Stroke from TIA on Patient Admission - Hui Zhao; Qingjie Li; Mengru Lu; Yuan Shao; Jingwei Li; Yun Xu (Translational Stroke Research, 2014)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

Role of Angptl4 in vascular permeability and inflammation - Liang Guo; Shao-Ying Li; Fu-Yun Ji; Yun-Feng Zhao; Yu Zhong; Xue-Jun Lv; Xue-Ling Wu; Gui-Sheng Qian (Inflammation Research, 2014)

Changes in some soil properties induced by re-conversion of cropland into grassland in the semiarid steppe zone of Inner Mongolia, China - Zhi-Hua Zhang; Xiao-Yan Li; Zhi-Yun Jiang; Hai-Ying Peng; Liu Li; Guo-Qin Zhao (Plant and Soil, 2013)

Erratum to: Expression Analysis of Anthocyanin Biosynthetic Genes in Different Colored Sweet Cherries (Prunus avium L.) During Fruit Development - Yun Liu; Xinjie Shen; Kai Zhao; Yue Ben; Xinwei Guo; Xiaoming Zhang; Tianhong Li (Journal of Plant Growth Regulation, 2013)

Expression Analysis of Anthocyanin Biosynthetic Genes in Different Colored Sweet Cherries (Prunus avium L.) During Fruit Development - Yun Liu; Xinjie Shen; Kai Zhao; Yue Ben; Xinwei Guo; Xiaoming Zhang; Tianhong Li (Journal of Plant Growth Regulation, 2013)

The Effect of Brominated Furanones on The Formation of Staphylococcus aureus Biofilm on PVC - Lei Yujie; Xu Geng; Yun-chao Huang; Yang Li; Kaiyun Yang; Lianhua Ye; Xiaobo Chen; Guangqiang Zhao; Chen Yin (Cell Biochemistry and Biophysics, 2013)

Molecular characterization of novel haplotypes of eIF4E family in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Shuan-Tao Liu; Zhi-Gang Zhang; Qiao-Yun Li; Shu-Fen Wang; Zhi-Zhong Zhao; Jin-Dong Lu; Wen-Ling Xu; Xian-Xian Liu; Wei-Min Fu (Genes & Genomics, 2013)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Seasonally variable intestinal metagenomes of the red palm weevil ( R hynchophorus ferrugineus ) - Shangang Jia; Xiaowei Zhang; Guangyu Zhang; An Yin; Sun Zhang; Fusen Li; Lei Wang; Duojun Zhao; Quanzheng Yun; Tala; Jixiang Wang; Gaoyuan Sun; et al. (Environmental Microbiology, 2013)
Summary The intestinal microbes residing in the red palm weevil ( RPW , R hynchophorus ferrugineus ) larva consume tender interior fibrous tissues of date palm trunks. The understanding of such microbiota at molecular level provides vital clues for the biological control of this devastating pest. Using pyrosequencing and shotgun strategy, we first study taxonomic profiles of the microbiota sampled at different months ( M arch, J uly and N ovember), and then confirm the impact of high‐temperature stress on the microbial populations based on data from 16S rRNA amplicons using both field and laboratory samples. We further identify K lebsiella pneumoniae in N ovember and L actococcus lactis in J uly as the dominant species of the microbiota. We find that the RPW gut microbiota degrades polysaccharides and sucrose with hydrolases and that different active bacterial species in N ovember and J uly are responsible for the symbiotic relationship between the microbiota and the host. Our results provide vital information for pest control and cellulolytic bacterial species characterization.

MK-2206 induces cell cycle arrest and apoptosis in HepG2 cells and sensitizes TRAIL-mediated cell death - Peng Jiao; Yun-Sheng Zhou; Juan-Xia Yang; Ya-Li Zhao; Qiang-Qiang Liu; Chuang Yuan; Feng-Ze Wang (Molecular and Cellular Biochemistry, 2013)

Erratum to: Genetic variants of fibroblast growth factor receptor 2 (FGFR2) are associated with breast cancer risk in Chinese women of the Han nationality - Fan Chen; Min Lu; Yun Xue; Jing Zhou; Feifei Hu; Xin Chen; Zhanqin Zhao; Yang Li; XingGuo Wang (Immunogenetics, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

The expression and phylogenetic analysis of four AP3-like paralogs in the stamens, carpels, and single-whorl perianth of the paleoherb Asarum caudigerum - Yin-He Zhao; Zachary Larson-Rabin; De-Zhu Li; Guo-Ying Wang; Seng Peng; Cheng-Yun Li (Molecular Biology Reports, 2013)

Iodine Excess Induces Hepatic Steatosis Through Disturbance of Thyroid Hormone Metabolism Involving Oxidative Stress in BaLB/c Mice - Yun Xia; Wei Qu; Li-Na Zhao; Hao Han; Xue-Feng Yang; Xiu-Fa Sun; Li-Ping Hao; Jian Xu (Biological Trace Element Research, 2013)

Threats to China’s biological resources posed by expanding international trade - Yun Song; Zhu Zhao; Jin Xu; Ke Chen; Mingfu Li (Biodiversity and Conservation, 2013)

β-receptor blocker influences return of spontaneous circulation and chemical examination in rats during cardiopulmonary resuscitation - Xiao-jing Zhao; Zhuo Pen; Ping Li; Er-xiu Chen; Jian Liu; Yan-xia Gao; Yun-xia Ren; Li-jun Li (Journal of Zhejiang University-SCIENCE B, 2013)

EMT and CSC-like properties mediated by the IKKβ/IκBα/RelA signal pathway via the transcriptional regulator, Snail, are involved in the arsenite-induced neoplastic transformation of human keratinocytes - Rongrong Jiang; Yuan Li; Yuan Xu; Yun Zhou; Ying Pang; Lu Shen; Yue Zhao; Jianping Zhang; Jianwei Zhou; Xinru Wang; Qizhan Liu (Archives of Toxicology, 2013)

Age and tectonic setting of the first orogenic gold deposit discovered in the Yanbian Region, NE China - Hua-Lei Zhao; Yun-Sheng Ren; He-Nan Hou; Hui Wang; Nan Ju; Cong Chen; Chen-Hui Li (International Geology Review, 2013)

Iron Overload Inhibits Osteoblast Biological Activity Through Oxidative Stress - Yin-Feng He; Yong Ma; Chao Gao; Guo-yang Zhao; Lin-Lin Zhang; Guang-Fei Li; Yun-Zhi Pan; Kai Li; You-Jia Xu (Biological Trace Element Research, 2013)

Lipopolysaccharide-induced failure of the gut barrier is site-specific and inhibitable by growth hormone - Chao Yue; Wei Wang; Wei-Liang Tian; Qian Huang; Ri-Sheng Zhao; Yun-Zhao Zhao; Qiu-Rong Li; Jie-Shou Li (Inflammation Research, 2013)

Microspore embryogenesis and production of haploid and doubled haploid plants in carrot (Daucus carota L.) - Jin-Rong Li; Fei-Yun Zhuang; Cheng-Gang Ou; Hong Hu; Zhi-Wei Zhao; Ji-Hua Mao (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Coastal Wetlands of China: Changes from the 1970s to 2007 Based on a New Wetland Classification System - Ping Zuo; Yun Li; Chang-An Liu; Shu-He Zhao; Dao-Ming Guan (Estuaries and Coasts, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Aggravated inflammation and increased expression of cysteinyl leukotriene receptors in the brain after focal cerebral ischemia in AQP4-deficient mice - Wen-Zhen Shi; Chun-Zhen Zhao; Bing Zhao; Qiao-Juan Shi; Li-Hui Zhang; Yan-Fang Wang; San-Hua Fang; Yun-Bi Lu; Wei-Ping Zhang; Er-Qing Wei (Neuroscience Bulletin, 2012)

Effects of recombinant hIL-2-Luffin P1 immunotoxin combining with arotinoid ethylester on the proliferation and apoptosis of Hut-78 cells - Shu-lei Liu; Wei He; Ru-peng Wang; Zhi Li; Ju Wu; Yun Zhao; Xiao-hong Hu (Molecular & Cellular Toxicology, 2012)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Characterization of carbonic anhydrase II from Chlorella vulgaris in bio-CO2 capture - Li Li; Ming-lai Fu; Yong-hao Zhao; Yun-tian Zhu (Environmental Science and Pollution Research, 2012)

Building detection in an urban area using lidar data and QuickBird imagery - Lei Chen; Shuhe Zhao; Wenquan Han; Yun Li (International Journal of Remote Sensing, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Molecular cloning and functional characterization of a novel apple MdCIPK6L gene reveals its involvement in multiple abiotic stress tolerance in transgenic plants - Rong-Kai Wang; Ling-Li Li; Zhong-Hui Cao; Qiang Zhao; Ming Li; Ling-Yun Zhang; Yu-Jin Hao (Plant Molecular Biology, 2012)

A comparative study of the characteristics of two Coxsackie A virus type 16 strains (genotype B) - ErXia Yang; Heng Zhao; Ying Zhang; JianSheng Liu; Yun Liao; LiChun Wang; PingFang Cui; LiXian Yang; LongDing Liu; ChengHong Dong; ShaoZhong Dong; CongWen Shao; et al. (Science China Life Sciences, 2012)

QTL mapping for seedling traits in wheat grown under varying concentrations of N, P and K nutrients - Ying Guo; Fan-mei Kong; Yun-feng Xu; Yan Zhao; Xue Liang; Ying-ying Wang; Diao-guo An; Si-shen Li (Theoretical and Applied Genetics, 2012)

Cutaneous Protothecosis in Patient with Diabetes Mellitus and Review of Published Case Reports - Qiang-Qiang Zhang; Li Li; Li-Ping Zhu; Ying Zhao; Yun-Ru Wang; Jun-hao Zhu; Min Zhu (Mycopathologia, 2012)

Molecular cloning and expression analysis of a RGA-like gene responsive to plant hormones in Brassica napus - Yong Gao; Jianmin Chen; Yun Zhao; Tingting Li; Maolin Wang (Molecular Biology Reports, 2012)

Genetic diversity and geographic differentiation analysis of duckweed using inter-simple sequence repeat markers - Huiling Xue; Yao Xiao; Yanling Jin; Xinbo Li; Yang Fang; Hai Zhao; Yun Zhao; Jiafa Guan (Molecular Biology Reports, 2012)

Effects of insulin-like growth factor-1 on the properties of mesenchymal stem cells in vitro - Yu-li Huang; Ruo-feng Qiu; Wei-yi Mai; Jian Kuang; Xiao-yan Cai; Yu-gang Dong; Yun-zhao Hu; Yuan-bin Song; An-ping Cai; Zhi-gao Jiang (Journal of Zhejiang University-SCIENCE B, 2012)

Removal of genotoxicity in chlorinated secondary effluent of a domestic wastewater treatment plant during dechlorination - Qian-Yuan Wu; Yi Li; Hong-Ying Hu; Ya-Nan Ding; Huang Huang; Feng-Yun Zhao (Environmental Science and Pollution Research, 2012)

Genetic variants of fibroblast growth factor receptor 2 (FGFR2) are associated with breast cancer risk in Chinese women of the Han nationality - Fan Chen; Min Lv; Yun Xue; Jing Zhou; Feifei Hu; Xin Chen; Zhanqin Zhao; Yang Li; XingGuo Wang (Immunogenetics, 2012)

Cloning, expression and characterization of a new lipase from Yarrowia lipolytica - Heyun Zhao; Lina Zheng; Xiaofeng Wang; Yun Liu; Li Xu; Yunjun Yan (Biotechnology Letters, 2011)

Gender-Specific Association Between ACE Gene I/D Polymorphism and Blood Pressure Response to Hydrochlorothiazide in Han Chinese Hypertensive Patients - Yun Li; Peng Yang; Shouling Wu; Juxiang Yuan; Chong Shen; Ying Wu; Dandan Zhao; Qi Ren; Fumin Feng; Weijun Guan (Biochemical Genetics, 2011)

In Vitro Model of Bacterial Biofilm Formation on Polyvinyl Chloride Biomaterial - Guang-qiang Zhao; Lian-hua Ye; Yun-chao Huang; Da-kuan Yang; Li Li; Geng Xu; Yu-jie Lei (Cell Biochemistry and Biophysics, 2011)

Effects of rhizobial inoculation, cropping systems and growth stages on endophytic bacterial community of soybean roots - Yun Zeng Zhang; En Tao Wang; Mao Li; Qin Qin Li; Yan Ming Zhang; Shuang Jin Zhao; Xiu Ling Jia; Li Hua Zhang; Wen Feng Chen; Wen Xin Chen (Plant and Soil, 2011)

A Novel PrP Partner HS-1 Associated Protein X-1 (HAX-1) Protected the Cultured Cells Against the Challenge of H2O2 - Yuan-Yuan Jing; Xiao-Li Li; Qi Shi; Zhao-Yun Wang; Yan Guo; Ming-Ming Pan; Chan Tian; Shu-Ying Zhu; Cao Chen; Han-Shi Gong; Jun Han; Chen Gao; et al. (Journal of Molecular Neuroscience, 2011)

Unusual CT Hyperattenuating Dermoid Cyst of Cerebellum: A New Case Report and Literature Review - Zhao-Jian Li; Yuan-Xin Miao; Peng Sun; Yu-Jun Li; Yi-He Dou; Jian Xu; Xin Chen; Yun-Xia Jiang (The Cerebellum, 2011)

Vascular Endothelial Growth Factor Increases Permeability of the Blood–Tumor Barrier via Caveolae-Mediated Transcellular Pathway - Li-ni Zhao; Zhi-hang Yang; Yun-hui Liu; Hao-qiang Ying; Hua Zhang; Yi-xue Xue (Journal of Molecular Neuroscience, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Biodegradation of malachite green by Pseudomonas sp. strain DY1 under aerobic condition: characteristics, degradation products, enzyme analysis and phytotoxicity - Lin-Na Du; Sheng Wang; Gang Li; Bing Wang; Xiao-Ming Jia; Yu-Hua Zhao; Yun-Long Chen (Ecotoxicology, 2011)

Isolation and characterization of a G protein γ subunit gene responsive to plant hormones and abiotic stresses in Brassica napus L - Yong Gao; Tingting Li; Yun Zhao; Caixia Ren; Yiqiong Zhang; Maolin Wang (Acta Physiologiae Plantarum, 2011)

Polymorphism of prion protein gene in sheep of Inner Mongolian, China - Cai-Xia Han; Hong-Xiang Liu; Yi-Xin Lu; Ming-Xin Song; De-Ming Zhao; Xiang-Mei Zhou; Li-Feng Yang; Xiao-Yun Li (Virus Genes, 2011)

A GA-insensitive dwarf mutant of Brassica napus L. correlated with mutation in pyrimidine box in the promoter of GID1 - Huapeng Li; Yun Wang; Xiaocheng Li; Yong Gao; Zhijun Wang; Yun Zhao; Maolin Wang (Molecular Biology Reports, 2011)

Isolation and characterization of gene encoding G protein α subunit protein responsive to plant hormones and abiotic stresses in Brassica napus - Yong Gao; Tingting Li; Yang Liu; Caixia Ren; Yun Zhao; Maolin Wang (Molecular Biology Reports, 2010)

IL-6/STAT3/TFF3 signaling regulates human biliary epithelial cell migration and wound healing in vitro - Gui-xing Jiang; Xiang-yu Zhong; Yun-fu Cui; Wei Liu; Sheng Tai; Zhi-dong Wang; Yu-guang Shi; Shi-yong Zhao; Chun-long Li (Molecular Biology Reports, 2010)

Cloning and Characterization of a G Protein β Subunit Gene Responsive to Plant Hormones and Abiotic Stresses in Brassica napus - Yong Gao; Yun Zhao; Tingting Li; Caixia Ren; Yang Liu; Maolin Wang (Plant Molecular Biology Reporter, 2010)

Effects of Manganese Deficiency on Spectral Characteristics and Oxygen Evolution in Maize Chloroplasts - Xiaolan Gong; Ying Wang; Chao Liu; Sisi Wang; Xiaoyang Zhao; Min Zhou; Na Li; Yun Lu; Fashui Hong (Biological Trace Element Research, 2010)

Two-stent strategy for renal artery stenosis with bifurcation lesion - Hong-bing Yan; Bin Zheng; Zheng Wu; Jian Wang; Han-jun Zhao; Li Song; Yun-peng Chi (Journal of Zhejiang University-SCIENCE B, 2010)

Distinct expression of three estrogen receptors in response to bisphenol A and nonylphenol in male Nile tilapias (Oreochromis niloticus) - Weiren Huang; Yong Zhang; Xiaoping Jia; Xilan Ma; Shuisheng Li; Yun Liu; Pei Zhu; Danqi Lu; Huihong Zhao; Wenna Luo; Shibai Yi; Xiaochun Liu; et al. (Fish Physiology and Biochemistry, 2010)

Effects of synaptic plasticity regulated by 17β-estradiol on learning and memory in rats with Alzheimer’s disease - Xiu-Li Shang; Jiu-Han Zhao; Yun-Peng Cao; Yi-Xue Xue (Neuroscience Bulletin, 2010)

Evidence for the Formation of the Male Gynogenetic Fish - Shaojun Liu; Qinbo Qin; Yuequn Wang; Hong Zhang; Rurong Zhao; Chun Zhang; Jing Wang; Wei Li; Lin Chen; Jun Xiao; Kaikun Luo; Min Tao; et al. (Marine Biotechnology, 2010)

Characterization of the gibberellic acid response of the Brassica napus L. em. Metzg. dwarf mutant NDF-1 - Yong Gao; Tingting Li; Yun Zhao; Wei Liu; Maolin Wang (Genetic Resources and Crop Evolution, 2010)

Mycotoxin Ochratoxin A-induced cell death and changes in oxidative metabolism of Arabidopsis thaliana - Xiao-Li Peng; Wen-Tao Xu; Yan Wang; Kun-Lun Huang; Zhi-hong Liang; Wei-wei Zhao; Yun-Bo Luo (Plant Cell Reports, 2010)

Molecular cloning and expression analysis of an F-box protein gene responsive to plant hormones in Brassica napus - Yong Gao; Yun Zhao; Tingting Li; Yang Liu; Caixia Ren; Maolin Wang (Molecular Biology Reports, 2010)

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells - Yun-mei Yang; Wei-dong Huang; Qiang-min Xie; Zhe-rong Xu; Qi-jiang Zhao; Xi-mei Wu; Fen-fen Li; Xin-wei Dong (Inflammation Research, 2010)

Extended expression of B-class MADS-box genes in the paleoherb Asarum caudigerum - Yin-He Zhao; Michael Möller; Jun-Bo Yang; Ting-Song Liu; Jin-Feng Zhao; Li-Na Dong; Jin-Peng Zhang; Cheng-Yun Li; Guo-Ying Wang; De-Zhu Li (Planta, 2010)

Analysis of two sequence variants in peroxisome proliferator activated receptor gamma gene in Tajik population at high altitudes and Han population at low altitudes in China - Xiao-Ling Liu; Feng-Lin Zhang; Zhi-Yong Zhou; Hua-Lu Zhao; Guo-Min Shen; Wu-Yun Baohan; Zi-Yuan Duan; Wei Li; Jun-Wu Zhang (Molecular Biology Reports, 2010)

Isolation of polymorphic microsatellite markers from amphioxus (Branchiostoma belcheri) and a test of cross-species amplification - Yun-Guo Liu; Ling-Xiao Liu; Zhao-Xia Li; Fang-Zhen Li; Chun-Ying Liu (Conservation Genetics Resources, 2009)

Gene mapping and expression analysis of a novel mutantreproduce organs absent (roa) in rice - Nan Wang; Xian-Chun Sang; Yun-Feng Li; Ying-Hua Ling; Fang-Ming Zhao; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

Production and cytogenetic characterization of intertribal somatic hybrids between Brassica napus and Isatis indigotica and backcross progenies - Xue-zhu Du; Xian-hong Ge; Xing-cheng Yao; Zhi-gang Zhao; Zai-yun Li (Plant Cell Reports, 2009)

Genetic and histological characterization of a novel recessive genic male sterile line of Brassica napus derived from a cross with Capsella bursa-pastoris - Hai-Feng Chen; Xian-Hong Ge; Xue-Zhu Du; Zhi-Gang Zhao; Zai-Yun Li (Euphytica, 2009)

Toxic Effects of Copper on Antioxidative and Metabolic Enzymes of the Marine Gastropod, Onchidium struma - Xiao-bo Li; Xue-li Hou; Qian Mao; Yun-long Zhao; Yong-xu Cheng; Qun Wang (Archives of Environmental Contamination and Toxicology, 2009)

Isolation and Characteristics of the CN Gene, a Tobacco Mosaic Virus Resistance N Gene Homolog, from Tobacco - Gai-Yun Zhang; Ming Chen; Jia-Ming Guo; Tong-Wen Xu; Lian-Cheng Li; Zhao-Shi Xu; You-Zhi Ma; Xue-Ping Chen (Biochemical Genetics, 2009)

Effect of the quality of the interaction data on predicting protein function from protein-protein interactions - Qing-Shan Ni; Zheng-Zhi Wang; Gang-Guo Li; Guang-Yun Wang; Ying-Jie Zhao (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Production and characterization of intergeneric somatic hybrids between Brassica napus and Orychophragmus violaceus and their backcrossing progenies - Zhi-gang Zhao; Ting-ting Hu; Xian-Hong Ge; Xue-zhu Du; Li Ding; Zai-yun Li (Plant Cell Reports, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Phylogenetic analysis of epiphytic marine bacteria on Hole-Rotten diseased sporophytes of Laminaria japonica - Gaoge Wang; Li Shuai; Yun Li; Wei Lin; Xiaowei Zhao; Delin Duan (Journal of Applied Phycology, 2008)

Losartan reduced connexin43 expression in left ventricular myocardium of spontaneously hypertensive rats - Li-li Zhao; Hong-juan Chen; Jun-zhu Chen; Min Yu; Yun-lan Ni; Wei-fang Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Chromosome elimination and fragment introgression and recombination producing intertribal partial hybrids from Brassica napus × Lesquerella fendleri crosses - Xue-Zhu Du; Xian-Hong Ge; Zhi-Gang Zhao; Zai-Yun Li (Plant Cell Reports, 2008)

Effects of Water-borne Copper on the Y-organ and Content of 20-hydroxyecdysone in Eriocheir sinensis - Zhi-biao Yang; Yun-long Zhao; Na Li; Jian Yang; Xiu-guo Hua (Archives of Environmental Contamination and Toxicology, 2008)

Simulation of terrestrial dust devil patterns - Zhaolin Gu; Jian Qiu; Yongzhi Zhao; Yun Li (Advances in Atmospheric Sciences, 2008)

Isolation and molecular characterization of the Triticum aestivum L. ethylene-responsive factor 1 (TaERF1) that increases multiple stress tolerance - Zhao-Shi Xu; Lan-Qin Xia; Ming Chen; Xian-Guo Cheng; Rui-Yue Zhang; Lian-Cheng Li; Yun-Xiang Zhao; Yan Lu; Zhi-Yong Ni; Li Liu; Zhi-Gang Qiu; You-Zhi Ma (Plant Molecular Biology, 2007)

A new linearly-combined bi-exponential model for kinetic analysis of the isometric relaxation process of Bufo gastrocnemius under electric stimulation in vitro - Rui Guo; Sheng-bing Li; Li-na Zhao; Yun-sheng Zhao; Wei Lu; Pei Yuan; Ping Deng; Fei Liao (Journal of Zhejiang University-SCIENCE B, 2007)

Induction and origin of adventitious shoots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Man Zhao; Sheng Ma; Ya-Ming Ge; Ming-Fang Zhang; Li-Ping Chen (Plant Cell Reports, 2007)

Highly efficient Agrobacterium-mediated transformation of embryogenic cell suspensions of Musa acuminata cv. Mas (AA) via a liquid co-cultivation system - Xia Huang; Xue-Lin Huang; Wang Xiao; Jie-Tang Zhao; Xue-Mei Dai; Yun-Feng Chen; Xiao-Ju Li (Plant Cell Reports, 2007)

Hydrogen peroxide-induced chlorophyll a bleaching in the cytochrome b 6 f complex: a simple and effective assay for stability of the complex in detergent solutions - Xiao-Bo Chen; Xiao-Hui Zhao; Yi Zhu; Yan-Dao Gong; Liang-Bi Li; Jian-Ping Zhang; Ting-Yun Kuang (Photosynthesis Research, 2007)

Effect of Waterborne Copper on the Microstructures of Gill and Hepatopancreas in Eriocheir sinensis and Its Induction of Metallothionein Synthesis - Zhi-Biao Yang; Yun-Long Zhao; Na Li; Jian Yang (Archives of Environmental Contamination and Toxicology, 2007)

rAAV-mediated angiogenin gene transfer induces angiogenesis and modifies left ventricular remodeling in rats with myocardial infarction - Xiao-Yan Zhao; Shen-Jiang Hu; Jiang Li; Yun Mou; Chi-Fung Chan; Juan Jin; Jian Sun; Zhao-Hui Zhu (Journal of Molecular Medicine, 2006)

EfficientAgrobacterium-mediated transformation of rice by phosphomannose isomerase/mannose selection - Ding Zai-Song; Zhao Ming; Jing Yu-Xiang; Li Liang-Bi; Kuang Ting-Yun (Plant Molecular Biology Reporter, 2006)

Agrobacterium-mediated transformation of cotton (Gossypium hirsutum L. cv. Zhongmian 35) using glyphosate as a selectable marker - Fu-Yong Zhao; Yun-Feng Li; Peilin Xu (Biotechnology Letters, 2006)

Evaluation of a kinetic uricase method for serum uric acid assay by predicting background absorbance of uricase reaction solution with an integrated method - Fei Liao; Yun-sheng Zhao; Li-na Zhao; Jia Tao; Xiao-yun Zhu; Lan Liu (Journal of Zhejiang University-SCIENCE B, 2006)

Decreased cardiac sarcoplasmic reticulum Ca2+-ATPase activity contributes to cardiac dysfunction in streptozotocin-induced diabetic rats - Xiao-Yan Zhao; Shen-Jiang Hu; Jiang Li; Yun Mou; Bao-Ping Chen; Qiang Xia (Journal of Physiology and Biochemistry, 2006)

A novel technique of three-dimensional reconstruction segmentation and analysis for sliced images of biological tissues - Jing Li; Hai-yan Zhao; Xing-yun Ruan; Yong-qing Xu; Wei-zheng Meng; Kun-peng Li; Jing-qiang Zhang (Journal of Zhejiang University-SCIENCE B, 2005)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)

Frame design of remote sensing monitoring for volcanic activities in Changbai mountains - Li-qun Bo; Yun-ping Zhao; Ren-kui Hua (Chinese Geographical Science, 2003)

Functional analysis of the rice AP3 homologue OsMADS16 by RNA interference - Han Xiao; Yun Wang; Daofeng Liu; Wemming Wang; Xiaobing Li; Xianfeng Zhao; Jichen Xu; Wenxue Zhai; Lihuang Zhu (Plant Molecular Biology, 2003)